Digital image analysis coupled with machine learning for rapid assessment of coffee of various roasting degrees and prediction of caffeine and chlorogenic acid content - Zhenqing Meng; Lin Li; Chunyan Liu; Ruiyuan Zhang; Yicheng Lei; Huiwen Pang; Chen Chen; Li Li; Fang Liu (Food Control, 2026)

Seismic reservoir characterization of deep carbonates under complex overburden: a lithofacies-association zonation workflow, Longwangmiao Formation, Sichuan Basin - Lei Tan; Yuanzhi Zhou; Junliang Li; Linzhi Zhang; Ya Zhang; Pingchao Fang; Minzhi Zhang; Bowen Liu; Longyan Yin; Lin Qiao; Mingzhi Kuang; Hong Liu (Carbonates and Evaporites, 2026)

Fulvic acid-iron colloid promotes the migration of As(III) in porous media - Yanhao Li; Youru Yao; Xinyi Wang; Huimin Zhang; Fengman Fang; Yuesheng Lin; Zhiming Zhang; Qing Ji; Jia Yu (Journal of Contaminant Hydrology, 2026)

Research on cross-domain translation method for core and electrical imaging images based on CUT - Yang Chen; Sinan Fang; Hongtao Wu; Hao Ma; Guilan Lin; Manxin Li; Chenxi Xue; Zeyu Zhang (Journal of Applied Geophysics, 2026)

Delta dynamics: Insights from high-density OSL chronology in the Han River Delta, Northern South China Sea - Ping Lai; Gui Long; Tiantian Huang; Guanjun Xu; Zibin Fang; Ziyuan Wu; Yuexin Liu; Penghui Lin; Xiwen Nong; Xiaojian Zeng; Hongwei Li; Zhongping Lai (Geomorphology, 2026)

Poly(phenol-imidazole) nanosheets engineered multifunctional hydrogel for promotion of infected diabetic wound healing - Jia Xin Yu; Lu Yao Li; Yu Fan; Piao Zheng; Sha Yang; Qi Fang Liu; Cai Juan Huang; Ya Lin Cao; Yang You (Chemical Engineering Journal, 2026)

Vacancy engineering triggers Cu-O-Ti superexchange: Spatial charge separation and synchronous utilization for enhanced Fenton-like performance - Zhimo Fang; Zhou Zhou; Xiaomeng Li; Dongyang Li; Bin Hu; Haoyu Wang; Lin Zhang; Qin Dai; Kai Li; Yao Kong; Shiguan Yang; Qiang Lu (Chemical Engineering Journal, 2026)

Broodstock pairing density as a management strategy to modulate behavior and enhance reproductive efficiency in the pot-bellied seahorse (Hippocampus abdominalis) - Fengyuan Shen; Guangjie Fang; Hui Xu; Yuanhao Ren; Siping Li; Lingzhi Li; TingTing Lin (Applied Animal Behaviour Science, 2026)

Unlocking the potential in municipal reclaimed water electrolysis for hydrogen production: Identification of the primary water matrix - Zongping Wang; Haoran Chen; Zhenbin Chen; Yunfei Li; Ang Lu; Yujie Cheng; Guosen Zhang; Ge Li; Shunjie Zhu; Lin Li; Lizhi Huang; Jiakun Fang; et al. (Water Research, 2026)

Arginine and putrescine ameliorate heat stress-induced testicular inflammation and apoptosis via inhibiting endoplasmic reticulum stress in mice - Kun Wu; Chenglong Yu; Guangmang Liu; Yong Zhuo; Bin Feng; Lianqiang Che; Shengyu Xu; Lun Hua; Jian Li; Zhengfeng Fang; De Wu; Yan Lin (Theriogenology, 2026)

Structure and bioactivity of protolimonoids from the root bark of Dictamnus dasycarpus Turcz. - Hua Yue; Zi-Xuan Li; Zi-Tong Hao; Dan Zeng; Jie Bao; Ling-Zhi Zhang; Xue-Man Lin; Hua Sun; Shu-Fang Li; Su-Juan Wang (Phytochemistry, 2026)

Mechanisms and applications of multifunctional low-temperature plasma technology for enhancing food safety - Jun Yan; Xue Yuan; Marie-Laure Fauconnier; Xiaoming Fang; Zhiqiang Kong; Lin Li; Bei Fan; Jesus Simal-Gandara; Minmin Li (Food Control, 2026)

Investigations on ballistic behaviour of additive manufactured 316L stainless steel corrugated sandwich panels filled with ultra-high performance geopolymer concrete - Jian Liu; Cunyi Li; Guobin Li; Sihao Lin; Ming-Xiang Xiong; Jianguang Fang (Engineering Structures, 2026)

Molecular mechanisms of neutron irradiation damage in CL-20: A multiscale modeling approach from collision cascades to real-space defect mapping - Wei-Yi Li; Tao Wang; Rong Liu; Yu-Heng Li; Wan-Xiao Guo; Xi-Yao Yun; Yi-Lin Fang; Jin-Tao Wang; Ning Gao (Chemical Engineering Journal, 2026)

Scalable cancer cell-derived liposome capable of homologous tumor-homing to encapsulate near-infrared light-responsive drug delivery nanocomposites for enhanced combination therapy - Fang-Yi Hsu; Wen-Jyun Wang; Li-Ting Yang; Yi-Zi Chen; Ting-Chi Lo; Jia-Sin Chen; Wei-Lun Huang; Yen-Liang Li; Hidenobu Takahashi; Wen-Chun Hung; Chi-Wen Luo; Shu-Yi Lin; et al. (Chemical Engineering Journal, 2026)

Prophage-dependent membrane vesicles in Geobacter soli: Implications for biofilm formation and extracellular electron transfer - Yanlun Fang; Xian Wu; Canfen Lin; Guiqin Yang; Yidong Jiang; Zheng Zhuang; Li Zhuang (Bioresource Technology, 2026)

TEC2Ne: a physics-informed deep learning framework for reconstructing ionospheric electron density profiles from global TEC maps - Chenghao Li; Hanxian Fang; Chao Xiao; Die Duan; Yang Lin; Hongtao Huang; Ganming Ren; Han Wu; Chuyue Zhou; Haiyang Zheng; Xuhui Shen; Xiaoqun Cao (GPS Solutions, 2026)

Multiplexed EDL-FET biosensor with tannic acid stabilization for simultaneous p-Tau217 and Aβ42/Aβ40 detection in plasma and whole blood from stroke patients - Shang-Chi Chien; I-Yin Chang; Yong-Chuan Chen; Yi-Zhen Lai; Yu-Fang Chen; Pei-Lun Sun; Bor-Ran Li; Yu-Lin Wang; Jung-Chih Chen (Analytica Chimica Acta, 2026)

Agricultural management shapes soil multitrophic communities and biodiversity-ecosystem function relationships in a dryland agroecosystem - Jiayao Han; Yali Zhang; Hao Xi; Lin Mao; Zhou Fang; Chenyu Li; Yongjun Liu (Agriculture, Ecosystems & Environment, 2026)

Environmental DNA metabarcoding complements bottom trawling and detects fish species beyond recorded ranges in the Chukchi Borderland, Central Arctic Ocean - Hai Li; Fang Yang; Xiang Zhang; Ran Zhang; Rui Wang; Xing Miao; Shigang Liu; Puqing Song; Yuan Li; Longshan Lin (Marine Environmental Research, 2026)

Disruption of OsGONST3 reduces grain cadmium accumulation without yield penalty in field-grown rice - Jing Huang; Qiang Zhang; Fang Wei Yu; Ming Qing Liu; Huai Kang Jing; Shen Yun Wang; Hao Yu Wang; Jia Qi Li; Lu Zheng; Hua Shao; Xiao Lin He; Ren Fang Shen; et al. (Journal of Hazardous Materials, 2026)

A sunscreen UV filter disrupts energy homeostasis and impairs growth in the endangered living fossil Tachypleus tridentatus - Guangjin Li; Yiting Li; Xingda Lin; Shiyong Wang; Meijiao Yan; Yaoyao Chu; Chuihong Fang; Zhi Chen; Fengxiao Hu (Journal of Hazardous Materials, 2026)

Regional surveillance of non-A-F Salmonella enterica reveals diverse risk profiles, with global genomic insights from Salmonella Worthington - Lei Fang; Guankai Lin; Yuezhuo Wang; Shiqi Lei; Haiyan Li; Xuewei Liu; Chaoyi Wang; Yi Li; Chen Zhang; Guozhi Zhang; Lin Teng; Leyi Zhang (Food Research International, 2026)

Comparative metabolomic analysis of flavor and metabolite profiles across cultivated kiwifruit species - Ran Wang; Chengkui Qiao; Li Liu; Ziqi Zhang; Sikai Li; Miaomiao Lin; Yukuo Li; Jinbao Fang; Leiming Sun; Xiujuan Qi (Food Chemistry, 2026)

Photo-crosslinking strategy to lock π-π-assembled ion channels in polymer membranes for enhanced monovalent anion selectivity - Yachun Ma; Simian Fei; Jie Fang; Qiuhua Li; Lin Zhang; Huchuan Wang; Liang Ge; Chuanrun Li (Desalination, 2026)

A synergistic piezo-photocatalytic strategy via BaTiO3 heterophase homojunctions for MRSA-infected diabetic wound therapy - Lei Qian; Han Lin; Min Wu; Zheng Fang; Jiawei Li; Yao Han; Jinxia Zhai; Peng Yu; Cairong Xiao; Chengyun Ning (Chemical Engineering Journal, 2026)

Spatiotemporal heterogeneity relationships between atmospheric methane and various driving factors across China - Yuanyuan Chen; Yufan Qian; Miaoyan Wang; Yi Li; Wei He; Yi Lin; Shuangxi Fang (Atmospheric Research, 2026)

Poricoic acid A administered during DSS exposure attenuates acute colitis in mice and is accompanied by barrier-associated changes and endpoint fecal microbiota shifts - Mei Wang; Kunkun Zhang; Danli Wang; Mingtao Cao; Rong Yong; Xiangqian Li; Wenyi Chen; Chengcheng Peng; Jiale Chang; Lu Fang; Feiyang Zhou; Yuyue Wan; et al. (Journal of Natural Medicines, 2026)

The role of growth differentiation factor 15 in the polarization and foaming of THP-1 macrophages induced by trans fatty acids from different sources - Jingyuan Lin; Weiting Fang; Yuan Yuan; Huijiao Shen; Xiaojing Shi; Guo Wang; Huzhong Li; Qifei Yang; Yang Yang; Xingcan Yang; Qibing Zeng; Haiqin Fang (Toxicology in Vitro, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Precise nanodelivery of screened compounds alleviates sepsis-associated encephalopathy by targeting microglial ANXA2 - Daoyi Lin; Yuan Huang; Shuyan Wu; Zefu Li; Hanhao Dai; Fei Gao; Danfeng Wang; Maokai Xu; Ziqi An; Xinmu Li; Peng Ye; Yingjie Chen; et al. (Science Bulletin, 2026)

Isolation, structural elucidation, and activities evaluation of proaporphine alkaloids from Thalictrum baicalense - Meng-Yue Yang; Jing-Jing Xue; Zhao-Jing Chen; Xiao-Peng Guo; Shi-Meng Qin; Han-Gao Yang; Fang-Shen Liu; Zhan-Lin Li; Da-Hong Li; Ya-Ting Sun; Hui-Ming Hua (Phytochemistry, 2026)

Anthraquinone‑modulated oxygen disproportionation enables highly selective singlet oxygen generation for pollutant degradation - Yu Luo; Chenqi Lu; Chuang Xiao; Lin Ding; Mengyuan Zhao; Lingling Liu; Longshuai Zhang; Xibao Li; Fang Deng; Xubiao Luo; Jian-Ping Zou (Journal of Environmental Chemical Engineering, 2026)

The TFAM-OGG1 axis mediates T-2 toxin-induced chondrocyte mitochondrial dysfunction and cartilage degeneration - Jiaxin Li; Chenxi Wang; Buyi Lin; Jiayuan Li; Fang Qi; Ying Liu; Haoyu Du; Yue Zhao; Jun Yu (Food and Chemical Toxicology, 2026)

Associations of prenatal individual and mixture per- and polyfluoroalkyl substances (PFAS) exposures with fetal growth trajectories: Modifying effects of maternal micronutrient status - Zhen-Hua Li; Hai-Yang Weng; Chun-Yong Wang; Xiao-Yu Zhao; Guo-Peng Gao; Kai Huang; Mao-Lin Chen; Fang-Biao Tao; Cheng-Yang Hu; Xiu-Jun Zhang (Environmental Research, 2026)

Vibration isolation for mechatronic metamaterial rings with piezoelectric shunting circuits - Long Zhao; Ze-Qi Lu; Li-Fang Lin; Hu Ding; Li-Qun Chen (Engineering Structures, 2026)

High-frequency redox fluctuations in deep-lacustrine basin and their impact on organic carbon burial: Records from micrometer-scale laminae in the Triassic Yanchang Formation Shale, Ordos Basin - Ke Li; Kelai Xi; Yingchang Cao; Zhe Zhao; Xiujuan Wang; Miruo Lin; Keyu Liu; Fang Hao (Science China Earth Sciences, 2026)

Interdecadal winter temperature variability driven by the East China Sea Mode: A global perspective - Keyan Fang; Hao Wu; Shuheng Lin; Jun Cheng; Jane Liu; Deliang Chen; Jinbao Li; Cesar Azorin-Molina; Zheng Zhao; Frode Stordal; Shuo Hao; Nicole Davi; et al. (Science China Earth Sciences, 2026)

Molecular and biological characterisation of Magnaporthe oryzae botourmiavirus 15 - Yuxin Wu; Weilan Wu; Cong Li; Xinyi Li; Hui shuang Yi; Yue lin Li; Pan Gong; Songbai Zhang; Shouguo Fang; Qingchao Deng (Archives of Virology, 2026)

Advances in oral delivery systems for alpha-linolenic acid: mechanisms, bioavailability, and applications in functional foods - Fazhan Zhong; Qianchun Deng; Shangwen Chen; Rui Fang; Yawen Huang; Dengfeng Peng; Xia Xiang; Yashu Chen; Li Chen; Xiao Lin; Ziyu Deng (Critical Reviews in Food Science and Nutrition, 2026)

A 44-min periodic radio transient in a supernova remnant - Di Li; Mao Yuan; Lin Wu; Jingye Yan; Xuning Lv; Chaowei Tsai; Pei Wang; Jiaqi Zhao; Weiwei Zhu; Li Deng; Ailan Lan; Renxin Xu; et al. (Science Bulletin, 2026)

Facile fabrication of PTFE/PET composite membrane with reinforced hydrophilic and antifouling properties for sustainable decentralized water system purification - Ludi Song; Yujie Fang; Xin Chen; Ziyuan Zhou; Liping Chen; Jun Yang; Ying Li; Yaqin Wu; Haitao Zhu; Lin Zhang; Congjie Gao (Journal of Environmental Management, 2026)

Interfacial heterogeneous electro-Fenton membrane distillation for risk-controlled concentration of high-salinity coal-chemical wastewater - Hongxin Liu; Kuiling Li; Lin Fang; Yang Yao; Zhigang Dan; Jun Wang (Journal of Environmental Sciences, 2026)

The Hippo–Yki pathway governs growth and cell fate in the posterior silk gland of the silkworm - Yan Ma; Zhiyong Zhang; Wenhui Zeng; Zhou Fang; Xin Yu; Lin Cheng; Zehui Ma; Qipeng Zeng; Dena Jiang; Yiyun Tang; Jie Hu; Chen Zhao; et al. (Insect Biochemistry and Molecular Biology, 2026)

Boosting pH-universal hydrogen evolution of the In/Cu3P Mott-Schottky heterojunction electrocatalyst by constructing the ohmic contact and promoting water activation - Pengfei Du; Fang Li; Huiqin Yu; Jing Cao; Yuan Ma; Haili Lin (Fuel, 2026)

Dual-modulated anthocyanin-based freshness indicators with improved stability using 2,5-dihydroxybenzoic acid and UiO-66-NH2 - Hao Fang; Limin Cao; Jianxin Sui; Xiudan Wang; Hong Lin; Kaiqiang Wang; Jinjie Li (Food Chemistry, 2026)

Flexural behavior and ultimate moment capacity calculation of R-UHTCC-recycled concrete composite beams - Zhiqiang Gu; Zuobiao Li; Dong Wei; Danying Gao; Lin Yang; Dong Fang; Ke Shi (Engineering Structures, 2026)

Demand-driven design of porous polyurethane composites for efficient chemical elimination of air pollutants and flame-retardant applications - Jijie Li; Xiaoran Guan; Mengyu Cao; Xiuping Liu; Xueying Cao; Jinhou Fang; Xiaoying Lin; Jingquan Liu (Chemical Engineering Journal, 2026)

Short-term hot spring balneotherapy ameliorates sleep disorders: wrist-worn wearable-assessed sleep improvement associated with neuroimmune, tryptophan metabolic and gut microbiome alterations - Xiao Zhang; Yue Zou; Xiao-qin He; Yi-hang Xu; Hong-xia Li; Fen Yang; Bao-chao Zhang; Lin-xuan Liao; Meng-xi Cao; Rui-xue Wang; Si-fan Hao; Meng-meng Wang; et al. (International Journal of Biometeorology, 2026)

Effect of Excavation Sequence and Bolt Support on Surrounding-Rock Stability of a Double-Tunnel System in Jointed Rock Mass - Feng Jiang; Tian-lin Huang; Hai-zhen Huang; Ji-song Wang; Peng He; Gang Wang; Chun-gui Li; Ting-fang Liu; Cheng-cheng Zheng; Zhi-yong Xiao (Applied Geophysics, 2026)

Time-Series Transcriptomics of a Gill Cell Line (BTG) from Chinese Bahaba (Bahaba taipingensis) During ISKNV Infection (3–24 hpi) - Chenfei Guo; Zhihong Gong; Fei Fang; Xihong Li; Lei Wang; Na Wang; Zhangfan Chen; Lin Yan; Kuoqiu Yan; Guobin Hu; Songlin Chen (Fishes, 2026)
The Chinese bahaba (Bahaba taipingensis), an endangered marine fish, is highly vulnerable to infectious spleen and kidney necrosis virus (ISKNV). In this work, we developed a gill filament-derived cell line, designated BTG, to investigate how these cells respond to ISKNV over time, specifically from 3 to 24 h post-infection (hpi). BTG cells grew steadily, displayed a diploid chromosome number of 2n = 48, demonstrated high transfection efficiency, and were highly susceptible to viral infection. Characteristic cytopathic effects (CPEs) became noticeable as early as 6 hpi at 27 °C. RNA-seq profiling showed that the number of differentially expressed genes (DEGs) steadily increased with time. Standard enrichment analysis at individual time points (3, 6, 12, and 24 hpi) highlighted pathways mainly involved in DNA replication, cell cycle control, ribosome assembly, transcription and translation, mismatch repair, and cell adhesion. Temporal clustering analysis, however, revealed hidden patterns in immune gene expression. Genes that were consistently downregulated were enriched in immune-related pathways, including ECM–receptor interaction, cytokine–receptor signaling, PI3K–AKT, and Wnt signaling, indicating prolonged suppression of host defense mechanisms. In contrast, clusters of genes transiently upregulated during the first 6 h post-infection were associated with antiviral and innate immune pathways, such as NF-κB, JNK, IRF3, IRF7, caspases, JAK, MHC I, and lysosome-related functions, suggesting a rapid but short-lived antiviral response. Genes that were continuously upregulated were primarily involved in nucleic acid replication and protein synthesis, reflecting a gradual host cell reprogramming to support viral replication. Taken together, these findings reveal a temporal shift in BTG cells from an initial burst of immune activity to immune suppression, accompanied by enhanced viral replication. The BTG cell line thus represents a valuable in vitro model for dissecting ISKNV–host interactions and offers new perspectives on the molecular strategies employed by megalocytiviruses in B. taipingensis.

Non-equilibrium criticality-enhanced quantum sensing with superconducting qubits - Hao Li; Yaoling Yang; Yun-Hao Shi; Zheng-An Wang; Ziting Wang; Jintao Li; Yipeng Zhang; Kui Zhao; Yueshan Xu; Cheng-Lin Deng; Yu Liu; Wei-Guo Ma; et al. (Science Bulletin, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

A novel phytoformula targeting lipid peroxidation inhibition attenuates UV-induced skin photoaging - Ling-Ping Wu; Wei Chen; Qian-Pei Lin; Shi-Yun Feng; Jin Dai; Qiong-Yi Zhang; Wen-Yi Chen; Hiroshi Kurihara; Xiao-Min Li; Shu-Hua Ouyang; Yi-Fang Li; Rong-Rong He (PharmaNutrition, 2026)

Mangrove species act as potential biofilters for legacy organochlorine pesticides: evidence from tissue-specific accumulation in the Zhangjiang Estuary - Nemin Luo; Ting Fang; Yingying Qian; Lei Wang; Wenhui Lin; Rongrong Song; Guoxin Li; Fengrun Wu; Xiaoqing Chen; Mingyuan Lin; Yan Lin (Marine Environmental Research, 2026)

Genesis of copper-deficient skarn iron deposits in the North China Craton: Insights from apatite and whole-rock geochemistry - Jun-Wu Zhang; Lin Li; Ju-Quan Zhang; Fang-Yue Wang; Xian Liang (Journal of Geochemical Exploration, 2026)

Manure and sewage dominate nitrate sources in runoff from key headwaters area in China - Xin Chen; Guoce Xu; Zhanbin Li; Shun Wan; Yang Lin; Bin Wang; Mingzhu Xu; Kang Fang; Yanming Qi (Journal of Cleaner Production, 2026)

Two purified polysaccharides from Anemarrhena asphodeloides alleviate type 2 diabetes in mice through remodeling gut microbiota and modulating glycolipid metabolism - Juncheng Chen; Li Zhu; Liqian Chen; Guihong Fang; Baolian Li; Jing Zhou; Meijuan Lan; Lin Li; Bing Li (Food Bioscience, 2026)

Trophic transfer in a cold seep food web: Dual constraints from δ13C-δ15N isotopes and rare earth elements - Zice Jia; Niu Li; Xun Sun; Shamik Dasgupta; Shaomin Lin; Hongfei Lai; Wenhua Feng; Chao Zhong; Zenggui Kuang; Fang Chen (Deep Sea Research Part I: Oceanographic Research Papers, 2026)

Impaired Glymphatic-Meningeal Lymphatic Function in Patients with Spontaneous Subarachnoid Hemorrhage - Jianan Lu; Miao Lin; Heping Tian; Yibo Liu; Bingrui Zhu; Jin Mao; Jiahao Zhang; Haocheng Zhang; Sixuan Tian; Xu Li; Ding Xu; Chenhan Ling; et al. (Translational Stroke Research, 2026)

Contrasting responses of bacterial-mediated soil organic phosphorus transformations to varying rates of nitrogen addition in a Cunninghamia lanceolata plantation - Xiang Zhang; Qiong Zhao; Li-Man Wei; Lin-Hui Wu; Xiang-Min Fang; Yong-Hong Ma; Fu-Sheng Chen (Applied Soil Ecology, 2026)

Mn defect enhanced oxidase-mimicking activity of MnO2 for colorimetric detection of total antioxidant capacity - Chengji Sui; Lin Wang; Fengjia Zheng; Fenghua Li; Wei Li; Chuan Qin; Yi Fang; Huanshun Yin (Analytica Chimica Acta, 2026)

Mechanical Properties of Glycated Cracked Articular Cartilage Under Uniaxial and Cyclic Tensile Loading - Li-Lan Gao; Yi Fang; Xiang-Long Lin; De-Zhao Kong; Yan-Song Tan; Rui-Xin Li; Kai Sun; Chun-Qiu Zhang; Yanliuxing Yan (Annals of Biomedical Engineering, 2026)

Atmospheric Boundary Layer Eco-Environment Shanghuang Observatory: An Integrated Multiscale Research Platform in Southeastern China for Understanding Boundary Layer Processes, Atmospheric Chemistry Feedback, and Extreme Weather–Climate Linkages - Zifa Wang; Xiaole Pan; Yele Sun; Jinyuan Xin; Hang Su; Junji Cao; Jie Li; Ting Yang; Hang Liu; Weijie Yao; Weiqi Xu; Xueshun Chen; et al. (Advances in Atmospheric Sciences, 2026)

Predicting Bacterial Radiation Resistance Through Identifying Novel Genomic Features - Jiayu Liu; Chao Fang; Boyang Ji; Tongrong Zhang; Lin Li; Liying Zhu; Zhidong Zhang; Zhengming Zhu; Ling Jiang (Environmental Microbiology, 2026)
Radiation resistance in bacteria is a critical trait with implications for biotechnology, medicine and environmental science. Deinococcus species possess unique genomic features that enable their extraordinary survival in extreme environments. However, the diversity of radiation resistance mechanisms across bacteria remains poorly explored. Here, we analysed the genomic diversity and functional gene repertoire of Deinococcus and extended the analysis to a broader set of radiation‐resistant bacteria. We found that highly resistant strains tend to have smaller genomes and harbour more genes positively associated with radiation resistance, highlighting their potential roles in sustaining cellular homeostasis under radiation‐induced stress. By integrating machine learning with curated genomic datasets, we identified key resistance‐associated gene signatures and developed a predictive tool to quantify bacterial radiation resistance. This study offers new insights into the genomic basis of radiation resistance and provides a practical framework for its assessment in environmental and microbial engineering applications.

Influence of salinity on the dynamic improving nutritional value of channel catfish (Ictalurus punctatus): Insights from targeted and untargeted metabolomics and antioxidant capacity analysis - Zhen Li; Yali Yu; Quanyou Guo; Na Lin; Xiaorong Lu; Jie Peng; Tao Mao; Yuntao Zhou; Lang Zhang; Liu Fang (Aquaculture, 2026)

Nanofiber engineering of covalent organic frameworks via monomer–solvent synergy for high-efficiency uranium capture - Xiao-yi Tang; Qun-yan Wu; Yi-chen Huang; Peng-fei An; Lin Wang; Ji-pan Yu; Shu-sen Chen; Zi-jie Li; Li-yong Yuan; Wang-suo Wu; Zhi-fang Chai; Wei-qun Shi (Journal of Hazardous Materials, 2026)

NO -driven chemical transformation of terpene mixtures: Linking highly oxygenated organic molecules to health effects in secondary organic aerosol - Xiaowen Chen; Kun Li; Ruiyu Li; Li Fang; Haizhen Bian; Wei Jiang; Caiqing Yan; Lin Du (Journal of Environmental Sciences, 2026)

Leaf functional traits and wood density of evergreen and deciduous tree species in a tropical karst forest - Yu-Meng Gao; Shi-Jian Yang; Jiao-Lin Zhang; Yan-Juan Jiang; Shu-Bin Zhang; Amy Ny Aina Aritsara; Guo-Hao Hu; Pei-Li Fu; Ze-Xin Fan; Kun-Fang Cao (Flora, 2026)

A chlorine-rich argyrodite electrolyte with cost-effectiveness and high ionic conductivity for all-solid-state lithium batteries - Shijie Yu; Lin Zheng; Manzhen Fang; Linping Liao; Ting Yang; Peidian Chong; Yafeng Li; Longyuan Guo; Mingdeng Wei (Chemical Engineering Journal, 2026)

Interleukin-12 Supports Self-renewal Division of Mouse Hematopoietic Stem Cells in Polyvinyl Alcohol-Based Culture - Jinglei Zhai; Xialin Li; Meiling Yin; Sen Zhang; Xiaoming Liu; Lisha Wang; Nini Wang; Lin Wang; Hideo Ema; Fang Dong (Stem Cell Reviews and Reports, 2026)

Environmental factors shape the intestinal microbiota and function of Manila clam Ruditapes philippinarum - Bifu Gan; Guiling Li; Yanru Xu; Jingmiao Yang; Weilang Lin; Xiaobo Yan; Maozi Lin; Guangmao Ding; Fang Su; Qizhen Xiao (Frontiers in Marine Science, 2026)
Intestinal microbiota of aquatic animals is closely associated with the environment, influencing their health, immune defense, and environmental adaptability. To understand the relationships among the Manila clam ( Ruditapes philippinarum ) intestinal microbiota, the bacterial communities in their habitats, and environmental factors, as well as the characteristics and potential functions of the intestinal microbiota. This study systematically analyzed the bacterial communities in the clam intestines, seawater, and sediment samples from two typical habitats using 16S rRNA gene (V3-V4) sequencing. The results revealed significant differences in bacterial community composition among the intestines, seawater and sediment, with pronounced regional variations also evident within the same sample type. The clams gut microbiota in Fuqing was predominantly composed of Alphaproteobacteria , Gammaproteobacteria , Bacteroidota , Bacillota , and Cyanobacteria . In Putian, Cyanobacteria comprised an exceptionally high proportion. However, Bacillota , Bacteroidota , and Actinomycetota showed similar relative abundances in both regions, indicating a potential “core bacterial community”. Regarding the α-diversity of gut microbiota, although no significant differences were observed between clam samples from the two regions, their diversity was significantly lower than that of the sediment bacterial communities. The intestinal bacterial communities exhibited high similarity to the aquatic bacterial communities in terms of richness, diversity, and dominant species abundance, and it shares most of the ASVs with the sediment, suggesting that environmental microorganisms may serve as the primary source of the clam intestinal microbiota. Environmental drivers of bacterial communities differed regionally. In Fuqing, bacterial communities were associated with temperature, DO, pH, and salinity, and exhibited broader niche widths; in Putian, they were mainly influenced by nutrients, showing narrower niches. Compared to bacterial networks in the environment, the interactions among members within the gut bacterial communities of clams display modularity, indicative of functional specialization. The composition and functions of the intestinal microbiota of clams vary significantly in different environments, which may be a manifestation of their ecological adaptability. The composition and function of clam intestinal microbiota varied with environment, reflecting their ecological adaptability. These findings provide a scientific theoretical basis for water quality regulation and disease prevention in aquatic animal farming operations.

Global inland waters trophic status from space observation: scientific advances and future challenges - Lili Lyu; Pierre-Andre Jacinthe; Nan Lin; Dongmei Lyu; Ge Liu; Sijia Li; Chong Fang; Hui Tao; Hao Yu; Zuchuan Li; Kaishan Song (Water Research, 2026)

Fe/Cu-γ-Al2O3 catalyst for pilot-scale internal circulation Fenton degradation of methyl orange: performance and mechanism - Dekai Fan; Yanran Lin; Peng Zhu; Yingwen Zhang; Bang Yao; Li Chao; Zhuangzhuang Jia; Jianjun Dai; Yingrui Ning; Rong Xiao; Chen Chen; Lei Gao; et al. (Journal of Environmental Management, 2026)

Urban-suburban-rural gradient variations in mortality associated with compound exposure to heat wave and ozone pollution: A case-crossover study using small-area assessment - Kang Ma; Fengman Fang; Xiuya Xing; Yuesheng Lin; Cheng He; Youru Yao; Fei Tong; Jingli Zhu; Huadong Wang; Feiyan Zhang; Ruoxi Li (Journal of Environmental Management, 2026)

Effects of co-existing substances on phosphorus recovery from swine wastewater via struvite crystallization with a carbon felt cathode - Ying Xiang; Weike Lin; Shuoshi Guo; Jinfeng Wei; Peng Li; Jin Li; Fang Wang (Journal of Environmental Management, 2026)

Al-doped α-MnO2 for low-temperature catalytic oxidation of formaldehyde - Zhengnan Lin; Zhao Zheng; Junchen Li; Cheng Zhang; Qingyan Fang; Peng Tan; Gang Chen (Journal of Environmental Chemical Engineering, 2026)

Screening, risk assessment, and rapid detection of mycotoxins in edible herbs based on UPLC-MS/MS and FT-NIR - Kangnan Liu; Ling Fang; Yaling An; Zijun Tang; Wenjie Zhao; Chunqian Song; Lin Feng; Xiaokang Liu; Zhenwei Li; Daidi Zhang; De-an Guo (Food Research International, 2026)

16S rDNA sequencing combined with non-targeted metabolomics profiling reveals the mechanism of simulated digestion ultra-sound pea protein isolate in vitro - Xinyu Zhao; Xuemei Dong; Jianke Fang; Chun Li; Lin Zhao; Guofang Zhang; Peng Du; Tong Zhang; Xinyao Sun; Libo Liu; Wenkui Guo (Food Bioscience, 2026)

Cellulose-based ultralight foam with dual-scale porosity from hybrid fibers for sustainable oil-water separation - Weiqiang Li; Jingge Liu; Meiying Li; Haitao Lin; Jian Fang; Xiaoqiao Wang; Jianchu Xu; Yuling Li; Junze Zhang; Xinheng Li; Gang Li (Carbohydrate Polymers, 2026)

A membrane-mediated algal–bacterial coupling strategy for energy – efficient and low-carbon PHA production - Long Huang; Lin Liu; Guangyi Zhang; Guoqiang Li; Yingke Fang; Yuan Li; Huiying Yang; Hongbin Xu (Bioresource Technology, 2026)

Research progress on NSP4 protein of porcine reproductive and respiratory syndrome virus - Xiaolin Lan; Fang Liang; Gan Li; Yaqiong Ye; Feng Li; Chen Lv; Kexin Liu; Zhiyu Yang; Ruyu Sun; Keshan Zhang; Lin Wang; Huawei Li; et al. (Veterinary Research Communications, 2026)

Extracellular vesicles in cancer progression: mechanisms and significance - Ying Gao; Denghui Wei; Li Zhong; Dan Liao; Xueping Zheng; Yujie Lin; Dongmei Fang; Boyang Chang; Tiebang Kang (Science China Life Sciences, 2026)

Magmatic evolution and mush processes of the Xiarihamu Ni-Cu deposit: insights from olivine-orthopyroxene-clinopyroxene chemistry - Xu-Yang Zheng; Ya-Jing Mao; Fang-Lin Yuan; Yi Li; Wen-Jun Li; Ke-Zhang Qin (Mineralium Deposita, 2026)

From SPP to RTK: promoting the satellite navigation potential of acoustically excited antenna - Shangyang Wang; Yifan Fu; Rui Hu; Du Li; Bing Xu; Ruofan Liu; Yinuo Song; Junru Li; Bin Fang; Wenkui Lin; Zhongming Zeng; Xiangwei Zhu (GPS Solutions, 2026)

Influence of Sea Surface Temperature on Precipitation Anomalies in Northeast China During the Late Summer, 2024: A Statistical Assessment Based on Generalised Equilibrium Feedback Analysis - Yitong Lin; Yihe Fang; Chunyu Zhao; Yu Zhang; Chang Liu; Xinze Li (International Journal of Climatology, 2026)
During the late summer (July–August) of 2024, the Northeast China (NEC) suffered extreme precipitation and severe floods, with rainfall in southern NEC marking the highest recorded since 1985. Using the daily precipitation records from 245 national meteorological stations across the NEC, this study analyses the characteristics of the rainfall anomalies and the associated large‐scale circulation patterns in the late summer of 2024. Based on the generalised equilibrium feedback analysis (GEFA) method, we investigate the response of precipitation and atmospheric circulation anomalies to sea surface temperature (SST) anomalies across various oceanic basins. The results indicate that the NEC precipitation anomalies in the late summer of 2024 exhibit a remarkable response to both the first empirical orthogonal function (EOF) mode of the North Pacific SST (NP1) and the second EOF mode of the tropical Atlantic SST (TA2). The NP1 features widespread positive SST anomalies extending from the Kuroshio Extension to the west coast of North America, and the TA2 is marked by positive anomalies in the northern tropical Atlantic and negative anomalies in the southeastern region. Both modes induce enhanced precipitation over NEC, with anomaly centres located southward, closely matching the observations. Specifically, the positive SST anomalies of the NP1 mode enhance the upward heat flux over the Japan Sea and its eastern regions, inducing positive geopotential height anomalies over Japan, thereby leading to an enhanced and northward anticyclone in the Northwest Pacific. Moreover, for the TA2 mode, the positive SST anomalies in the northern tropical Atlantic are closely associated with the downstream propagating Rossby wave train, resulting in an anomalous circulation pattern characterised by active Northeast China cold vortexes over the NEC and an intensified western Pacific subtropical high. These circulation anomalies facilitate the northward transport of warm and humid airflows to the NEC and promote the frequent convergence of cold and warm airflows over the NEC region, thereby contributing to the anomalously more precipitation over the NEC in the late summer of 2024. By quantifying the relative contributions of different SST modes, this study helps better target key precursors of NEC summer rainfall anomalies, which provides useful guidance for seasonal climate forecasting in NEC.

Magnetoelastomer-based grain flow sensor for combine harvesters - Xin-Dong Ni; Mao-Lin Li; Fang-Lei Li; Zi-Xuan Dai; Chun-Xiao Xing; Feng Wang; Yan-Xin Yin; Du Chen; Zhi-Zhu He (Computers and Electronics in Agriculture, 2026)

Improved swimming performance from exercise training is driven by optimized muscle energy metabolism and antioxidant capacity in juvenile large yellow croaker Larimichthys crocea - Sijian Deng; Yuhe Yang; Tingting Lin; Xin Liu; Yazhou Jiang; Zhengli Fang; Siping Li (Aquaculture, 2026)

Characterization of novel Vibrio parahaemolyticus JD2305 and comparative genomics of the Tc toxin mobilome in Vibrio pathogens associated with translucent postlarvae disease - Laizhuang Jin; Na Ying; Qianhui Song; Liguo Yang; Letian Li; Lei Feng; Hui Zhang; Mao Lin; Xinshu Li; Wenhong Fang (Aquaculture, 2026)

In situ biofilm development on microplastics and its impact on PFAS adsorption in aquatic environment - Guoqing Hou; Rui Zhang; Tianhui Zhao; Mengyuan Fang; Lin Niu; Qitao Lei; Qiang Li; Nuo Chen; Zhi Tang; Xiaoli Zhao; Fengchang Wu (Water Research, 2026)

Visco-elastic interface and dynamic response of a lined tunnel in anisotropic rock mass under unloading waves - Xue-Qian Fang; Zhao-Feng Zhong; Bai-Lin Li; Xin-Yu Liu; Ya-Wen Xiong (Soil Dynamics and Earthquake Engineering, 2026)

Spiral-fluorene-integrated sterically shielded multi-resonance TADF emitter: simultaneously achieving narrowband emission and restraining Dexter energy transfer - Jiasen Zhang; Hao Liu; Lin Wu; Kaibo Fang; Deli Li; Denghui Liu; Xuewei Nie; Letian Xu; Zujin Zhao; Wei Li; Ziyi Ge (Science Bulletin, 2026)

Delineating fish ecological corridors in a subtropical bay using eDNA metabarcoding: A case study from Xiamen Bay, China - Hai Li; Fang Yang; Xiang Zhang; Yuzhuo Liao; Yuan Li; Puqing Song; Shigang Liu; Longshan Lin (Regional Studies in Marine Science, 2026)

The overlooked role of nitrate in mediating electron transfer and enhancing reactive species generation in TiO2 photocatalytic water remediation - Zheng Hu; Jin Wu; Lingzhi Shen; Zili Lin; Zihong Xu; Zhenjun Xiao; Zheng Fang; Daguang Li; Ping Chen; Wenying Lv; Guoguang Liu (Process Safety and Environmental Protection, 2026)

The F116V mutation and overexpression of CYP9A186 confer high-level resistance to emamectin benzoate and abamectin in Spodoptera exigua - Qiuxia Zeng; Lin Li; Yongsheng Yao; Bingbing Fang; Yu Shi; Yihua Yang; Yidong Wu (Pesticide Biochemistry and Physiology, 2026)

An integrated flotation-cyclic leaching process for reduced acid consumption in vanadium shale extraction - Yibo Hu; Chenkun Lin; Zhiwen Xia; Jianxing Fang; Cong Yin; Qingliang Wang; Huijuan Li; Pengfei Hu (Minerals Engineering, 2026)

Impact of sulfonamides on microbial community and antibiotic resistome profiles in anaerobic digestion of swine wastewater - Qinmao Zhou; Hebin Liang; Jin Huang; Uli Klümper; Peiju Fang; Zehui Yu; Yuyang Wang; Thomas U. Berendonk; Lin Lin; Xiaoyan Li; Bing Li (Journal of Hazardous Materials, 2026)

Optoelectronic synaptic transistor array based on CsPbBr3/grating-patterned IDTBT heterojunctions for neuromorphic visual fatigue sensing - Jiajie Hong; Zhiqian Wei; Zunxian Yang; Yue Chen; Luxi Yuan; Shangwei Ye; Xudong Jiang; Yuting Bai; Benfang Liu; Zhiyu Yuan; Wenxin Zhang; Jie Li; et al. (Chemical Engineering Journal, 2026)

Decoupling detoxification from resource recovery: Mechanisms of organic electromigration control in bipolar membrane electrodialysis - Hao-Ran Yang; Zhi-Hua Yuan; Chang-Jiang Li; Yan-Fang Guan; Jiuyang Lin; Mohammad Younas; Xinfei Dong; Yi-Hong Jiang; Yu-Ming Zheng (Chemical Engineering Journal, 2026)

Assessing the Probiotic Properties and safety of Limosilactobacillus reuteri LP4 Isolated from Apis cerana Based on Whole Genome and Phenotype Analyses - Le Xu; Pingping Fang; Mingkui Lv; Shiyu Chen; Chen Liu; Sifan Wang; Jiqin Li; Kun Dong; Qiuye Lin; Zhenhui Cao (Probiotics and Antimicrobial Proteins, 2026)

Clostridium butyricum Promotes Bone Remodeling by Activating Inflammatory Genes in Mice - Yanxin Jia; Longfei Xu; Zijing Ju; Mengze Song; Yonghao Zhou; Bin Li; Fang Wang; Hai Lin; Shuhong Sun; Haifang Li (Probiotics and Antimicrobial Proteins, 2026)

Coupled effects of straw return practices on soil microbial functional potential and agricultural productivity in Semi-Arid Region - Rui-Zhi Liu; Xiao-Ya Zhao; Li-Jie Wang; Xing Zhang; Shu‑Ping Hu; Ju‑Lin Gao; Xiao‑Fang Yu; Qinggeer Borjigin (Plant and Soil, 2026)

Naturalization of Pinus tabulaeformis plantations modifies the soil nutrient and microbial community structures at the soil aggregate level across different depths - Yiping Lin; Kefan Wang; Xin Fang; Haomin Wang; Nuo Li; Zilu Wang; Cong Shi; Fuchen Shi (Plant and Soil, 2026)

Identification of a novel stripe rust resistance locus in a Chinese wheat landrace by bulked segregant analysis of recombinant inbred lines combined with the 660 K SNP array - Liuyang Shang; Suyu Li; Yuqin Li; Fang Wang; Shutao Chen; Kanghui Zeng; Yanling Hu; Yinghui Li; Zhenzhen Wei; Lianquan Zhang; Guoyue Chen; Bihua Wu; et al. (Euphytica, 2026)

FSHR-GnRH bispecific vaccine suppresses the fertility of female rats - Jingjing Zhang; Xinyue Jiang; Yuke Jia; Jingya Xu; Yuwen Huang; Tao Tao; Meng Cao; Wei Qian; Fugui Fang; Yunsheng Li; Yinghui Lin; Hongwei Duan; et al. (Theriogenology, 2026)

Short-, medium-, and long-chain chlorinated paraffins in sediments from the Pearl River Delta, China: Occurrence, sources, and risks - Fei-Xiang Xie; Yu-Fang Huang; Yong-Hong Zhang; Ya-Hui Xue; Run-Lin Chen; Xiao-Mei Huang; Hong-De Shi; Jia-Hui Huang; Hui-Ru Li (Science of The Total Environment, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Advancements in environmental microplastic removal and upcycling techniques - Tianyu Lin; Penggang Li; Huaping Jia; Heng Jiang; Fengjia Xie; Yanting Liu; James Kar-Hei Fang; Changchao Li; Xuming Zhang (Journal of Environmental Chemical Engineering, 2026)

Regime Shift from Macrophytes to Algal Dominance Enhances Lake Carbon Persistence: Molecular Evidence from DOM Transformation - Ziwei Zhang; Huanjun Zhang; Yi Li; Wangkai Fang; Li Lin (Journal of Environmental Sciences, 2026)

Dose-dependent root phenotypic plasticity in Casuarina equisetifolia: Mechanistic insights into drought adaptation strategies for coastal sand-fixation afforestation - Chen Fang; Qinqin Lin; Can Chen; Yu Chen; Han Lin; Guoying Pan; Chuanyang Jiang; Anqiang Xie; Xia Li (Journal of Arid Environments, 2026)

Enzymatic chain elongation of A-, B-, and C-type grain starches by amylosucrase: Universal structure–function rules for resistant-starch design - Shiyang Li; Yufeng Lin; Zhao Jin; Jiajia Rao; Islam Shahidul; Baochen Fang; Minwei Xu (Food Research International, 2026)

Optimizing water and nitrogen management to balance yield and nitrogen loss in mechanically harvested low-stubble ratoon rice - Chaojie Lan; Hailong Xu; Bin Qin; Jinying Li; Bianhong Zhang; Jingnan Zou; Ting Chen; Jiahui Song; Zhihan Chen; Changxun Fang; Zhixing Zhang; Hongfei Chen; et al. (Field Crops Research, 2026)

MoB2 nanozyme-decorated borate hydrogels with ROS-scavenging and antibacterial abilities for infected diabetic wound healing - Yueguang Fang; Chenxi Li; Ruifang He; Lanling Xiu; Dingwen Xiao; Miao Wang; Yuesheng Dong; Lin Sun; Junwei Ye (Chemical Engineering Journal, 2026)

Scale-up analysis of packed-bed ammonia decomposition reactor for efficient hydrogen production using multiscale model - Lixuan Zhang; Minghao Zhang; Li Lin; Wenshi Huang; Chongqi Chen; Dabiao Wang; Huihuang Fang; Yu Luo; Lilong Jiang (Chemical Engineering Journal, 2026)

Advance in the characteristics, bioactivities, and drug delivery application of chitosan and its derivatives for osteoarthritis: A review - Ruiyuan Zhang; Li Yang; Lin Li; Haiyan Huang; Yao Song; Yicheng Lei; Yuan Hu; Shiyin Chen; Fang Liu (Carbohydrate Polymers, 2026)

Structural characteristics and bioactivities of an exopolysaccharide from mycelial fermentation of a medicinal fungus Cs-HK1 - Fang Ting Gu; Jun Hui Li; Zi Chen Zhao; Yan Yu Zhu; Lin Xi Huang; Jian Yong Wu (Carbohydrate Polymers, 2026)

Instant catapult steam explosion pretreatment combined with ultrasound-assisted organic acid extraction for efficient calcium recovery from crayfish shells - Hong Wang; Qiang Li; Jianfeng Lu; Mengying Ren; Yuan Song; Fang Tao; Lin Lin; Hongsen Zhang; Bin Zheng; Changhu Xue (Bioresource Technology Reports, 2026)

Multifaceted Role of RIMBP2 in Promoting Hearing in Murine Cochlear Hair Cells - Menghui Liao; Xin Chen; Ling Lu; Qing Liu; Rongrong Guo; Yuyang Qiu; Yangnan Hu; Yuhua Zhang; Qiaojun Fang; Panpan Zhang; Yige Li; Shuijin He; et al. (Neuroscience Bulletin, 2026)

Icariside II sensitizes osteosarcoma to doxorubicin through the lincROR/Wnt/β-catenin signaling regulatory axis - Shu-ting Zhou; Zhi-peng Li; Yong-xin Mai; Yu-Yan Wang; Feng-xiang Pang; Jin-fang Zhang; Xian-lin Wu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Discovery of FLF-15 as a novel selective inhibitor of ADAM17 to prevent hepatocellular carcinoma metastasis - Qing Li; Dao-ping Wang; Ting Zhong; Ai-ling Ling-hu; Jia-lin Chen; Fang Luo; Feng Zhang; Ming-zhi Su; Ying Yang; Yan-hua Fan (Molecular Diversity, 2026)

Short-term and long-term effects of outdoor artificial light at night on reproductive hormones among infertile women from a preconception cohort study - Wenbin Fang; Cun Huang; Ying Tang; Mengdie Li; Yaning Sun; Yanlan Tang; Yinyin Chen; Yawen Cao; Jiqi Fang; Kunjing He; Jing Shen; Zhiyuan Huang; et al. (International Journal of Biometeorology, 2026)

Enhancing thermospheric density modeling using bias factor analysis - Yao Wu; Junyu Chen; Chusen Lin; Zijie Li; Yaobin Fang; Yu Wu (Advances in Space Research, 2026)

Two new compounds from the capitula of Chrysanthemum morifolium cv. Fubaiju - Jin-Lin Chen; Yue-Hao Huang; Si-Yu Yang; Xue-Fang Zhuo; Yao-Lan Li; Yu-Bo Zhang; Jun-Jie Zhong; Guo-Cai Wang (Natural Product Research, 2026)

A modeling approach for dynamically assessing the carbon storage potential of the Manila clam Ruditapes philippinarum in typical aquaculture systems - Weiwei Jiang; Weiwei Li; Fan Lin; Jinghui Fang; Yuze Mao; Jianguang Fang; Zengjie Jiang (Aquaculture, 2026)

From parasitic to productive: Leveraging ORR-generated alkalinity for electrochemical lithium recovery via Ti3C2Tx/Li4Ti5O12 microenvironment design - Dezhi Fang; Xueli Zhang; Feng Liu; Sile Hu; Peng Lin; Bowen Li; Peng Zhang; Kexun Li (Water Research, 2026)

A new Coniopteris (Dicksoniaceae) from the Middle Jurassic of the Baojishan Basin, Gansu, China, with discussion on its heteromorphic pinnule characteristics - Lan-Xing Wei; Cun-Lin Xin; Zhi -Peng Jiao; Fang-Fang Zhang; Hong Li (Review of Palaeobotany and Palynology, 2026)

Photovoltaic-driven electrochemistry struvite electrolyzer for sustainable phosphate recovery - Weike Lin; Ying Xiang; Xinglong Wu; Chen Xia; Lanlan Zheng; Jin Li; Fang Wang (Process Safety and Environmental Protection, 2026)

Monoterpenes amplify the oxidative potential of biomass burning secondary aerosols - Xiaowen Chen; Kun Li; Haizhen Bian; Shan Zhang; Xueqi Ma; Li Fang; Wei Jiang; Caiqing Yan; Lin Du (Journal of Hazardous Materials, 2026)

Evaluating technical soil derived from lithium mica residue: Integrating soil quality and life cycle assessment for functional performance and environmental sustainability - Yanqi Li; Zi Guo; Xinyan Lv; Xin Liao; Guilan Duan; Liping Fang; Xiaoliang Li; Xiao Tan; Aijun Lin (Journal of Cleaner Production, 2026)

Low-cholesterol egg yolk lipids alleviated the development of atherosclerosis in ApoE −/− mice by regulating bile acid metabolism and gut microbiota - Le Cheng; Ming Zhang; Fang Wu; Jianguo Dong; Yifei Wang; Lin Dong; Yumeng Ma; Chenyan Zheng; Zihan Wang; Yixuan Li; Ran Wang; Fazheng Ren; et al. (Food Research International, 2026)

Comparison of in vitro digestion and absorption characteristics of human milk triglycerides analogues and human milk lipids - Suqi Wei; Kequn Lin; Quanzhang Li; Meng Wei; Qi Fang; Sufang Duan; Zeyuan Deng; Ting Li; Jing Li (Food Bioscience, 2026)

A pH/glucose dual-responsive Janus dressing with optimized gradient modulus/tissue adhesion promotes diabetic wound healing by dynamic drug-payload release - Huabiao Ye; Ting Dong; Ruoxuan Li; Lihua Fang; Kaifang Xie; Guangting Han; Que Chen; Shan Chi; Jia-Horng Lin; Ching-Wen Lou (Chemical Engineering Journal, 2026)

Hierarchical microstructure PANI@NH4V4O10@CC enables multifunctional pressure sensing and high capacity supercapacitive for self-powered wearable electronics - Yong Wang; Zelin Bai; Wanzhihan Zhang; Hang Li; Ling Li; Youwei Zhao; Haijiao Lin; Chuan Fang; Wenming Zhang (Chemical Engineering Journal, 2026)

Using statistical Change-Point Analysis to refine Holocene estuarine–deltaic transition - Penghui Lin; Guanjun Xu; Xianhe Zhang; Fang Li; Xiaolin Xu; Hongwei Li; Zhongping Lai (CATENA, 2026)

Structural diversity of aldehydes determines covalent versus non-covalent inhibition mechanisms against steroid 5α-reductase type 1: Species-specific differences and preliminary structure-activity relationships - Junying Chen; Shufang Qi; Zijian Lin; Haonan Fang; Putian Zhang; Wanyu Li; Ren-shan Ge; Yiyan Wang (Chemico-Biological Interactions, 2026)

Differential contributions of microbial necromass to humification: Hyperthermophilic vs. conventional thermophilic composting - Minru Liu; Xuechang Ren; Zhenrong Lin; Kejing Fang; Kai Li; Qizhe Fan; Zhen Yu (Bioresource Technology, 2026)

Shadow under the lamp: Evidence-based assessments reveal local extirpation risk of large Indian civets (Viverra zibetha) concealed by intensive activity in human-dominated landscapes - Weiming Lin; Yue Weng; Hongmin Wang; Minhui Li; Qi Wang; Jia A; Qing Zhao; Fang Wang (Biological Conservation, 2026)

Exploring the role of VAV2 rare variants in primary open-angle glaucoma: genetic insights and pathophysiological mechanisms - Runze Li; Yuhong Chen; Shanshan Zhang; Lin Ye; Huaping Tian; Zheng Li; Wentao Wang; Hongjing Li; Ruilin Liao; Haojue Xu; Junlan Chuan; Chao Qu; et al. (Science China Life Sciences, 2026)

How do moss-dominated biocrusts drive carbon sequestration under lithological constraints in karst soils? - Fang Wang; Yuanfeng Yang; Ze Li; Zhe Lin; Zhiyong Fu; Hongsong Chen; Yusong Deng (Plant and Soil, 2026)

STAT3 Signaling Mediates Agomelatine Restoration of Prefrontal Cortex Synaptic Plasticity in Chronic Social Defeat Stress Mice - Chi-Wei Lee; Han-Fang Wu; Hsin-Ju Yen; Lun-De Liao; Wei-Chang Mao; Hsun-Shuo Chang; Yih-Fung Chen; Chia-Hsien Lin; Cheng-Ta Li; Hui-Ching Lin (Molecular Neurobiology, 2026)
Major depressive disorder (MDD) is a major public health issue worldwide. It not only causes an increased socio-economic burden, but also negatively affects personal lives. It has been shown that depression leads to impairments in synaptic plasticity, such as impaired long-term potentiation (LTP) in the prefrontal cortex (PFC). A recent study reported that administration of agomelatine, a melatonin receptor agonist and 5-hydroxytryptamine (5-HT) 2C antagonist, which may be involved in synaptic functions, for 1 week has a rapid antidepressive effect. Moreover, the mechanism of Glycogen synthase kinase 3β (GSK3β), regulated by signal transducer and activator of transcription 3 (STAT3), may play an important role in the synapse-related pathological mechanisms of depression. Hence, we used chronic social defeat stress (CSDS) as an animal model of depression, to investigate whether synaptic plasticity impairment in depression, improved by agomelatine, is mediated through the STAT3 mechanism. The results showed that depressive-like behaviors were reversed after 1 week of agomelatine treatment. Moreover, the impairment of LTP and alteration of spine density were reversed by agomelatine in the PFC. We further applied AG490, an inhibitor of STAT3, to demonstrate that the therapeutic mechanism of agomelatine improves synaptic plasticity through STAT3-regulated phosphorylation of GSK3β. Taken together, these results demonstrated that STAT3-regulated downstream molecules are potential therapeutic targets for the rapid action of antidepressants.

QTL analysis of single-segment substitution lines dissected from a rice CSSL-Z668 and fine-mapping of qGL3.4 for grain length - Si-Qian Xiang; Yu-Zhu Tao; Zhao-Peng Yu; Zhuo-Wen Zhao; Han Zhang; Qiao-Long Li; Lu Li; Ao-Ni Xiang; Jing-Hong Xu; Fan Zhang; Xu Yan; Zheng-Lin Yang; et al. (Euphytica, 2026)

Effects of the dietary proportions of lipids and carbohydrates on milk fat, blood metabolites, and the fecal microbial community in lactating jennies - Shu-xian Zhang; Tao Xu; Qiong-xian Yan; Liang Deng; Allan Degen; Li-lin Liu; Lei Fang; Xiao-ling Zhou (Animal Feed Science and Technology, 2026)

Hierarchical attention and feature enhancement network for multi-scale small targets in pine wilt disease - Jiajun Wang; Li Jin; Fang Wang; Hongping Zhou; Haifeng Lin (Computers and Electronics in Agriculture, 2025)

Large-scale analysis of SARS-CoV-2 genomic data from sewage using eVarEPS reveals that amino acid mutations detected in sewage provide an early warning on population prevalence - Ziquan Lv; Chang Shu; Yulin Fu; Yinghui Li; Shisong Fang; Xiangjie Yao; Qinglan Sun; Kesheng Peng; Jian Lu; Guomei Fan; Dongmei Liu; Jinzhen Tang; et al. (Water Research, 2025)

Nuclear transport factor IPO4 modifies localization by PCV2 and facilitates viral replication - Cui Lin; Chengcheng Wu; Fanfan Zhang; Na Li; Haiqin Li; Lihan Tao; Jia Tan; Yanbing Zeng; Shaopei Fang; Quanyong Zhou (Veterinary Microbiology, 2025)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Biomass electrooxidation-involved carbon radicals boost electrochemiluminescence - Qie Fang; Lin Xu; Lijin Wang; Jingshuai Li; Yan Zhou; Yifei Chen; Wenxuan Jiang; Liuyong Hu; Wenling Gu; Chengzhou Zhu (Science Bulletin, 2025)

Real-time simulation for deep-sea mining system with sea trial validation - Lin Huang; Shuqing Wang; Wencheng Liu; Yuankun Sun; Ying Li; Xuewu Hong; Mingqiang Xu; Lianjin Jiang; Fang Xu; Yuanhe Li; Hai Wu; Chi Zhan (Ocean Engineering, 2025)

Multi-objective optimization of a semi-submersible floating wind Platform: Integrating cost, stability, and strength - Siqi Lai; Hongwei Liu; Yajing Gu; Rongfu Li; Long Fang; Yonggang Lin; Souleymane Drabo; Xiangheng Feng (Ocean Engineering, 2025)

Petrogenesis of Triassic intermediate-felsic intrusions from three skarn tungsten deposits in the East Kunlun Orogenic Belt, NW China: Evidence from zircon U Pb geochronology, petrochemistry, and Hf isotopic characteristics - Yan Tan; Jin-Xiang Li; Fang Xu; Yan-Qian Yang; De-Xin Zhang; Hua-Liang Lai; Sheng-Qiang Ma; Shun-Long Yang; Yi-Jun Yang; Chen Wu; Ya-Hui Yue; Chao Wang; et al. (Lithos, 2025)

Enhancing photocatalytic CO2 reduction over single-crystalline BiOCl nanosheets: A synergistic effect of nickel doping and oxygen vacancies - Qichong Fang; Haoyang Lin; Weirui Chen; Xukai Li; Yiming Tang; Laisheng Li; Jing Wang (Journal of Environmental Chemical Engineering, 2025)

Natural and built environments and heart failure risk: An exposome-wide analysis in the UK Biobank - Xuewei Huang; Siyu Yin; Meng Yao; Fang Lei; Weifang Liu; Lijin Lin; Tao Sun; Yuanyuan Cao; Xingyuan Zhang; Ru Li; Liwen Wang; Yufeng Hu; et al. (Environmental Research, 2025)

Recovery of industrial waste heat for district heating: A complementary heating method and stakeholder coordination - Zichen Rao; Jiayu Li; Pei Liu; Hao Zhou; Yuqing Chen; Hao Fang; Borong Lin (Energy and Buildings, 2025)

HFPO-TA induces liver damage and ferroptosis in zebrafish by disrupting iron metabolism homeostasis - Lin Cheng; Zhonghua Fan; Yu Zhang; Xu Fang; Yuanyuan Wu; Hongru Liu; Lanxi Ye; Li Wang; Hui Liu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Alkylammonium ligands-driven perovskite lattice engineering for white perovskite nanocrystals single emitters - Jean-Sébastien Bénas; Zhen-Li Yan; Wei-Cheng Chen; Chu-Chen Chueh; Jing-Yan Wu; Wei-Wen Chen; Fang-Cheng Liang; Erdi Akman; Yu-Jung Lu; Yen-Yu Wang; Ja-Hon Lin; Ye Zhou; et al. (Chemical Engineering Journal, 2025)

Cobalt-doped sunflower plate-derived porous carbon as a dual-functional cathode host for high-performance Li S batteries via synergistic confinement-catalysis - Ying Fang; Bin Yue; Lin Li; Yuqi Wang; Xinyu Yan; Jinxian Wang; Yang Su; Guixia Liu; Wensheng Yu; Xiangting Dong (Chemical Engineering Journal, 2025)

Electrostatic and functional group-mediated biosorption of microalgae and lead using biosafe Aspergillus oryzae 3.042 fungal pellets - Feili Li; Shiyu Chen; Yijie Lin; Jingjing Fang; Wen Shi; Junjie Qian; Gaoxiang Zhang; Jun Hu (Bioresource Technology, 2025)

Novel compound bacterial agent effects on pig farm wastewater denitrification and nitrogen transformation - Rong Gao; Zhuangzhuang Liu; Weikun Li; Liu Lou; Tong Xu; Lin Shi; Jie Cao; Jun Fang; Gang Liu (Bioresource Technology, 2025)

Chemical constituents of Rhododendron virgatum Hook and their chemotaxonomic significance - Gui-fang Li; Xin Wang; Hong-ying Chen; Shuai Huang; Lin Chen; Xian-li Zhou (Biochemical Systematics and Ecology, 2025)

Chicago Sky Blue 6B modulates MAPK/NF-kB pathway in rat knee osteoarthritis - Yejin Zhang; Weiqing Li; Yu Bai; Hehuan Lai; Jiawei Fang; Lin Ye; Dengwei He; Zhenzhong Chen (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Synergistic effects and mechanism of recombinant viral vector-mediated STAT1 overexpression and STAT3 silencing on glioma U251 apoptosis - Xin-Long Hu; Hong Li; Guo-Dong Zhang; Chao Lin; Ping Huang; Xiu-Feng Chen; Fang Wan; Chang-Wu Dou; Hai-Tao Ju (Molecular Biology Reports, 2025)

Correction: Severe enterovirus A71 pathogenesis and immune responses in human nucleolin transgenic mice - Nien-En Hsiao; Ya-Fang Wang; Yi-Chen Lin; Wei-Ting Chou; Li-Jin Hsu; Shih-Min Wang; Jen-Ren Wang; Ming-Derg Lai; Shun-Hua Chen; Chuan-Fa Chang (Medical Microbiology and Immunology, 2025)

Severe enterovirus A71 pathogenesis and immune responses in human nucleolin transgenic mice - Nien-En Hsiao; Ya-Fang Wang; Yi-Chen Lin; Wei-Ting Chou; Li-Jin Hsu; Shih-Min Wang; Jen-Ren Wang; Ming-Derg Lai; Shun-Hua Chen; Chuan-Fa Chang (Medical Microbiology and Immunology, 2025)

MOF promotes cisplatin resistance in lung cancer cells by enhancing WSTF acetylation - Qian Sui; Dongsheng Lin; Fang Huang; Haijian Hu; Xiaohui Liu; Zheng Li; Jiheng Liu (In Vitro Cellular & Developmental Biology - Animal, 2025)

Histological studies on the ontogeny of the big-belly seahorse (Hippocampus abdominalis) - Yuanyuan Xue; Lu Tang; Chunhui Lv; Fang Wang; Xiaolei Su; Mingzhu Li; Yuping Hou; Jie Dong; Chengde Fan; Jiezhou Wang; Lin Shi; Qunhao Zhou; et al. (Fish Physiology and Biochemistry, 2025)

Smartphone-assisted ratiometric fluorescence detection of sodium salicylate based on a dual-ligand Eu(III)-MOF - Zhong-Lin Li; Fang-Hua Zhao; Fang Mi; Shan Zhang; Ming Guan; Jinmao You (Analytica Chimica Acta, 2025)

Serum cortisol and AdipoR2 rs12342 were involved in the correlation between stress and serum cholesterol in a gender-specific manner - Yi Lin Shen; Qi Wei Guo; Xue Cheng Li; Ke Xin Jia; Jun Yi Liu; Yan Zhi Yi; Jun Tao Ren; Jia Jing Cai; Guo Ming Su; Jia Lin; Ding Zhi Fang (Metabolic Brain Disease, 2025)

The nonstructural protein 13 of porcine deltacoronavirus exhibits an ATP- independent and nondirectional annealing activity that is inhibited by Mg2+ - Lihan Tao; Chengcheng Wu; Cui Lin; Na Li; Shaopei Fang; Jianzhen Huang (Veterinary Microbiology, 2025)

Identification and evaluation of Nordihydroguaiaretic acid (NDGA) as an active traditional Chinese medicine compound inhibiting the 3C-like protease of feline infectious peritonitis virus - Wei Yuan; Xiaoen Pang; Jingru Zhu; Zan Chen; Shuna Li; Zhibo Yang; Xiaohu Zhang; Changbin Jin; Xintong Huang; Yu Shen; Huarong Fang; Jiahao Lin; et al. (Veterinary Microbiology, 2025)

Analysis of cellular and gene therapy product reviews in the United States - Cheng-Fang Weng; Jhe-Yuan Dong; Shiuan-Fei Lin; Ai-Lei Jiang; Yu-Li Cheng; Lin-Chau Chang (Regulatory Toxicology and Pharmacology, 2025)

Biocontrol potential and antifungal mechanism of a novel Bacillus velezensis NH-13–5 against Botrytis cinerea causing postharvest gray mold in table grapes - Lin Xiao; Jin-Tian Wang; Dong-Fang Cao; Hong Li; Hong-Yu Fang; Tian-Li Qu; Bao-Hua Zhang; Shuai-Shuai Li; Feng-Yu Du (Postharvest Biology and Technology, 2025)

Varroa destructor infestation amplifies imidacloprid vulnerability in Apis mellifera - Yinchen Wang; Xijie Li; Chunhui Miao; Chonghui Zhao; Jun Zhang; Yantao Pang; Junjie Li; Richan Fang; Xueyi Shen; Ying Lin; Tian Zhao; Mengqing Deng; et al. (Pesticide Biochemistry and Physiology, 2025)

Biogenic synthesis of selenium nanoparticles by Bacillus amyloliquefaciens: A promising method for mitigating mycotoxin contamination and fighting Fusarium graminearum - Ezzeldin Ibrahim; Yan Fang; Raghda Nasser; Dan Wang; Doaa Abd El-maksoud Khalil Kafsheer; Solabomi Olaitan Ayoade; Rahila Hafeez; Wafa Abdullah I. Al-Megrin; Bin Li; Haiping Lin (Journal of Hazardous Materials, 2025)

The dual role of organic carbon: Mitigation of nitrogen-induced soil acidification but amplification of greenhouse gas emissions - Lin Zhao; Qinghua Li; Yufang Lu; Hongmei Chen; Ju Min; Ren Fang Shen; Xue Qiang Zhao (Journal of Environmental Management, 2025)

Mechanisms of high yield formation and carbon budget surplus in ratoon rice and its rhizosphere microecological responses - Jinying Li; Hailong Xu; Bin Qin; Bianhong Zhang; Mengying Chen; Peiying Weng; Chunlin Guo; Chaojie Lan; Jingnan Zou; Zhimin Lin; Wenfang Lin; Wenfei Wang; et al. (Field Crops Research, 2025)

Association of compound exposure to heat wave and ozone pollution with cause-specific cardiopulmonary mortality: A space-time-stratified case-crossover study - Kang Ma; Fengman Fang; Yuesheng Lin; Fei Tong; Cheng He; Youru Yao; Jingli Zhu; Huadong Wang; Xiuya Xing; Feiyan Zhang; Ruoxi Li (Environmental Research, 2025)

Microplastic contamination in waterbirds and their habitats: evidence from little egrets (Egretta garzetta) in tropical rice fields - Han-xun Qiu; Chuan-biao Xu; Xin Huang; Xiang-yin Wei; Zi-lin Pang; Lan-fang Du; Li Jiang; Ji-liang Zhang (Environmental Research, 2025)

Cobalt-embedded carbon nanotube-bridged hollow carbon cubes enabling electron/ion co-transport and catalytic conversion in lithium-sulfur batteries - Xinyu Yan; Bin Yue; Lin Li; Yuqi Wang; Ying Fang; Ye Li; Yang Su; Jinxian Wang; Wensheng Yu; Xiangting Dong (Chemical Engineering Journal, 2025)

Synergistic cation-anion interface engineering for uniform zinc deposition and stress mitigation in reinforced Zn metal anodes - Yixing Fang; Ping Li; Feng Sun; Chuyuan Lin; Xiao Yang; Zhen Wang; Guodong Miao; Lingxing Zeng; Yongchang Liu; Xuanhui Qu (Chemical Engineering Journal, 2025)

Simultaneous quantitative point-of-care detection of nucleic acid and protein biomarkers for acute myocardial infarction using bright aggregation-induced emission nanoparticles - Yue Cao; Peng Li; Zhiwei Guo; Yuhang Yang; Kuangrou Jia; Zihao Xu; Banglao Xu; Guanfeng Lin; Fang Hu; Zhenhua Chen; YingSong Wu (Chemical Engineering Journal, 2025)

Stable and efficient n-type perylene diimides radical as cathode interlayer with wide thickness tolerance for organic solar cells - Lin Hu; Senmei Lan; Guobin Shen; Fang Wang; Yingzhi Jin; Zhen Su; Jia Yao; Mengzhen Du; Zheng Yan; Wei Li; Dan Zhou; Erjun Zhou; et al. (Chemical Engineering Journal, 2025)

HFPO-TA exposure triggers hepatomegaly and lipid peroxidation via Nrf2/keap1 antioxidant dysregulation and ferroptosis activation in the liver - Xu Fang; Zhonghua Fan; Mengjiao Li; Zhi Li; Lin Cheng; Yuanyuan Wu; Li Wang; Hui Liu (Chemico-Biological Interactions, 2025)

Food-derived bioactive peptides: health benefits, structure–activity relationships, and translational prospects - Hongda Chen; Jiabei Sun; Haolie Fang; Yuanyuan Lin; Han Wu; Dongqiang Lin; Zhijian Yang; Quan Zhou; Bingxiang Zhao; Tianhua Zhou; Jianping Wu; Shanshan Li; et al. (Journal of Zhejiang University-SCIENCE B, 2025)

Human adenovirus in Taiwan, 2019–2023 - Su-Lin Yang; Wan-Ju Tsai; Chung-Hao Li; Yu-Hsin Cheng; Shu-Wei Lin; Ming-Tsan Liu; Fang-Tzy Wu (Archives of Virology, 2025)

Multivariate explainable machine learning assists in redefining high-performance phosphate removal by layered double hydroxides - Peng Zhang; Yafei Li; Silu Huo; Peng Lin; Dezhi Fang; Sile Hu; Bowen Li; Zikang Xu; Xinyuan Qiu; Kexun Li; Hao Wang (Water Research, 2025)

Assessment of environmental and health impacts during 3D printing of candidate polymeric materials for space additive manufacturing - Junling Li; Yi Liu; Chao Peng; Qifan Liu; Wei Zhao; Mingyuan Liu; Xinyu Du; Yongyin Yan; Yufei Song; Kaihui Xia; Chun Chen; Haijie Zhang; et al. (Journal of Hazardous Materials, 2025)

Maternal placental growth factor mediates the association between PM2.5 and its constituents with adverse pregnancy outcomes - Yuanyuan Yu; Wenjun Fan; Jiayan Ni; Xiaoli Gao; Weixia Li; Jianqiong Zheng; Hongping Zhang; Juan Chen; Qisijing Liu; Zi Lin; Bin Chen; Yajuan Wang; et al. (Journal of Hazardous Materials, 2025)

The mobility, host, and co-occurrence of antibiotic resistance genes in multi-type pig manure-soil systems: Metagenome assembly analysis - Xiangyue Xu; Xvdong Lin; Mengya Fang; Meixia Huo; Ziyan Kou; Wenjin Ma; Xiaoqian Li; Qiuqi Cheng; Hanyu Wang; Lingli Huang (Journal of Environmental Management, 2025)

Effects of puerarin on growth performance, digestive ability, immune response, and resistance to ammonia stress in Pacific white shrimp (Litopenaeus vannamei) in low-salinity water - Yu-Lin Chang; Long Qi; Chao-Li Guan; Yu-Yun He; Wen-Xing Lu; Guo-Fang Zhong (Fish & Shellfish Immunology, 2025)

Bond-oriented selective hydrogenation of unsaturated aldehyde by the tailoring of electronic metal-support interaction - Lin Ai; Peidong Li; Hui Ding; Yutong Jiao; Fang Lu; Jiaxu Liu; Xiao-Feng Wu; Shengjun Huang (Chemical Engineering Journal, 2025)

Synergistic solar-magnetic desalination via covalently anchored Fe₃O₄/hydrogel composites - Juan Du; Hao Fang; Jialiang Ma; Jing Lin; Shikuo Li; Yu Jiang; Fangzhi Huang (Chemical Engineering Journal, 2025)

A stable silicon anode with closed-pore structure constructed via trace ammonia-induced etching for lithium-ion batteries - Fenghui Li; Hao Wu; Fang Wang; Yang Yang; Hong Wen; Wen-Feng Lin; Lianbang Wang (Chemical Engineering Journal, 2025)

Self-healing and thickness-insensitive perylene diimide-based cathode interfacial layers for organic solar cells - Wei Chen; Dan Zhou; Lin Hu; Jiangang Ma; Guobin Shen; Wentian Wan; Shuhua Wang; Fang Wang; Ruizhi Lv; Bin Hu; Haitao Xu; Zaifang Li; et al. (Chemical Engineering Journal, 2025)

Both biotic and abiotic soil N₂O productions are lower under organic N than inorganic N deposition in a Moso bamboo forest - Wenting Jiang; Yan Wang; Yongxin Lin; Hiroko Akiyama; Yunying Fang; Tony Vancov; Shenglei Fu; Hojeong Kang; Xinli Chen; Zhengqin Xiong; Zhijie Li; Shuijin Hu; et al. (Biology and Fertility of Soils, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

DEHP and its metabolite MEHP exposure impairs endometrial decidualization during early pregnancy via up-regulation of Mtmr6 - Li-Ping Tan; Liu Yuan; Yan Zhang; Jun-Lin He; Xin Yin; Yi-Dan Ma; Xue-Mei Chen; Wei-Ke Li; Fang-Fang Li; Ru-Fei Gao (Reproductive Toxicology, 2025)

Olfactory dysfunction induced by pesticides: Adverse outcomes, emerging mechanisms, and risk for neurodegenerative diseases - Lin Wang; Si-Yang Liu; Han-Yue Zheng; Shou-Min Fang; Li Zhuo; Feng Xu; Quan-You Yu (Pesticide Biochemistry and Physiology, 2025)

FTUVE based global fast terminal backstepping sliding mode control for dynamic positioning ships - Lin Li; Chen Wang; Ke Lu; Zhengkang Wu; Fang Deng (Ocean Engineering, 2025)

Alternative splicing of OsNPR3 promoted by the bacterial TAL effectors-targeted splicing regulator OsRBP11 antagonizes OsNPR1 function and enhances disease susceptibility in rice - Xiaochen Chen; Xiaohui Yao; Fang Yan; Shaofang Li; Zuo-Dong Wang; Fu-You Yin; Miao Zhou; Zhen Wang; Lina Qin; Baoguo Zhao; Kai Lu; Liyuan Zhang; et al. (Molecular Plant, 2025)

Recent advances in bioassays for assessing the toxicity of environmental contaminants in effect-directed analysis - Yao Liu; Minjie Li; Qi-Lin Wan; Xun Wang; Monika Mortimer; Wen-Di Fang; Liang-Hong Guo (Journal of Environmental Sciences, 2025)

Dynamic changes in metabolites during the manufacture of three distinct flavor types of Tieguanyin - Lin Zeng; Yan-Qing Fu; Jin-Long Liu; Yuan-Chao Li; Shui-lian Gao; Ying Gao; Fang Wang; Yong-Quan Xu (Food Chemistry, 2025)

Boosting the initial Coulombic efficiency of Bi2S3-based anode for practical sodium-ion batteries - Lankun Shi; Rongji Jiao; Dawei Lan; Li Wang; Yu Gao; Meng-Fang Lin; Zhongmin Lang; Wenxiu He; Guixiao Jia; Jinlong Cui; Shaohui Li (Chemical Engineering Journal, 2025)

Multiple endogenous aldehydes amplify acetaminophen-induced liver injury - Hong Pan; Qi Luo; Qiuyi Jing; Lin Chen; Ni Li; Chao Fang; Fuguo Shi (Chemico-Biological Interactions, 2025)

Multidecadal modulation of multi-year El Niño events over the past millennium - Shuheng Lin; Keyan Fang; Hao Wu; Hanjie Fan; Feifei Zhou; Jinbao Li; Kaiqiang Deng; Hans W. Linderholm; Song Yang (Science China Earth Sciences, 2025)

Screening of Antibiotic-Sensitive Lactic Acid Bacteria (LAB) Associated with the Gut of Penaeus Vannamei and its Application in Shrimp Farming - Yiwen Gu; Xiu Lin; Yanxu Lu; Shuguang Fang; Kun Hu; Xin Ju; Liangzhi Li; Zhi Chen (Current Microbiology, 2025)

Evaluating the sustainability potential of perennial rice in southeastern China by comparing yield, environmental impacts and economic benefits - Hailong Xu; Bianhong Zhang; Bin Qin; Jinying Li; Chaojie Lan; Jingnan Zou; Yazhou Liu; Chunlin Guo; Zhimin Lin; Qiaohong Fan; Changxun Fang; Zhixing Zhang; et al. (Agriculture, Ecosystems & Environment, 2025)

Overview of Non-Destructive Exploration Technologies for Complex Urban Underground Spaces - Jiu-lin Li; Han-ming Zhang; Tian-cai Li; Fang-ning Li; Yong-hui Li; Jian-ning Wang (Applied Geophysics, 2025)

Shewanella mytili sp. nov., a novel bacterial species isolated from the intestinal tract of Mytilus edulis in the South China Sea - Suyun Fang; Jun Min; Haikun Zhang; Yan Li; Xingyue Lin; Xiaoke Hu (Antonie van Leeuwenhoek, 2025)

Changes in growth and transcriptome expression patterns in mandarin fish (Siniperca scherzeri) under different photoperiods - Jiao Li; Yong Wei; Jun Song; Jun Yang; Xu-Fang Liang; Ke Lu; Qiuling Wang; Ke-Xiang Wang; Kaiting Zhi; Dan Zhao; Yan Wang; Yufeng Zhang; et al. (Acta Oceanologica Sinica, 2025)

Cognitive reserve mitigates cognitive impairment in cerebral small vessel disease by protecting white matter fibers: an automated fiber quantification study - Mingyu Li; Yachen Shi; Lin Ma; Haixia Mao; Min Xu; Qianqian Gao; Jiayi Yang; Feng Wang; Xiangming Fang; Xiaoyun Hu (Brain Imaging and Behavior, 2025)

Xanthine oxidase inhibitory constituents from the roots of Ampelopsis japonica - Yu-Lin Li; Fen Liu; Li-Yun Zhao; Han-Xiang Li; Aikebaier Jumai; Zhi-Fang Xu; Sheng-Xiang Qiu (Natural Product Research, 2025)

Pharmacokinetic study of Vibrio parahaemolyticus phage Фvp140 in Litopenaeus vannamei following oral administration - Di Fang; Laizhuang Jin; Qianhui Song; Xiong Zou; Lei Feng; Letian Li; Hui Zhang; Kun Hu; Mao Lin; Wenhong Fang (Aquaculture, 2025)

Multi-omics analysis reveals BPF exposure causes hepatic glucose and lipid metabolism disorder in rats by disrupting energy homeostasis - Zhi Li; Yuanyuan Wu; Mingqing Qian; Bingya Zhang; Xinxin Deng; Penghui Mao; Zhonghua Fan; Xu Fang; Lin Cheng; Xuan Liu; Li Wang; Hui Liu (Toxicology, 2025)

Extension rate variations across the South Tibetan rifts – New data from the northern Xainza-Dinggye Graben - Marie-Luce Chevalier; Ziqi Fang; Shenqiang Chen; Jiawei Pan; Haibing Li; Kungang Wu; Fucai Liu; Junyi Wang; Lin Ding (Tectonophysics, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Structural characteristics of two polysaccharides from L. fumosum (Pers.) P.D. Orton. and their immunomodulatory effects on RAW264.7 macrophages - Rui-Fang Zhong; Wen-Lin Sun; Yi-Meng Li; Jian Chen (Food Research International, 2025)

Cobalt-modification on UiO-bpydc MOF facilitates ligand-to-metal charge transfer for superior visible-light photocatalytic degradation of refractory fluoroquinolone antibiotics - Kaichun Lin; Jingjun Qin; Zhang Liu; Weicheng Xu; Meng Li; Yuanzhi Zheng; Wei Han; Guangying Zhou; Jianzhang Fang; Zhanqiang Fang; Feng Peng; King Lun Yeung (Environmental Research, 2025)

Sustainable conversion of liquefied-chitin to anti-bacterial and photothermal polyurethane foams for efficient desalination of seawater - Xiwei Guo; Yijie Li; Qian Zhang; Dongxu Wang; Lin Fang; Zhifen Wang; Xingfang Xiao; Yucang Zhang (Chemical Engineering Journal, 2025)

Sequential delivery of anti-inflammatory and anti-scar drugs by Rg3 liposome-embedded thiolated chitosan hydrogel eye drops for corneal alkali burn - Huan Tang; Xinnan Li; Chunmei Li; Wenhao Shen; Lin Jin; Yumeng Zhou; Wenna Jiao; Lijun Zhang; Fang Cheng (Carbohydrate Polymers, 2025)

Exploring Lumbar Ligamentum Flavum, Disc Height and Foraminal Height Variations Across Different Postures: A Cadaveric Computed Tomography Investigation - Yuan-Fu Liu; Nozomu Inoue; Yu-Hua Dean Fang; Jing-Yao Wang; Alejandro A. Espinoza Orías; Chao-Jui Chang; Cheng-Li Lin (Journal of Medical and Biological Engineering, 2025)

Genesis of the South Pit Deposit in Jiama District, Tibet: Constraints from Geology, Geochronology and Amphibole Geochemistry - Pan Tang; Juxing Tang; Bin Lin; Aorigele Zhou; Faqiao Li; Xiang Fang; Jing Qi; Mengdie Wang; Yan Xiong; Yuke Xie; Zhengkun Yang; Xiaofeng Yao (Journal of Earth Science, 2025)

Recommendations of Stable Mg, Si, V, Fe, Cu, Zn, Rb, Sr, Ag, Cd, Ba, and U Isotope Compositions for Multiple Geological References - Jinting Kang; Xuqi Chen; Xi Deng; Yuan Fang; Haichuan Jiang; Chengyihong Liu; Cuihua Luo; Xing Li; Yuchao Lin; Zhaoqi Ren; Jiaru Sheng; Xue Tang; et al. (Journal of Earth Science, 2025)

Phage Therapy Enhances Survival, Immune Response, and Metabolic Resilience in Pacific White Shrimp (Litopenaeus vannamei) Challenged with Vibrio parahaemolyticus - Chao Zeng; Long Qi; Chao-Li Guan; Yu-Lin Chang; Yu-Yun He; Hong-Zheng Zhao; Chang Wang; Yi-Ran Zhao; Yi-Chen Dong; Guo-Fang Zhong (Fishes, 2025)
Acute hepatopancreatic necrosis disease (AHPND), caused by the bacterium Vibrio parahaemolyticus, is a major threat to global shrimp aquaculture. In this study, we evaluated the therapeutic effects of phage therapy in Litopenaeus vannamei challenged with AHPND-causing Vibrio parahaemolyticus. Phage application at various concentrations significantly improved shrimp survival, with the 1 ppm group demonstrating the highest survival rate. Enzymatic assays revealed that phage-treated shrimp exhibited enhanced immune enzyme activities, including acid phosphatase (ACP), alkaline phosphatase (AKP), and lysozyme (LZM). In addition, antioxidant defenses such as superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GSH-PX), and total antioxidant capacity (T-AOC) significantly improved, accompanied by reduced malondialdehyde (MDA) levels. Serum biochemical analyses demonstrated marked improvements in lipid metabolism, particularly reductions in triglyceride (TG), total cholesterol (TC), and low-density lipoprotein (LDL), alongside higher levels of beneficial high-density lipoprotein (HDL). Transcriptomic analysis identified 2274 differentially expressed genes (DEGs), notably enriched in pathways involving fatty acid metabolism, peroxisome functions, lysosomes, and Toll-like receptor (TLR) signaling. Specifically, phage treatment upregulated immune and metabolic regulatory genes, including Toll-like receptor 4 (TLR4), myeloid differentiation primary response protein 88 (MYD88), interleukin-1β (IL-1β), nuclear factor erythroid 2-related factor 2 (Nrf2), and peroxisome proliferator-activated receptor (PPAR), indicating activation of innate immunity and antioxidant defense pathways. These findings suggest that phage therapy induces protective immunometabolic adaptations beyond its direct antibacterial effects, thereby providing an ecologically sustainable alternative to antibiotics for managing bacterial diseases in shrimp aquaculture.

Tissue and cell types infected by Ecytonucleospora hepatopenaei (EHP) - Yuan Wang; Shi-ting Lin; Ming Zhao; Peng Di; Jun-fang Zhou; Shou-hu Li; Yan-qing Huang; Ying Na; Xin-cang Li; Wen-hong Fang (Journal of Invertebrate Pathology, 2025)

Regulating the Cu-Ce interaction of CuCeOx/SAPO-34 catalysts to achieve a wide reaction temperature window for the collaborative synergistic removal of NOx and toluene at low temperatures and reaction mechanisms - Rong Liu; Xuehui Jia; Lin Li; Fengying Li; Xiang Tu; Weicheng Xu; Hansun Fang; Danping Li; Hong Huang; Chenglong Yu (Journal of Hazardous Materials, 2025)

Protective effects of loquat leaf on tobacco-specific carcinogen NNK induced lung epithelial cell injury in vitro and in vivo by regulating miR-328-3p - Yingjie Wang; Zimu Liu; Fanyan Fang; Yapeng Liang; Bin Lin; Huiming Hua; Gang Chen; Di Zhou; Ning Li (Food Bioscience, 2025)

Formation and evolution of overpressure and its control on hydrocarbon accumulation in the Yinggehai Basin - Lu Yang; Lin Hu; Gaowei Hu; Yazhen Zhang; Jinqiang Tian; Fang Hao; Zonglin He; Yue Xue; Xuezhe Li; Ziqi Feng; Chunlei Li; Baibing Yang (Science China Earth Sciences, 2025)

Liquid–liquid phase separation in normal hematopoiesis and hematological diseases - Lexuan Lin; Fang He; Xu Jin; Xiaoru Zhang; Yue Li; Di Wang; Jingwei Wang; Lingyue Zheng; Haoze Song; Xu Zhu; Qimei Cheng; Yitong Zhao; et al. (Cell and Tissue Research, 2025)

Genomic analysis of the novel Stenotrophomonas phage vB_Srh_LBjhp91a, isolated from a Karst cave in China - Lou Ren; Zheng Fang; Shixia Li; Qingshan Wu; Lan Xiang; Chuangen Lin; Qiuping Liu; Leitao Tan; Qingbei Weng (Archives of Virology, 2025)

A Deep Learning Framework for Parameter Estimation in 1D Marine Ecosystem Model - Ao Li; Kewei Zhao; Weiwei Fang; Chan Shu; Runjie Zhou; Qiuyi Li; Xiaolong Huang; Xiaohong Lei; Menghan Xu; Haoyu Jiang; Lin Mu (Journal of Marine Science and Engineering, 2025)
Marine ecosystems play an increasingly critical role in both global climate regulation and the impacts of anthropogenic activities. Accurate marine biogeochemical numerical models are essential tools for understanding and predicting the complex dynamics of these systems. However, as model complexity increases, so does the number of biological parameters and the uncertainties associated with them, which can substantially affect model performance. Consequently, efficient and reliable parameter estimation has become a key challenge in model development and application. In this study, we proposed a deep learning-based approach for parameter estimation in numerical models, utilizing deep neural networks to capture the complex nonlinear relationships between numerical model input parameters and output variables. A one-dimensional marine ecosystem model is employed as a case study to evaluate the effectiveness of the proposed method. The results demonstrate that (1) the deep learning approach provides an automated and adaptive solution for parameter estimation, significantly improving the efficiency of model calibration in engineering and scientific applications by enabling rapid identification of near-optimal parameter sets; and (2) the deep learning model effectively learns the underlying nonlinear mappings between inputs and outputs. During training, the mean squared error (MSE) loss exhibits a steady decline, with minor fluctuations in the early stages, ultimately converging to a stable value. The predicted parameter combinations show strong agreement with the reference numerical model outputs, yielding correlation coefficients exceeding 0.95.

Rakicidin J and K, two cytotoxic and antibacterial cyclic depsipeptides from the marine bacterium Micromonospora chalcea - Li Chen; Lijun Xie; Jian Zhou; Dongsheng Fang; Honglei Jiang; Wei Liu; Yuqiu Ye; Wei Zhao; Hong Jiang; Feng Lin (Natural Product Research, 2025)

Searching for neutrinoless double-beta decay of 136 Xe with PandaX-4T - Shu Zhang; Zihao Bo; Wei Chen; Xun Chen; Yunhua Chen; Zhaokan Cheng; Xiangyi Cui; Yingjie Fan; Deqing Fang; Zhixing Gao; Lisheng Geng; Karl Giboni; et al. (Science Bulletin, 2025)

Mechanistic insights into temoporfin-based photodynamic therapy: Ferroptosis as a critical regulator under normoxic and hypoxic conditions in head and neck cancer - Tong-Hong Wang; Li-Fang Chou; Yen-Wen Shen; Nan-Chin Lin; Yin-Hwa Shih; Tzong-Ming Shieh (Journal of Photochemistry and Photobiology B: Biology, 2025)

Microplastics and nanoplastics increase major adverse cardiac events in patients with myocardial infarction - Yun Zhang; Qianhui Gao; Qiang Gao; Mingcheng Xu; Ning Fang; Lin Mu; Xuejie Han; Hui Yu; Song Zhang; Yue Li; Yongtai Gong (Journal of Hazardous Materials, 2025)

Elucidating the interaction mechanism of rutin with β-casein and β-lactoglobulin: A comprehensive analysis using multi-spectroscopy, molecular docking, and molecular dynamic simulations - Hailin Wang; Leiwen Xiang; Zhuangwei Zhang; Guoqiang Li; Peng Li; Wentao Chen; Yu Fang; Xinyan Lin; Shufen Lin (Food Chemistry, 2025)

Characterization of GR-14 peptide from Cordyceps militaris mycelial albumin and its mechanism of heat protection on Lactobacillus fermentum J26 - Ping-Ping Gao; Han-Qing Liu; Qian-Wang Zheng; Zhi-Wei Ye; Li-Qiong Guo; Yuan Zou; Jun-Fang Lin (Food Bioscience, 2025)

Photogenerated electron transfer in Ni/NiO supported on g-C3N4 enables sustainable catalytic activation of peroxymonosulfate for emerging pollutant removal - Runqi Li; Zhang Liu; Jingjun Qin; Kaichun Lin; Weicheng Xu; Meng Li; King Lun Yeung; Ximiao Zhu; Jianzhang Fang; Guangying Zhou; Zhanqiang Fang (Environmental Research, 2025)

Association of prenatal exposure to perfluoroalkyl and polyfluoroalkyl substances with fetal growth trajectories - Yi Yang; Sheng Teng; Leshi Lin; Wenjuan Li; Zhenzhen Zhu; Tangxin Chen; Li Li; Fang Peng; Dongmei Peng; Xiao Gao (Environmental Research, 2025)

Synergetic carbon emission reduction in the construction industry: A spatial correlation perspective from urban agglomerations in southeast coastal China - Xiaojuan Li; Gaona Duan; Chengxin Lin; Yun Lin; Jieyi Chen; Congying Fang; Tinghui Zhang (Energy and Buildings, 2025)

Selective interfacial polymerization improves reversibility of Si anodes - Wen Yang; Shuwei Li; You Liu; Yanyan Li; Ping Jiang; Xiaobo Hong; Gaofeng Li; Bo Fan; Fang Chen; Liangdong Lin; Zhijun Qiao; Dianbo Ruan (Chemical Engineering Journal, 2025)

Identifying Novel QTLs and Candidate Genes for Tillering Ability in Sugarcane (Saccharum spp.) - Junteng Fang; Ruiqiang Lai; Zaid Chachar; Yiyun Gui; Lina Fan; Huanzhang Lin; Weijun Cai; Yueping Su; Weiwei Chen; Xiaoming Xue; Yucong Li; Liping Xu; et al. (Sugar Tech, 2025)

Epigenetics in the modern era of crop improvements - Yan Xue; Xiaofeng Cao; Xiangsong Chen; Xian Deng; Xing Wang Deng; Yong Ding; Aiwu Dong; Cheng-Guo Duan; Xiaofeng Fang; Lei Gong; Zhizhong Gong; Xiaofeng Gu; et al. (Science China Life Sciences, 2025)
Epigenetic mechanisms are integral to plant growth, development, and adaptation to environmental stimuli. Over the past two decades, our comprehension of these complex regulatory processes has expanded remarkably, producing a substantial body of knowledge on both locus-specific mechanisms and genome-wide regulatory patterns. Studies initially grounded in the model plant Arabidopsis have been broadened to encompass a diverse array of crop species, revealing the multifaceted roles of epigenetics in physiological and agronomic traits. With recent technological advancements, epigenetic regulations at the single-cell level and at the large-scale population level are emerging as new focuses. This review offers an in-depth synthesis of the diverse epigenetic regulations, detailing the catalytic machinery and regulatory functions. It delves into the intricate interplay among various epigenetic elements and their collective influence on the modulation of crop traits. Furthermore, it examines recent breakthroughs in technologies for epigenetic modifications and their integration into strategies for crop improvement. The review underscores the transformative potential of epigenetic strategies in bolstering crop performance, advocating for the development of efficient tools to fully exploit the agricultural benefits of epigenetic insights.

Responses of carbon storage to thinning intensity of Larix principis-rupprechtii Mayr - Kuangji Zhao; Yifei Lin; Shilong He; Chuan Fan; Shun Gao; Fang He; Ziteng Luo; Guirong Hou; Gang Chen; Zhongkui Jia; Xianwei Li (Mitigation and Adaptation Strategies for Global Change, 2025)

Rational design and pairing of single-domain antibodies for developing rapid detection methods for botulinum neurotoxins A and B - Ruomei Lv; Jiaxin Li; Xinyu Fang; Li Tang; Rui Shi; Jin Wang; Wenjing Zhang; Jinglin Wang; Guangyu Zhao; Jing Wang; Shan Gao; Xuefang Xu; et al. (Analytica Chimica Acta, 2025)

Application of a Dual-Stream Network Collaboratively Based on Wavelet and Spatial-Channel Convolution in the Inpainting of Blank Strips in Marine Electrical Imaging Logging Images: A Case Study in the South China Sea - Guilan Lin; Sinan Fang; Manxin Li; Hongtao Wu; Chenxi Xue; Zeyu Zhang (Journal of Marine Science and Engineering, 2025)
Electrical imaging logging technology precisely characterizes the features of the formation on the borehole wall through high-resolution resistivity images. However, the problem of blank strips caused by the mismatch between the instrument pads and the borehole diameter seriously affects the accuracy of fracture identification and formation continuity interpretation in marine oil and gas reservoirs. Existing inpainting methods struggle to reconstruct complex geological textures while maintaining structural continuity, particularly in balancing low-frequency formation morphology with high-frequency fracture details. To address this issue, this paper proposes an inpainting method using a dual-stream network based on the collaborative optimization of wavelet and spatial-channel convolution. By designing a texture-aware data prior algorithm, a high-quality training dataset with geological rationality is generated. A dual-stream encoder–decoder network architecture is adopted, and the wavelet transform convolution (WTConv) module is utilized to enhance the multi-scale perception ability of the generator, achieving a collaborative analysis of the low-frequency formation structure and high-frequency fracture details. Combined with the spatial channel convolution (SCConv) to enhance the feature fusion module, the cross-modal interaction between texture and structural features is optimized through a dynamic gating mechanism. Furthermore, a multi-objective loss function is introduced to constrain the semantic coherence and visual authenticity of image reconstruction. Experiments show that, in the inpainting indexes for Block X in the South China Sea, the mean absolute error (MAE), structural similarity index (SSIM), and peak signal-to-noise ratio (PSNR) of this method are 6.893, 0.779, and 19.087, respectively, which are significantly better than the improved filtersim, U-Net, and AOT-GAN methods. The correlation degree of the pixel distribution between the inpainted area and the original image reaches 0.921~0.997, verifying the precise matching of the low-frequency morphology and high-frequency details. In the inpainting of electrical imaging logging images across blocks, the applicability of the method is confirmed, effectively solving the interference of blank strips on the interpretation accuracy of marine oil and gas reservoirs. It provides an intelligent inpainting tool with geological interpretability for the electrical imaging logging interpretation of complex reservoirs, and has important engineering value for improving the efficiency of oil and gas exploration and development.

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Deriving leaf-scale chlorophyll index (CIleaf) from canopy reflectance by correcting for the canopy multiple scattering based on spectral invariant theory - Chenpeng Gu; Jing Li; Qinhuo Liu; Hu Zhang; Alfredo Huete; Hongliang Fang; Liangyun Liu; Faisal Mumtaz; Shangrong Lin; Xiaohan Wang; Yadong Dong; Jing Zhao; et al. (Remote Sensing of Environment, 2025)

Unraveling the molecular transformation of textile-dyeing wastewater DOM: A key to optimizing full-scale TDWW treatment performance - Minru Liu; Xiaojun Niu; Zhenrong Lin; Xuechang Ren; Kejing Fang; Zhihua Tang; Qizhe Fan; Kai Li (Journal of Water Process Engineering, 2025)

Research on combustion characteristics of new high energy composite materials − using tungsten powder as fuel and DAP-4 as oxidizer - Guangwei Xiao; Erhai An; Hua Fang; Xueli Zhang; Yingxin Tan; Lin Li; Peng Deng; Zhuoxin Fei; Xiong Cao (Fuel, 2025)

Differentiation of Citri Reticulatae Pericarpium varieties via HPLC fingerprinting of polysaccharides combined with machine learning - Min-yong Zhong; Meng-ning Li; Wen-shu Zou; Si-qi Hu; Jiang-nan Luo; Qing-xiang Jiang; Qiu-fang Cao; Long-fei Lin; Zhi-xin Wang; Hui Li; Wen-wen Deng (Food Chemistry, 2025)

Dynamics of chemical profile and microbial community in 3 consecutive years reveal Rhodococcus and Apiotrichum are potential microbes contributing to quality formation of Guang Chenpi - Fang Li; Kaiying Ge; Yi Lu; Hui Lin; Enwei Tian; Hua Li; Zhiye Yang; Zhi Chao (Food Chemistry, 2025)

Specifically targeted antimicrobial cyclic peptide to staphylococcal protein A for the treatment of S. aureus infection - Xiao-Ling Lei; Yong Li; Xue-Ting Cheng; Jie Zhuang; Fang Zhang; Xiao-Ting Xie; Lin-Fang Tan; Jin-Xuan Fan; Yuan-Di Zhao; Chuan-Liu Wu; Kai Cheng (Chemical Engineering Journal, 2025)

Two-photon polymerization 3D printing of biomimetic microstructures for functionalizing surfaces to inhibit bacterial growth - Wentao Zhu; Fang-Yi Huo; Lei-Ming Cao; Zi-Zhan Li; Qian Zhu; Rongxiang He; Bolei Chen; Yong Liang; Bo Cai; Hong He; Lin-Lin Bu; Ligang Hu (Chemical Engineering Journal, 2025)

Bimetallic MOF-derived Co/Ni@C and MXene co-decorated cellulose-derived carbon foams for absorption-dominated electromagnetic interference shielding - Fang Ren; Lin Ma; Chunjie Li; Tong Wu; Jiale Zhang; Lu Pei; Yanling Jin; Zhenfeng Sun; Zhengzheng Guo; Ping Song; Penggang Ren (Carbohydrate Polymers, 2025)

The association between anti-inflammatory therapies and renal outcomes in patients with established cardiovascular disease or high cardiovascular risks: a meta-analysis of randomised controlled trials - Wenfeng Yang; Zonglin Li; Chu Lin; Xiaoling Cai; Fang Lv; Wenjia Yang; Linong Ji (Inflammopharmacology, 2025)

A feasibility study on cortisol and cortisone as biomarkers for psychological stress in wastewater-based epidemiology - Xue-Ting Shao; Yan-Song Wang; Zhen-Fang Gong; Yan-Ying Li; Jian-Guo Lin; De-Gao Wang (Water Research, 2025)

Deciphering the microbiome, lipopolysaccharides, and metabolome interplay: Unveiling putrescine's mechanism for enhancing sperm quality in heat-stressed boars - Chenglong Yu; Hao Li; Lun Hua; Lianqiang Che; Bin Feng; Zhengfeng Fang; Shengyu Xu; Yong Zhuo; Jian Li; De Wu; Junjie Zhang; Yan Lin (Theriogenology, 2025)

Flow analysis and fate of mercury in Chinese polyvinyl chloride production - Dandan Liu; Gang Fang; Yuchen Lin; Fan Wang; Zixiu Li; Chunge Dang (Process Safety and Environmental Protection, 2025)

Structural controls on the magma emplacement and distribution of sulfide orebodies in the Kalatongke Cu-Ni sulfide district, NW China - Xue-Hai Wang; Ke-Zhang Qin; Xing-Wang Xu; Dong-Mei Tang; Ya-Jing Mao; Lei Zhang; Min-Qiang Zhang; Fang-Lin Yuan; Yi Li (Journal of Asian Earth Sciences, 2025)

The discrepancy in amino acids within high-temperature Daqu: A novel metabolic marker for the quality evaluation of Daqu - Shuang Xing; Gailing Shi; Jun Lu; Chao Fang; Changwen Li; Shuai Yuan; Feng Shi; Liangcai Lin; Cuiying Zhang (Food Chemistry, 2025)

Catalyst pre-diffusion: An efficient strategy for the construction of COF nanofiltration membranes - Lin Yu; Aida Aibulatova; Zhen-Liang Xu; Li Li; Changqing Hao; Rui Jia; Yin-Xin Fang; Yan Zheng; Yong-Jian Tang (Desalination, 2025)

Sexual dimorphism in zebrafish aggression and metabolism under acute ammonia stress - Fang Zhi Chua; Li-Yih Lin; Yung-Che Tseng; Ming-Yi Chou (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Horizontally oriented 2D skin structures on fiber interface for long-life flexible energy storage devices - Guangyu Fang; Xiaorui Ma; Rong Hu; Jiao Dai; Haoran Tian; Lin Li; Weilin Xu; Yonggang Yao; Jun Wan (Chemical Engineering Journal, 2025)

Dynamic redox evolution in the middle-late Mesoproterozoic oceans - Wei Wei; Huajian Wang; Shuichang Zhang; Lin-Hui Dong; Dongdong Li; Fang Huang (Chemical Geology, 2025)

Association between sleep quality and serum biomarkers among long-term hot spring bathers: a cross-sectional study - Fen Yang; Yue Zou; Ying-ying Zhang; Hong-xia Li; Yi-hang Xu; Bao-chao Zhang; Lin-xuan Liao; Meng-xi Cao; Rui-xue Wang; Yuan Yuan; Yun Zhou; Da-yong Zeng; et al. (International Journal of Biometeorology, 2025)

Rhizosphere microecological mechanism of carbon sequestration and its emission mitigation in rice ratooning - Jinying Li; Bin Qin; Chaojie Lan; Hailong Xu; Jingnan Zou; Bianhong Zhang; Changxun Fang; Zhixing Zhang; Hongfei Chen; Wenxiong Lin (Agriculture, Ecosystems & Environment, 2025)

Multi-omics analysis reveals the potential mechanisms underlying long-term exercise-induced enhancement of learning and memory in male mice - Qiu-Xia Xiao; Hao-Yue Qin; Jun-Jie Chen; Chang-Le Fang; Qiu-Lin Wang; Qi-Jun Li; Shuai-Yu Zhu; Liu-Lin Xiong (Biogerontology, 2025)

Cavity as radio telescope for galactic dark photon - Yanjie Zeng; Yuxin Liu; Chunlong Li; Yuxiang Liu; Bo Wang; Zhenxing Tang; Yuting Yang; Liwen Feng; Peng Sha; Zhenghui Mi; Weimin Pan; Tianzong Zhang; et al. (Science Bulletin, 2025)

The allelic mutation of NBS-LRR gene causes premature senescence in wheat - Lin Qiu; Rongmin Fang; Yong Jia; Hongchun Xiong; Yongdun Xie; Linshu Zhao; Jiayu GU; Shirong Zhao; Yuping Ding; Chengdao LI; Huijun Guo; Luxiang Liu (Plant Science, 2025)

Long-term effectiveness of heavy metal(loid) stabilization: Development of an assessing method - Yanqing Liu; Zewen Wang; Xiao Tan; Deyi Hou; Liping Fang; Aijun Lin; Fangbai Li; Guilan Duan (Environmental Pollution, 2025)

Nonlinear flutter critical state prediction for a bridge girder based on instantaneous power balance principle - Yue Cheng; Genshen Fang; Wei Cui; Yongle Li; Lin Zhao (Engineering Structures, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Developing multifunctional luminophore of deferasirox molecule with excitation-sensitive mechanofluorochromic properties - Yanan Wang; Yayun Wang; Lin Wei; Aisen Li; Yuanyuan Fang; Lei Li; Qian Li; Kai Wang (Chemical Engineering Journal, 2025)

Synthesis and antitumor activity of ultra-low molecular weight hyaluronic acid-decorated camptothecin conjugates - Changsheng Chen; Henan Zhang; Jingjun Han; Lin Yang; Shuang Li; Qingwen Jia; Junqiang Fang; Peixue Ling; Shuaishuai Wang (Carbohydrate Polymers, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

A new diterpenoid alkaloid from the Aconitum scaposum - Cheng-En Fu; Gui-Fang Li; Guo-Qing Sun; Shuai Huang; Lin Chen; Xian-Li Zhou (Phytochemistry Letters, 2025)

A coupled optical–radiometric modeling approach to removing reflection noise in TLS data of urban areas - Li Fang; Tianyu Li; Yanghong Lin; Shudong Zhou; Wei Yao (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Half-day (daytime and nighttime) precipitation extremes in China: Changes and attribution from 1981 to 2022 - Jiahao Han; Shibo Fang; Xiaomao Lin; Zhanhao Zhang; Man Li; Yanru Yu; Wen Zhuo; Xinyu Wang (Global and Planetary Change, 2025)

American ginseng fruit: Antioxidant capacity, bioactive components, and biosynthesis mechanism during development - Yujuan Zhang; Lijuan Hou; Jing Hu; Xianchang Wang; Shujing Guo; Hongqing Xie; Yun Zhou; Wen Ai; Lin Li; Xin Wang; Li Ren; Fangzhou Zhao; et al. (Food Research International, 2025)

Carboxymethyl cellulose-induced Cryptococcus laurentii improves disease resistance and regulates phenylpropane and reactive oxygen metabolism in grapefruit - Le Yang; Diantong Ma; Fang Wang; Li Liu; Lin Chen; Xiahong He; Junrong Tang; Jia Deng (Food Chemistry, 2025)

Effects of decapitation on yield-related traits of total node number per plant in soybean - Ran Fang; Yichun Wu; Xin Huang; Zhihong Hou; Jialin Zhang; Lingshuang Wang; Yanan Wang; Yaru Li; Liyu Chen; Hui Yang; Lin Yue; Haiping Du; et al. (Field Crops Research, 2025)

Reproductive toxicity and molecular mechanisms of benzo[a]pyrene exposure on ovary, testis, and brood pouch of sex-role-reversed seahorses (Hippocampus erectus) - Yuanyuan Xue; Fang Wang; Xiaolei Su; Mingzhu Li; Hansheng Yan; Shiyi Zheng; Yicong Ma; Jie Dong; Yali Liu; Qiang Lin; Kai Wang (Environmental Pollution, 2025)

Corrigendum to “Chemically programmed nanozyme with microenvironment remodeling for combinatorial treatment of osteoarthritis” [Chem. Eng. J. 485 (2024) 149897] - Jiang Guo; Canfeng Li; Jianjing Lin; Jiajin Fang; Yi Sun; Peng Zhang; Shun Li; Wenqiang Li; Xintao Zhang (Chemical Engineering Journal, 2025)

Metabolic outcomes of Cordyceps fungus and Goji plant polysaccharides during in vitro human fecal fermentation - Fang Ting Gu; Jun Hui Li; Zi Chen Zhao; Yan Yu Zhu; Lin Xi Huang; Jian Yong Wu (Carbohydrate Polymers, 2025)

Nicotinamide riboside restores nicotinamide adenine dinucleotide levels and alleviates brain injury by inhibiting oxidative stress and neuroinflammation in a mouse model of intracerebral hemorrhage - Jing She; Hua Zhang; Hui Xu; Yan-Yan Li; Jun-Chao Wu; Rong Han; Fang Lin; Yan Wang; Rui Sheng; Jin-hua Gu; Zheng-Hong Qin (Molecular Neurobiology, 2025)
Hemorrhagic stroke is a global health problem owing to its high morbidity and mortality rates. Nicotinamide riboside is an important precursor of nicotinamide adenine dinucleotide characterized by a high bioavailability, safety profile, and robust effects on many cellular signaling processes. This study aimed to investigate the protective effects of nicotinamide riboside against collagenase-induced hemorrhagic stroke and its underlying mechanisms of action. An intracerebral hemorrhage model was constructed by stereotactically injecting collagenase into the right striatum of adult male Institute for Cancer Research mice. After 30 minutes, nicotinamide riboside was administered via the tail vein. The mice were sacrificed at different time points for assessments. Nicotinamide riboside reduced collagenase-induced hemorrhagic area, significantly reduced cerebral water content and histopathological damage, promoted neurological function recovery, and suppressed reactive oxygen species production and neuroinflammation. Nicotinamide riboside exerts neuroprotective effects against collagenase-induced intracerebral hemorrhage by inhibiting neuroinflammation and oxidative stress.

Water Quality, Influential Factors, and Management Strategies from 2016 to 2020 in the Yangtze River Economic Belt, China - Lanyu Lin; Congrong Guo; Yanan Chen; Lihuan He; Luyu Yan; Dekun Fang; Guangwen Ma; Fengying Zhang; Mingsheng Li (Chinese Geographical Science, 2025)

Impacts of Spartina alterniflora invasion on soil carbon components of particulate and mineral-associated organic matter and soil organic matter mineralization in estuarine wetlands - Lin Wang; Yuan Li; Jie Hei; Weiqi Wang; Jordi Sardans; Zhihao Zhang; Fanjiang Zeng; Maoquan Ge; Yiyang Liao; Yunying Fang; Tony Vancov; Jiawei Gan; et al. (Applied Soil Ecology, 2025)

Dynamics and resilience of earthworm fecal microbiomes under distinct feeding regimes - Ziyan Pan; Petr Heděnec; Qiang Lin; Lingjuan Li; Amirah Alias; Fang Deng; Jan Frouz (Applied Soil Ecology, 2025)

The influence of atmospheric turbulence-induced optical intensity scintillation on the accuracy of satellite-to-ground laser one-way timing - Zhiqian Yin; Xin Zhou; Lin Lu; Chuanbo Zhang; Peng Xiang; Weiheng Dai; Yuliang Chen; Tao Fang; Zizhuo Li; Zhuoying Wang; Jiaqiang Nie; Xiangfei Chen (Advances in Space Research, 2025)

Cadmium translocation combined with metabolomics analysis revealed potential mechanisms of MT@MSN-CS and GSH@MSN-CS in reducing cadmium accumulation in rice (Oryza sativa L.) grains - Wen-Ze Fang; Jun-Qiao Chen; Jing-Dong Mao; Bao-Feng Zhang; Li-Ping Lou; Qi Lin (Environmental Science and Pollution Research, 2025)

Magnetic Co/Fe bimetallic confined nitrogen dopped porous carbon to activate peroxymonosulfate for efficient degradation of mycotoxins: Radical and non-radical pathways - Yudan Wang; Yu Li; Wenlei Zhai; Lin Fang; Meng Wang (Journal of Water Process Engineering, 2025)

Dissolved oxygen activated by single-atom-state iron coupled with sodium dithionite for norfloxacin degradation: Efficiency and mechanism - Wei Song; Sen Xu; Caixia Fu; Ruiyi Huang; Hongze Fang; Li Li; Dachao Lin; Yuning Fang; Xing Du; Zhihong Wang (Journal of Cleaner Production, 2025)

Enhanced rock weathering boosts ecosystem multifunctionality via improving microbial networks complexity in a tropical forest plantation - Xing Wang; Guochen Li; Arshad Ali; Camelia Algora; Manuel Delgado-Baquerizo; Daniel S. Goll; Sara Vicca; Tongtong Xu; Boyuan Bi; Qiong Chen; Luxiang Lin; Yunting Fang; et al. (Journal of Environmental Management, 2025)

Jellyfish–mimetic solar evaporator with polyelectrolyte skeleton for sustainable desalination under higher salinity - Shan Zhai; Fang Yu; Naila Arshad; Suji Huang; Junyang Tao; Changwen Li; Liangyou Lin; Jingwen Qian; Muhammad Sultan Irshad; Xianbao Wang (Desalination, 2025)

Rational design of high-entropy P2/O3 biphasic layered cathodes for enhanced sodium storage performance - Yanfen Wen; Chungang Lin; Hao Shen; Kai Fang; Fupeng Li; Chengkui Luo; Xiaolin Wang; Huilin Peng; Yu Qiao; Shuxin Zhuang; Mi Lu (Chemical Engineering Journal, 2025)

Elastomer foam templated three dimensional hybrid hydrogels for heterogeneously integrated stretchable electronics - Changqing Qin; Qian Wang; Ting Fang; Lin Wang; Cheng Yang; Yong Lin; Chong Bai; Wenqiang He; Likang Ding; Jinheng Zhang; Dongchan Li; Desheng Kong (Chemical Engineering Journal, 2025)

Surface chemistry regulation enables highly durable superhydrophobic coatings with environmental robustness and pH-triggered recoatability - Mei-Lin Guo; Fang Wang; Ren-Yi Sun; Chun-Bo Li; Jin-Le Li; Fei Song; Yu-Zhong Wang (Chemical Engineering Journal, 2025)

Excessive accumulation of auxin inhibits protocorm development during germination of Paphiopedilum spicerianum - Yefei Li; Hong Chen; Xinping Kong; Yuying Yin; Ji Li; Kunlin Wu; Songjun Zeng; Lin Fang (Plant Cell Reports, 2025)

Three-dimensional Heterogeneity and Intrinsic Plasticity of the Projection from the Cerebellar Interposed Nucleus to the Ventral Tegmental Area - Chen Wang; Si-Yu Wang; Kuang-Yi Ma; Zhao-Xiang Wang; Fang-Xiao Xu; Zhi-Ying Wu; Yan Gu; Wei Chen; Ying Shen; Li-Da Su; Lin Zhou (Neuroscience Bulletin, 2025)

CircHAT1 regulates the proliferation and phenotype switch of vascular smooth muscle cells in lower extremity arteriosclerosis obliterans through targeting SFRS1 - Xian-ying Huang; Fang-yong Fu; Kai Qian; Qiao-li Feng; Sai Cao; Wei-yu Wu; Yuan-lin Luo; Wei-jie Chen; Zhi Zhang; Shui-chuan Huang (Molecular and Cellular Biochemistry, 2025)

Enhanced spectral reconstruction of ultrafast spatiotemporal encoded 2D NMR spectroscopy - Hong Li; Yida Chen; Ze Fang; Yulan Lin; Lucio Frydman; Yu Yang; Zhong Chen (Analytica Chimica Acta, 2025)

The beneficial potential of protein hydrolysates as prebiotic for probiotics and its biological activity: a review - Ping-Ping Gao; Han-Qing Liu; Zhi-Wei Ye; Qian-Wang Zheng; Yuan Zou; Tao Wei; Li-Qiong Guo; Jun-Fang Lin (Critical Reviews in Food Science and Nutrition, 2024)

Carbonate precipitation-derived CO2 outgassing offsets the mineral weathering sink in the orogenic regime of southwestern Taiwan: Insights from triple Sr isotopes - Hou-Chun Liu; Yun-Cian Lin; Yan-Hong Chen; Meng-Xuan Li; Chen-Feng You; Kuo-Fang Huang; Wei-Jen Huang; Hung-Chun Chao (Science of The Total Environment, 2024)

Screening potential biomarkers for acute respiratory infectious diseases from antipyretics, antiviral, and antibiotics in wastewater - Xue-Ting Shao; Hao-Yang Li; Zhen-Fang Gong; Jian-Guo Lin; De-Gao Wang (Science of The Total Environment, 2024)

Characterization and ecological risks of microplastics in urban road runoff - Yinghong Lin; Yuhong Wang; Yuen-Wa Ho; James Kar-Hei Fang; Yuan Li (Science of The Total Environment, 2024)

Facile formation of van der Waals metal contact with III-nitride semiconductors - Xiyu Sun; Danhao Wang; Xiaojing Wu; Jiahao Zhang; Yangjian Lin; Dongyang Luo; Fang Li; Haochen Zhang; Wei Chen; Xin Liu; Yang Kang; Huabin Yu; et al. (Science Bulletin, 2024)

A data-driven ISM-BN model for safety analysis of inland shipping in the Pearl River Basin - Fang Li; Shengliang Lin; Heping Li; Jianchuan Yin; Dexin Li; Jinshui Zhang (Ocean Engineering, 2024)

Long-term fallowing produces specific fungal taxa associated with soil carbon storage - Fang LI; Lin CHEN; Yue LI; Yanlai HAN; Yi WANG; Peipei LI; Shuiqing ZHANG; Jiabao ZHANG (Pedosphere, 2024)

Unveiling the susceptibility mechanism of Microcystis to consecutive sub-lethal oxidative stress—Enhancing oxidation technology for cyanobacterial bloom control - Fang Bai; Jie Li; Tianli Li; Jun Sha; Jin Liu; Lin Li; Guofei Dai; Yunlu Jia; Lirong Song (Journal of Hazardous Materials, 2024)

Lactobacillus reuteri or Lactobacillus rhamnosus GG intervention facilitates gut barrier function, decreases corticosterone and ameliorates social behavior in LPS-exposed offspring - Xinyuan Wang; Riqiang Hu; Fang Lin; Ting Yang; Yiwen Lu; Zhujun Sun; Tingyu Li; Jie Chen (Food Research International, 2024)

Bifidogenic properties of polysaccharides isolated from mushroom Lentinula edodes and enhanced immunostimulatory activities through Bifidobacterial fermentation - Lin Xi Huang; Fang Ting Gu; Yan Yu Zhu; Zi Chen Zhao; Jun Hui Li; Jian Yong Wu (Food Bioscience, 2024)

Experimental evaluation of bonded/unbonded prestressed precast concrete joints under repetitive loading scenarios: Seismic performance and retrofit intervention - Hao Fang; Hai-Rong Shi; Xiu-Hang Li; Chun-Lin Wang; Bin Zeng (Engineering Structures, 2024)

Assessment of multidimensional diversity and conservation of threatened timber trees in China under climate change - Jian-Lin Hu; Xiu-Qin Ci; Xiao-Yan Zhang; Run Zhou; Jian-Hua Xiao; Zhi-Fang Liu; Can-Yu Zhang; Xuan Jin; Jie Li (Biological Conservation, 2024)

Comparative Analysis of Seven Endogenous Hormones in a Novel Dual-axillary Bud Mutant Genotype of Sugarcane - Kamal Priyananda Wickramasinghe; Jun Mao; Chao-hua Xu; Xiu-qin Lin; Xu-juan Li; Wei Qin; Hong-bo Liu; Xin-long Liu; Faisal Mehdi; Pei-fang Zhao; Xin Lu (Sugar Tech, 2024)
The sugarcane genotype YZ 07-86 is a distinct natural mutant with dual-axillary buds. Exploitation of this valuable trait in sugarcane breeding requires an understanding of the physiological mechanism of dual-axillary bud formation. This experiment determined the contents of indole-3-acetic acid (IAA), abscisic acid (ABA), gibberellins (GA 3 and GA 4 ), and three cytokinins (CKs), namely isopentenyl adenosine (iPA), zeatin riboside (ZR), and dihydrozeatin riboside (DHZR), in the shoot apical meristem tissues of YZ 07-86 and its sister line YZ 07-87, which served as the control genotype. The field experiment followed a completely randomized design with three replications for each genotype. Sampling was done at 5-day intervals, starting 106 days after planting. The ELISA technique was used to measure the contents of endogenous hormones. The study revealed that the mean contents of IAA, GA 3 , GA 4 , DHZR, and iPA were not significantly different ( P > 0.05) among the genotypes. Conversely, in YZ 07-86, the mean ZR content was significantly higher ( P < 0.05), and the mean ABA content was significantly lower than in the control genotype. Moreover, the mean content ratios of ZR/IAA, ZR/ABA, ZR/GA 3 , and ZR/GA 4 were also significantly higher in YZ 07-86. The study concludes that elevated ZR content and an increased ZR/ABA ratio directly contributes to dual-axillary bud formation in YZ 07-86, offering valuable insights for the advancement of sugarcane genotypes.

Increase of PCSK9 expression in diabetes promotes VEGFR2 ubiquitination to inhibit endothelial function and skin wound healing - Jian-Jun Gao; Fang-Yuan Wu; Yu-Jia Liu; Le Li; Yi-Jun Lin; Yue-Ting Kang; Yue-Ming Peng; Yi-Fang Liu; Chen Wang; Zhen-Sheng Ma; Yang Cao; Hong-Yu Cao; et al. (Science China Life Sciences, 2024)

Enhanced 3D dose prediction for hypofractionated SRS (gamma knife radiosurgery) in brain tumor using cascaded-deep-supervised convolutional neural network - Nan Li; Jinyuan Wang; Yanping Wang; Chunfeng Fang; Yaoying Liu; Chunsu Zhang; Dongxue Zhou; Lin Cao; Gaolong Zhang; Shouping Xu (Physical and Engineering Sciences in Medicine, 2024)

Pupil dilation and behavior as complementary measures of fear response in Mice - Jing Sun; Lin Zhu; Xiaojing Fang; Yong Tang; Yuci Xiao; Shaolei Jiang; Jianbang Lin; Yuantao Li (Cognitive Neurodynamics, 2024)

KLK7, KLK10, and KLK11 in Papillary Thyroid Cancer: Bioinformatic Analysis and Experimental Validation - Tao Ni; Ru-hua Zhao; Jing-fang Wu; Chao-you Li; Gang Xue; Xu Lin (Biochemical Genetics, 2024)

Effect of alfalfa downy mildew (Peronospora aestivalis) infection on the growth and development of Therioaphis trifolii (Homoptera: Aphidiidae) - Lin-bo Xu; Liang-bin Yu; Fang-zheng Yue; Dan-yang Wang; Wen-long Li; Ba-teer Wulan; Yan-wei Cui (Crop Protection, 2024)

Hydrology controls sulfuric acid-mediated weathering in an orogenic regime of southwestern Taiwan - Hou-Chun Liu; Meng-Xuan Li; Chen-Feng You; Yan-Hong Chen; Kuo-Fang Huang; Chuan-Hsiung Chung; Guan-Wei Lin (Science of The Total Environment, 2024)

Unveiling the common laws of extracellular polymeric substances (EPS) properties on short-chain fatty acids production from sludge by EPS disintegration pretreatment - Xi-qi Li; Zhe Yu; Zhen Lin; Ying-ke Fang; Qi Sun; Kan Chen; Ai-jie Wang; Wen-zong Liu (Science of The Total Environment, 2024)

Burden of biliary tract carcinoma in China (1990–2021): Findings from the 2021 Global Burden of Disease Study - Wei Zhang; Yi-Jun Wang; Jiang-Mei Liu; Xu-Heng Sun; Yan Jiang; Fang Shen; Li-Juan Shen; Jing Xiang; Jun-Feng Zhang; Lin-Hua Yang; Wen-Guang Wu; Tao Chen; et al. (Science Bulletin, 2024)

Synergistic management of nitrogen contamination in overflow wastewater and algal proliferation in lake receiving wastewater based on electrochemical oxidation process - Ya-Ning Wang; Ding Li; Lin Liu; Jia-Fang Xie; Zhi-Tang Lyu; Quan-Bao Zhao; Yu-Ming Zheng (Process Safety and Environmental Protection, 2024)

Global climate change promotes aboveground growth and high-latitude species distribution in medicinal plants: Insights from the genus Panax - Qi Yan; Xinke Zhang; Mingchi Li; Guoshuai Zhang; Lin-Fang Huang (Journal of Cleaner Production, 2024)

Performance of carbon felt as cathodes in magnesium corrosion method to recover phosphate from swine wastewater - Ying Xiang; Weike Lin; Jinfeng Wei; Fan Yang; Meng Guo; Can Li; Jin Li; Fang Wang (Journal of Environmental Management, 2024)

Intelligent identification of picking periods of Lu’an Guapian tea by an indicator displacement colorimetric sensor array combined with machine learning - Yao Chen; Yuan Li; Li-Lin Lin; Yue Liao; Huan Fang; Tong Wang (Food Research International, 2024)

Comprehensive evaluation of the distribution, transport and ecological risk of heavy metals in intra-urban river sediments using high-resolution techniques - Kang Liao; Weijie Li; Zhiwei Huang; Shu Lin; Lingfang Fu; Wei Liu; Huaiyang Fang; Hong Deng (Environmental Pollution, 2024)

Livestock grazing modes induced the rapid differentiation of community recruitment in alpine meadow - Hui Fang; Lingchao Meng; Zhiqiang Dang; Jingxue Zhao; Shixiong Li; Gao-Lin Wu (Ecological Engineering, 2024)

Conductive hydrogel with responsive release of Herbal-Derived carbon dots for neurovascular reconstruction in diabetic critical limb ischemia - Zhibin Zhou; Mengzhen Zhao; Huaqiang Fang; Ziyue Lin; Xinrui Zheng; Yi Zhuo; Zimeng Li; Weiming Zhou; Xiaolei Wang (Chemical Engineering Journal, 2024)

A surfactant-mediated dynamic protection strategy for 100% waterborne fabrication of durable superhydrophobic coatings - Rong-Gang Zhang; Rui Feng; Fang Wang; Hang-Lin Li; Ren-Yi Sun; Hui-Hui Gao; Chun-Bo Li; Yu-Zhong Wang; Fei Song (Chemical Engineering Journal, 2024)

Simulated human digestion and fermentation of a high-molecular weight polysaccharide from Lentinula edodes mushroom and protective effects on intestinal barrier - Jun Hui Li; Fang Ting Gu; Ye Yang; Zi Chen Zhao; Lin Xi Huang; Yan Yu Zhu; Shiguo Chen; Jian Yong Wu (Carbohydrate Polymers, 2024)

Single-atom oxide-decorated AuNPs for universal enhancement in SERS detection of pesticide residues - Qi Zhang; Binbin Chen; Qingbian Ma; Zunlong Fang; Shu Li; Xiaoyu He; Yufeng Wang; Xiaohua Qi; Qian Chen; Ting Cai; Lin Zhang; Mingqiang Zou; et al. (Analytica Chimica Acta, 2024)

Epidemiology of human metapneumovirus in Taiwan from 2013 to 2023 - Su-Lin Yang; Tai-Yuan Chiu; Kun-Lin Tsai; Chung-Hao Li; Jyh-Yuan Yang; Ming-Tsan Liu; Fang-Tzy Wu (Archives of Virology, 2024)

A preliminary study of T-2 toxin that cause liver injury in rats via the NF-kB and NLRP3-mediated pyroptosis pathway - Shicong Zheng; Haonan Li; Hexuan Dong; Fang Qi; Bing Zhang; Qian Yu; Buyi Lin; Hong Jiang; Haoyu Du; Ying Liu; Jun Yu (Toxicon, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

An innovative enhanced flotation approach of non-metallic components in waste printed circuit boards: Application of pyrolysis oil as self-generated collector - Chun-chen Nie; Qian-yun Sun; Xi-guang Li; Shuo Yang; Fei-fei Wang; Gang Hu; Si-qi Jiang; Xiang-nan Zhu; Lin Li; Xiao-fang You (Process Safety and Environmental Protection, 2024)

Organic-inorganic fertilization promotes paddy soil macroaggregate organic carbon accumulation associated with key bacterial populations in subtropical China - Jinhua ZHAO; Lin CHEN; Guixiang ZHOU; Fang LI; Jiabao ZHANG; Congzhi ZHANG; Donghao MA; Biao FENG (Pedosphere, 2024)

An unusual winter bloom of dinoflagellates with notable damage to kelp cultivation around Shandong peninsula, China - Hui-Xia Geng; Fan-Zhou Kong; Jin-Xiu Wang; Qing-Chun Zhang; Fang Li; Xin Hong; Min-Jie Song; Ziru Lian; Yu-Lin Cai; Ren-Cheng Yu (Marine Environmental Research, 2024)

Effects of OSA-starch-fatty acid interactions on the structural, digestibility and release characteristics of high amylose corn starch - Mingyue Liu; Xiaoyan Wang; Yihui Li; Danni Jin; Yuling Jiang; Yong Fang; Qinlu Lin; Yongbo Ding (Food Chemistry, 2024)

Colorimetric sensing based on silver nanoparticle-functionalized copper porphyrin nanozyme for glyphosate - Li-Hong Yu; Rui Jiang; Cheng-Lin Yang; Yue-Hong Pang; Xiao-Fang Shen (Food Bioscience, 2024)

Trans-cinnamaldehyde inhibits Escherichia coli growth by regulating lipopolysaccharide accumulation - Huanling Xing; Xiaomin Liu; Jianhao Lin; Mingfei Sun; Junyi Huang; Xinghai Li; Yanqun Li; Shining Guo; Fang Zhou; Hong Wu (Food Bioscience, 2024)

Personal exposure to airborne organic pollutants and lung function changes among healthy older adults - Xiaojie Guo; Huimin Ren; Peijie Sun; Enmin Ding; Jianlong Fang; Ke Fang; Xiao Ma; Chenfeng Li; Chenlong Li; Yibo Xu; Kangning Cao; Elizabeth.Z. Lin; et al. (Environmental Research, 2024)

Digital twin-based virtual modeling of the Poyang Lake wetland landscapes - Hao Chen; Xin Xiao; Chao Chen; Min Chen; Chaoyang Li; Kai Lu; Hui Lin; Chaoyang Fang (Environmental Modelling & Software, 2024)

Machine learning for subsurface geological feature identification from seismic data: Methods, datasets, challenges, and opportunities - Lei Lin; Zhi Zhong; Chenglong Li; Andrew Gorman; Hao Wei; Yanbin Kuang; Shiqi Wen; Zhongxian Cai; Fang Hao (Earth-Science Reviews, 2024)

Mitigating thermal burden and enhancing minor phase emission energy transfer in perovskite by introducing dopamine-mediated silver nanoparticles - Zhen-Li Yan; Jhih-Yuan Chang; Chieh Tsao; Meng-Xiu Fang; Bi-Hsuan Lin; Jia-Hau Tsai; Mei-Hsin Chen; Ru-Jong Jeng; Chi-Ching Kuo (Chemical Engineering Journal, 2024)

Inflammatory microenvironment-responsive “double-insurance” nanoreactors for accurate sonodynamic-chemodynamic therapy of rheumatoid arthritis - Sui Zhou; Meng-Wen Ma; Shao-Zhe Cai; Kai-Lin He; Lin-Fang Tan; Kai Cheng; Jin-Xuan Fan; Ling-Li Dong; Bo Liu (Chemical Engineering Journal, 2024)

Removal performance of Nitrogen, sulfur and chlorine pollutants during chemical looping combustion of textile dyeing sludge using red mud as an oxygen carrier - Hongming Jiang; Yan Lin; Na Gao; Shiwen Fang; Duo Li; Zhen Huang; Hongyu Huang (Chemical Engineering Journal, 2024)

Enhancing arsenate removal through interpretable machine learning guiding the modular design of metal–organic frameworks - Zuhong Lin; Hui Cai; Hongjia Peng; Ying Fang; Pengxu Pan; Haipu Li; Ying Yang; Jingjing Yao (Chemical Engineering Journal, 2024)

The Faradaic-Induced hybrid capacitive engine enables high-performance selective defluorination via capacitive deionization - Peng Zhang; Xinyuan Qiu; Peng Lin; Chen Li; Zikang Xu; Shuai Liu; Fukuan Li; Dezhi Fang; Kexun Li; Hao Wang (Chemical Engineering Journal, 2024)

Developments in molecular docking technologies for application of polysaccharide-based materials: A review - Ruikang Lin; Jihui Zhang; Ruoxuan Xu; Chao Yuan; Li Guo; Pengfei Liu; Yishan Fang; Bo Cui (Critical Reviews in Food Science and Nutrition, 2024)

S-scheme carbon doped-TiO2/ZnIn2S4 heterojunction for enhanced photocatalytic degradation of microcystin-LR and hydrogen evolution - Xiaotong Wang; Lin Ding; Xibao Li; Zhenzhou Wang; Xiwei Xu; Fang Deng; Xubiao Luo (Chemosphere, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Saline-alkali land reclamation boosts topsoil carbon storage by preferentially accumulating plant-derived carbon - Lin Chen; Guixiang Zhou; Biao Feng; Chao Wang; Yu Luo; Fang Li; Congcong Shen; Donghao Ma; Congzhi Zhang; Jiabao Zhang (Science Bulletin, 2024)

Rutin alleviates Pb-induced oxidative stress, inflammation and cell death via activating Nrf2/ARE system in SH-SY5Y cells - Fen Li; Lin Zhang; Xingxu Zhang; Qimeng Fang; Yingshun Xu; Hui Wang (NeuroToxicology, 2024)

Paospora carinifang n. gen., n. sp. (Microsporidia: Spragueidae), a parasite of the ridgetail white prawn, Palaemon carinicauda - Yuan Wang; Ying Na; Yan-qing Huang; Jun-fang Zhou; Shou-hu Li; Quan-lin Liu; Le-tian Li; Yuan-ge Chen; Wei Tian; Hai Chi; Xin-cang Li; Wen-hong Fang (Journal of Invertebrate Pathology, 2024)

Utilizing spontaneous plants for sustainable development in residential green spaces: Insights from environmental drivers and niche analysis in Fuzhou City, China - Chengyu Ran; Junyi Pan; Yuxin Lin; Tongyan Li; Yaling Huang; Jingkai Huang; Shiyuan Fan; Wenqiang Fang; Shuang Zhao; Yuxiang Liu; Jiali Jin; Weicong Fu (Journal of Environmental Management, 2024)

Metal-organic cages for efficient capture and convenient detection of iodine from vapor and aqueous solutions - Zhi-Yong Zeng; Zhen-Chen Lou; Lianrui Hu; Weitao Dou; Xiaoli Zhao; Xiaodong Li; Junfeng Fang; Xuhong Qian; Hai-Bo Yang; Lin Xu (Chemical Engineering Journal, 2024)

Enhancing interfacial compatibility and ionic transportation kinetics in lithium-rich manganese oxide via magnetron sputtering conformal coating with amorphous LiPON - Yue Chen; Yulin Huang; Chenxi Fang; Pengcheng Wang; Houlin Cheng; Guiying Zhao; Yingbin Lin; Zhigao Huang; Jiaxin Li (Chemical Engineering Journal, 2024)

An injectable COL6-crosslinked HA-DTPH hydrogel promotes spinal tract-like structure organization during spinal cord regeneration - Jia-Hui Sun; Zhou Fang; Zhiling Li; Ting-Ting Zheng; Sheng Liu; Jixiang Zhu; Wensheng Lin; Li-Kang Zhang; Aihua Yin; Aiguo Xuan; Jian-Long Zou (Chemical Engineering Journal, 2024)

Hinokione: an abietene diterpene with pancreatic β cells regeneration and hypoglycemic activity, and other derivatives with novel structures from the woods of Agathis dammara - Zheng Wang; Zhe-Wei Yu; Yi Zhang; Wen-Hui Wang; Xin-Yi Wu; Shun-Zhi Liu; Yan-Lin Bin; Bang-Ping Cai; Shi-Yan Huang; Mei-Juan Fang; Rong Qi; Ming-Yu Li; et al. (Journal of Natural Medicines, 2024)

Community Composition and Functional Characterization of Microorganisms in Surface Sediment of the New Britain Trench - Lin Hu; Zhixuan Wang; Zixuan Wang; Li Wang; Jiasong Fang; Rulong Liu (Current Microbiology, 2024)

Signal Transduction Associated with Mn-induced Neurological Dysfunction - Xiao-wei Zheng; Yuan-yuan Fang; Jun-jie Lin; Jing-jing Luo; Shao-jun Li; Michael Aschner; Yue-ming Jiang (Biological Trace Element Research, 2024)

Harmful Cyanobacterial Bloom Control with Hydrogen Peroxide: Mechanism, Affecting Factors, Development, and Prospects - Yue Chen; Fakhar Zaman; Yunlu Jia; Yingzi Huang; Tianli Li; Fang Bai; Lin Li; Lirong Song; Jie Li (Current Pollution Reports, 2024)

Hipposponols A and B, two new 9, 11-secosterols from the marine sponge Hippospongia lachne de Laubenfels - Ya-Fang Ding; Li-Yun Liu; Jie Tang; Dong-Xue Fan; Yuan-Yuan Ji; Hou-Wen Lin; Jie Wang; Li-Li Hong (Natural Product Research, 2024)

Size-dependent deleterious effects of nano- and microplastics on sperm motility - Ziyi Lin; Zijie Li; Shuqin Ji; Hoi Shing Lo; Baki Billah; Ayesha Sharmin; Xiaofang Han; Wing-yee Lui; William Ka Fai Tse; James Kar-Hei Fang; Chunqiu Zhang; Xuejun Shang; et al. (Toxicology, 2024)

Spatio-temporal patterns and population exposure risks of urban heat island in megacity Shanghai, China - Dan Liu; Rui Zhou; Qun Ma; Tianxing He; Xuening Fang; Lishan Xiao; Yina Hu; Jie Li; Lin Shao; Jun Gao (Sustainable Cities and Society, 2024)

Core microbial taxonomies that maintain high organic carbon content in upland soil - Fang Li; Lin Chen; Zhongjun Jia; Jiabao Zhang; Zhanhui Zhao; Yanlai Han; Yi Wang (Science of The Total Environment, 2024)

Three new chemical constituents of Senecio raphanifolius - Shu-Wen Huang; Huan He; Zhi-Qiang Li; Yu-Wei Wang; Yuan-Ying Fang; Yu-Lin Feng; Zhi-Feng Li; Qi Wang (Phytochemistry Letters, 2024)

Clean and efficient process for the recycling of all components from waste printed circuit boards: Pre-treatment, bio-metallurgy, and deep utilization - Chun-chen Nie; Xi-guang Li; Qian-yun Sun; Qiang Gao; Xiang-nan Zhu; Xian-jun Lyu; Lin Li; Xiao-fang You (Journal of Cleaner Production, 2024)

The mitigation of citric acid on cadmium toxicity in Iris tectorum and its effects on the composition of cell walls - Xiao-Fang Yu; Zhi-Wen Wang; Feng-Lian Chen; Mao-Lin Chen; Xin-Yu Zhang; Jun-Rui Zhang; Wen-Yu Ji; Xue Xiao; Li-Juan Yang; Ting Lei; Xi Li; Ming-Yan Jiang (International Biodeterioration & Biodegradation, 2024)

Advancing gelatin/cinnamaldehyde O/W emulsions electrospinability: Role of soybean lecithin in core-shell nanofiber fabrication - Lin Lin; Houzhi Fang; Changzhu Li; Jinming Dai; Metab Alharbi; Haiying Cui (Food Chemistry, 2024)

Potential of Cordyceps militaris protein hydrolysates as prebiotic and thermo-protectants of Lactobacillus fermentum J26 - Ping-Ping Gao; Han-Qing Liu; Qian-Wang Zheng; Yuan Zou; Zhi-Wei Ye; Tao Wei; Li-Qiong Guo; Jun-Fang Lin (Food Bioscience, 2024)

Stabilizing Cu0/Cu2+ interface by hydroxy-rich amorphous SiO2 for enhanced electrocatalytic CO2 reduction to ethylene - Jie Zhu; Sifan Wang; Jiaji Zhang; Zhecheng Fang; Weitao Ji; Gaobo Lin; Lei Guo; Bolong Li; Jianghao Wang; Jie Fu (Chemical Engineering Journal, 2024)

Electrothermal-assisted all-weather solar steam generator based on hydrogel implantation strategy - Hao Fang; Jialiang Ma; Jing Lin; Juan Du; Shikuo Li; Hui Zhang; Fangzhi Huang (Chemical Engineering Journal, 2024)

Alleviating Pentatrichomonas hominis-induced damage in IPEC-J2 cells: the beneficial influence of porcine-derived lactobacilli - Yibin Zhu; Haiming Cai; Zhuanqiang Yan; Hanqin Shen; Siyun Fang; Dingai Wang; Shenquan Liao; Nanshan Qi; Minna Lv; Xuhui Lin; Junjing Hu; Yongle Song; et al. (Veterinary Research Communications, 2024)

Enhanced silicate weathering accelerates forest carbon sequestration by stimulating the soil mineral carbon pump - Tongtong Xu; Zuoqiang Yuan; Sara Vicca; Daniel S. Goll; Guochen Li; Luxiang Lin; Hui Chen; Boyuan Bi; Qiong Chen; Chenlu Li; Xing Wang; Chao Wang; et al. (Global Change Biology, 2024)
Enhanced silicate rock weathering (ERW) is an emerging strategy for carbon dioxide removal (CDR) from the atmosphere to mitigate anthropogenic climate change. ERW aims at promoting soil inorganic carbon sequestration by accelerating geochemical weathering processes. Theoretically, ERW may also impact soil organic carbon (SOC), the largest carbon pool in terrestrial ecosystems, but experimental evidence for this is largely lacking. Here, we conducted a 2‐year field experiment in tropical rubber plantations in the southeast of China to evaluate the effects of wollastonite powder additions (0, 0.25, and 0.5 kg m −2 ) on both soil organic and inorganic carbon at 0–10 cm depth. We found that ERW significantly increased the concentration of SOC and HCO 3 − , but the increases in SOC were four and eight times higher than that of HCO 3 − with low‐ and high‐level wollastonite applications. ERW had positive effects on the accrual of organic carbon in mineral‐associated organic matter (MAOM) and macroaggregate fractions, but not on particulate organic matter. Path analysis suggested that ERW increased MAOM mainly by increasing the release of Ca, Si, and Fe, and to a lesser extent by stimulating root growth and microbial‐derived carbon inputs. Our study indicates that ERW with wollastonite can promote SOC sequestration in stable MOAM in surface soils through both the soil mineral carbon pump and microbial carbon pump. These effects may have been larger than the inorganic CDR during our experiment. We argue it is essential to account for the responses of SOC in the assessments of CDR by ERW.

A new phenylpropanoic acid congener from Zanthoxylum nitidum - Feng Qin; Li Luo; Yao Chen; Gang Wei; Chun-Ce Wei; Xiao-Hua Yang; Yi-Lin Fang; Heng-Shan Wang (Natural Product Research, 2024)

Resveratrol in disease prevention and health promotion: A role of the gut microbiome - Xuexiang Chen; Jing Zhang; Ni Yin; Prachi Wele; Fang Li; Soham Dave; Juanying Lin; Hang Xiao; Xian Wu (Critical Reviews in Food Science and Nutrition, 2024)

Phylogeny and genetic diversity of Echinometra sea urchin in Taiwan - Mei-Fang Lin; Ming-Che Yang; Yi-Yuan Lin; Sheng-Chi Chung; Li-Lian Liu (Marine Biology Research, 2024)

Functional identification of specialized diterpene synthases from Chamaecyparis obtusa and C. obtusa var. formosana to illustrate the putative evolution of diterpene synthases in Cupressaceae - Tsai-Jung Wu; Chi-Chun Lin; Li-Ting Ma; Chih-Kai Yang; Chen-Lung Ho; Sheng-Yang Wang; Fang-Hua Chu (Plant Science, 2024)

Litoamentenes A–K, eleven undescribed cembranoids with cytotoxicity from the South China Sea soft coral Litophyton amentaceum - Yuan Zong; Jun-Jie Yang; Kai Li; Yan-Fang Pei; Hui-Yue Hou; Yue Zhang; Ci-Li Wang; Ping-Lin Li (Phytochemistry, 2024)

Phellintremulins A-C, antinociceptive sesquiterpenoids from the medicinal fungus Phellinus tremulae - Chun Tian; Li-Tang Sun; Tian Jin; Lin-Lin Yuan; Wei-Fang Xu; Hui-Xiang Yang; Tao Feng; Ji-Kai Liu (Phytochemistry, 2024)

Corrosion performance of A3 carbon steel in 30wt.% MEA and AMP-MEA blends for post-combustion carbon capture: Effect and mechanism of corrosion inhibitors - Yuwei Wang; Mengxiang Fang; Jun Gao; Chao Li; Yan Huang; Lin Yang; Shuifei Li; Ximing Hu; Tao Wang (International Journal of Greenhouse Gas Control, 2024)

Heterogenetic mechanism in high-temperature Daqu fermentation by traditional craft and mechanical craft: From microbial assembly patterns to metabolism phenotypes - Gailing Shi; Chao Fang; Shuang Xing; Ying Guo; Xin Li; Xiao Han; Liangcai Lin; Cuiying Zhang (Food Research International, 2024)

Endowing turbostratically porous carbon with rich edge nitrogen active sites for efficient capacitive removal of phosphate - Peng Zhang; Fukuan Li; Peng Lin; Dezhi Fang; Bowen Li; Xueli Zhang; Cuicui Lv; Kexun Li; Hao Wang (Desalination, 2024)

Insights into nitrogen-doped BiOBr with oxygen vacancy and carbon quantum dots photocatalysts for the degradation of sulfonamide antibiotics: Actions to promote exciton dissociation and carrier migration - Zhenchao Li; Chenghui Wen; Daguang Li; Zheng Fang; Zili Lin; Dezhu Liu; Yishun Wang; Xiaoyu Zhang; Ping Chen; Wenying Lv; Guoguang Liu (Chemical Engineering Journal, 2024)

Tuning multiple enzyme-like activities by metal doping for identification and quantitation of antioxidants in cosmetics - Sheng-Tao Wu; Hui-Qi Su; Kai-Lin Shen; Ying Li; Yi Ge; Xiu-Fang Cheng; Chang-Ming Nie; Cong-Hui Wang; Ying-Wu Lin (Chemical Engineering Journal, 2024)

Characterization of a pangolin SARS-CoV-2-related virus isolate that uses the human ACE2 receptor - Luo-Yuan Xia; Xue-Feng Wang; Xiao-Ming Cui; Yi-Ming Zhang; Zhen-Fei Wang; En-Tao Li; Chang-Fa Fan; Ke Song; Yuan-Guo Li; Run-Ze Ye; Fang-Xu Li; Dai-Yun Zhu; et al. (Science China Life Sciences, 2024)

Loss-of-function mutation in DDX53 associated with hereditary spastic paraplegia-like disorder - Xiangshu Yuan; Ya Wang; Xiyuan Li; Sheng Zhong; Danyi Zhou; Xianlong Lin; Hezhi Fang; Yanling Yang; Maofeng Wang (Journal of Molecular Medicine, 2024)

Effects of luteolin supplementation on growth, histology, antioxidant capacity, non−specific immunity and intestinal microbiota of the red swamp crayfish (Procambarus clarkii) - Yanbin Lin; Shengxuan Li; Yulong Li; Liu Fang; Heng Zhang; Qian Wang; Guoliang Ruan (Animal Feed Science and Technology, 2024)

Microplastics from face mask impairs sperm motility - Ziyi Lin; Zijie Li; Shuqin Ji; Hoi Shing Lo; Baki Billah; Ayesha Sharmin; Wing-yee Lui; William Ka Fai Tse; James Kar-Hei Fang; Keng Po Lai; Lei Li (Marine Pollution Bulletin, 2024)

Effects of different precipitation on the runoff-lake library carbon cycle process in the Three Gorges reservoir - Yixuan Li; Kaikai Deng; Zhe Li; Guijiao Lin; Bin Chen; Fang Fang; Jinsong Guo (Journal of Cleaner Production, 2024)

Salinity influence on adsorption of lipid molecules in clay minerals: Results from experiments and calculations - Xiao Gao; Zuozhen Han; Gang Zhou; Lin Li; Xiaowei Lyu; Yanyang Zhao; Wenjie Chen; Zhenhua Qi; Fang Liu; Qingqiang Meng; Michael Steiner; Chao Han (Journal of Environmental Chemical Engineering, 2024)

Noncovalent hybridization of Fe single-atom with biochar for highly efficient peroxymonosulfate activation: Built-in electric field-driven radical and non-radical processes - Shu Fang; Yiyang He; Xiao Cao; Yaru Li; Lin Gu; Wei Mao; Boyang Wang; Hanlin Zhang (Journal of Environmental Chemical Engineering, 2024)

S-scheme heterojunction of crystalline carbon nitride nanosheets and ultrafine WO3 nanoparticles for photocatalytic CO2 reduction - Gongjie Chen; Ziruo Zhou; Bifang Li; Xiahui Lin; Can Yang; Yuanxing Fang; Wei Lin; Yidong Hou; Guigang Zhang; Sibo Wang (Journal of Environmental Sciences, 2024)

Effects of rice bran rancidity on the interfacial adsorption properties of rice bran protein fibril aggregates and stability of high internal phase Pickering emulsions - Mengmeng Zhao; Fang Li; Helin Li; Qinlu Lin; Xiaoling Zhou; Xiaojuan Wu; Wei Wu (Food Chemistry, 2024)

Interfacial competing interaction eliminates voids in the buried interface for efficient and stable perovskite solar modules on bare NiOX - Sibo Li; Xin Wang; Jun Fang; Dongxu Lin; Nuanshan Huang; Daozeng Wang; Sisi He; Longbin Qiu (Chemical Engineering Journal, 2024)

Enzymatic modular synthesis of asymmetrically branched human milk oligosaccharides - Yinshuang Li; Yi Li; Yuxi Guo; Congcong Chen; Lin Yang; Qian Jiang; Peixue Ling; Shuaishuai Wang; Lei Li; Junqiang Fang (Carbohydrate Polymers, 2024)

A compound enzyme as an additive to a continuous anaerobic dynamic membrane bioreactor for enhanced lignocellulose removal from codigestion: Performance, membrane characteristics and microorganisms - Bao-Shan Xing; Xiang-Lin Chang; Yi Zhang; Sifan Cao; Xi-Fang Tang; Yong-Chen Han; Yu-You Li; Xiaochang C. Wang; Rong Chen (Bioresource Technology, 2024)

Chemical constituents of the deep-sea-derived fungus Trichoderma simmonsii ZEN3 and their chemotaxonomic significance - Li-Fang Liu; Yuan Wang; Rong Chao; Lin Xu; Zheng-Biao Zou; Kai Zhang; Ming-Min Xie; Xian-Qiang Chen; Cheng-Hai Gao; Xian-Wen Yang (Biochemical Systematics and Ecology, 2024)

Metagenomic Next-Generation Sequencing Contributes to the Early Diagnosis of Mixed Infections in Central Nervous System - Li Lin; Junyue Fang; Jiahao Li; Ying Tang; Tengteng Xin; Nengtai Ouyang; Wenying Cai; Lisi Xie; Sha Lu; Junmin Zhang (Mycopathologia, 2024)

Regulatory effect of Yinchenhao decoction on bile acid metabolism to improve the inflammatory microenvironment of hepatocellular carcinoma in mice - Jian Shi; Lin Zhu; Bang-Yi Tang; Wan-Qing Yang; Sheng-Yan Xi; Chen-Long Zhang; Peng-Fei Li; Yu-Jie Wang; Kai-Hang Guo; Jing-Ru Huang; Chen-Rui Huang; Zhou-Xin Yu; et al. (Journal of Natural Medicines, 2024)

An Automatic Approach of Video-Based Landmark Detection and Movement Analysis for Assessing Symptoms of Bradykinesia in Parkinson’s Disease - Ching-Fang Chien; Chen-Sen Ouyang; Yi-Hung Chiu; Lung-Chang Lin; Rei-Cheng Yang; Yang-Pei Chang; San-Yuan Wang; Li-Min Liou (Journal of Medical and Biological Engineering, 2024)

Algae-bacteria consortia promotes the cell growth of marine microalgae Phaeodactylum tricornutum and Chrysotila roscoffensis - Jiaqi Fang; Yan Sun; Zhujun Zhu; Jian Li; Pengfei Cheng; Spiros N. Agathos; Yuanyuan Fu; Lin Zhang; Chengxu Zhou; Jichang Han (Algal Research, 2024)

Toward intelligent food packaging of biosensor and film substrate for monitoring foodborne microorganisms: A review of recent advancements - Feng Bao; Zhao Liang; Jing Deng; Qinlu Lin; Wen Li; Qiong Peng; Yong Fang (Critical Reviews in Food Science and Nutrition, 2024)

Intelligent agent for hyperspectral image classification with noisy labels: a deep reinforcement learning framework - Chunhua Fang; Guifeng Zhang; Jia Li; Xinping Li; Tengfei Chen; Lin Zhao (International Journal of Remote Sensing, 2024)

Insights into growth stages and genotypes in airborne Pb accumulation in Oryza sativa L. grains: Utilizing isotope fingerprinting alongside a model study - Qi Lin; Ming-Jin Zhuang; Wei Dai; Jing Fang; Bao-Feng Zhang; Jing-Dong Mao; Li-Ping Lou (Chemosphere, 2024)

Atmospheric CO2 in the megacity Hangzhou, China: Urban-suburban differences, sources and impact factors - Yuanyuan Chen; Yanran Lu; Bing Qi; Qianli Ma; Kunpeng Zang; Yi Lin; Shuo Liu; Fengmei Pan; Shan Li; Peng Guo; Lihan Chen; Wengang Lan; et al. (Science of The Total Environment, 2024)

Zeolite prepared from high-calcium ladle furnace slag and fly ash for Pb2+ removal - Wenqing Ma; Yuanrong Yi; Minghang Fang; Yue Lin; Chunhui Li; Jie Li; Wei Liu (Journal of Water Process Engineering, 2024)

Micro-structure change and crystal-structure modulated of oxygen carriers for chemical looping: Controlling local chemical environment of lattice oxygen - Da Song; Tao Long; Cuiqin Li; Yang Li; Mingyang Fan; Yonghao Lu; Yuchao Zhou; Haitao Chen; Yan Lin; Zhen Huang; Fang He (Fuel, 2024)

DEHP induces apoptosis and autophagy of the thyroid via Rap1 signaling pathway: In vivo and in vitro study - Xu Li; Honghao Qian; Hui Ye; Haotang Zhao; Jianwei Cui; Xiaoqi Fang; Zhili Ge; Jingjing Shi; Wen Qi; Lin Ye (Food and Chemical Toxicology, 2024)

Regulation of photoassimilate transportation and nitrogen uptake to decrease greenhouse gas emissions in ratooning rice with higher economic return by optimized nitrogen supplies - Jingnan Zou; Hailong Xu; Chaojie Lan; Bin Qin; Jinying Li; Witness Joseph Nyimbo; Hongmei Lin; Ziqin Pang; Nyumah Fallah; Chunlin Guo; Changxun Fang; Zhixing Zhang; et al. (Field Crops Research, 2024)

Geographic distribution of bacterial communities of inland waters in China - Binhao Wang; Kaiming Hu; Chuqiao Li; Yinan Zhang; Chao Hu; Zhiquan Liu; Jiafeng Ding; Lin Chen; Wei Zhang; Jing Fang; Hangjun Zhang (Environmental Research, 2024)

A new substrate equalization method for optimizing the influent conditions and fluid flow patterns of a multifed upflow anaerobic sludge blanket reactor with mature anammox granules - Bao-Shan Xing; Xi-Fang Tang; Ling-Hu Li; Yu-Lin Fu; Jia-Yi Liu; Ya-Ge Wang; Xin-Xin Sun; Yu-You Li; Rong Chen; Ren-Cun Jin (Bioresource Technology, 2024)

Enhanced rock weathering increased soil phosphorus availability and altered root phosphorus‐acquisition strategies - Boyuan Bi; Guochen Li; Daniel S. Goll; Luxiang Lin; Hui Chen; Tongtong Xu; Qiong Chen; Chenlu Li; Xing Wang; Zhanqing Hao; Yunting Fang; Zuoqiang Yuan; et al. (Global Change Biology, 2024)
Enhanced rock weathering (ERW) has been proposed as a measure to enhance the carbon (C)‐sequestration potential and fertility of soils. The effects of this practice on the soil phosphorus (P) pools and the general mechanisms affecting microbial P cycling, as well as plant P uptake are not well understood. Here, the impact of ERW on soil P availability and microbial P cycling functional groups and root P‐acquisition traits were explored through a 2‐year wollastonite field addition experiment in a tropical rubber plantation. The results show that ERW significantly increased soil microbial carbon‐use efficiency and total P concentrations and indirectly increased soil P availability by enhancing organic P mobilization and mineralization of rhizosheath carboxylates and phosphatase, respectively. Also, ERW stimulated the activities of P‐solubilizing ( gcd , ppa and ppx ) and mineralizing enzymes ( phoADN and phnAPHLFXIM ), thus contributing to the inorganic P solubilization and organic P mineralization. Accompanying the increase in soil P availability, the P‐acquisition strategy of the rubber fine roots changed from do‐it‐yourself acquisition by roots to dependence on mycorrhizal collaboration and the release of root exudates. In addition, the direct effects of ERW on root P‐acquisition traits (such as root diameter, specific root length, and mycorrhizal colonization rate) may also be related to changes in the pattern of belowground carbon investments in plants. Our study provides a new insight that ERW increases carbon‐sequestration potential and P availability in tropical forests and profoundly affects belowground plant resource‐use strategies.

Isolation and absolute configuration of alkylpyridine alkaloids from the marine sponge Hippospongia lachne - Dong-Xue Fan; Xiang-Chao Luo; Ya-Fang Ding; Li-Yun Liu; Xin Wang; Jia-Yan Pan; Yuan-Yuan Ji; Jie Wang; Cui Li; Li-Li Hong; Hou-Wen Lin (Phytochemistry, 2024)

Analysis of dissolved oxygen influencing factors and concentration prediction using input variable selection technique: A hybrid machine learning approach - Wei Liu; Shu Lin; Xiaobao Li; Wenjing Li; Hong Deng; Huaiyang Fang; Weijie Li (Journal of Environmental Management, 2024)

Temperature sensitivity of soil-borne fungal phytopathogens depends on niche breadth and land use types - Bangguo Yan; Yi Sun; Guangxiong He; Xuemei Wang; Lin Li; Xuewen Yue; Liangtao Shi; Haidong Fang (Fungal Ecology, 2024)

Microcystin-LR and polystyrene microplastics jointly lead to hepatic histopathological damage and antioxidant dysfunction in male zebrafish - Wang Lin; Fen Hu; Fang Liu; Ling Liao; Ling Ling; Li Li; Jifeng Yang; Pinhong Yang (Environmental Pollution, 2024)

Chemically programmed nanozyme with microenvironment remodeling for combinatorial treatment of osteoarthritis - Jiang Guo; Canfeng Li; Jianjing Lin; Jiajin Fang; Yi Sun; Peng Zhang; Shun Li; Wenqiang Li; Xintao Zhang (Chemical Engineering Journal, 2024)

Ammoniated straw returning: A win-win strategy for increasing crop production and soil carbon sequestration - Jinchao Li; Yue Li; Nanping Lin; Yanxin Fang; Qin’ge Dong; Tibin Zhang; Kadambot H.M. Siddique; Naijiang Wang; Hao Feng (Agriculture, Ecosystems & Environment, 2024)

Effects of lianas on forest biogeochemistry during their lives and afterlives - Gbadamassi G. O. Dossa; Hong‐Lin Li; Bo Pan; Tial C. Ling; Douglas A. Schaefer; Mareike Roeder; Denis M. Njoroge; Juan Zuo; Liang Song; Bismark Ofosu‐Bamfo; Stefan A. Schnitzer; Rhett D. Harrison; et al. (Global Change Biology, 2024)
Climate change and other anthropogenic disturbances are increasing liana abundance and biomass in many tropical and subtropical forests. While the effects of living lianas on species diversity, ecosystem carbon, and nutrient dynamics are receiving increasing attention, the role of dead lianas in forest ecosystems has been little studied and is poorly understood. Trees and lianas coexist as the major woody components of forests worldwide, but they have very different ecological strategies, with lianas relying on trees for mechanical support. Consequently, trees and lianas have evolved highly divergent stem, leaf, and root traits. Here we show that this trait divergence is likely to persist after death, into the afterlives of these organs, leading to divergent effects on forest biogeochemistry. We introduce a conceptual framework combining horizontal, vertical, and time dimensions for the effects of liana proliferation and liana tissue decomposition on ecosystem carbon and nutrient cycling. We propose a series of empirical studies comparing traits between lianas and trees to answer questions concerning the influence of trait afterlives on the decomposability of liana and tree organs. Such studies will increase our understanding of the contribution of lianas to terrestrial biogeochemical cycling, and help predict the effects of their increasing abundance.

Transforming waste brake pads from automobiles into Nano-Catalyst: Synergistic Fe-C-Cu triple sites for efficient fenton-like oxidation of organic pollutants - Fuyuan Qi; Jianfei Peng; Zilu Liang; Jiliang Guo; Jiawei Yin; Ainan Song; Zongxuan Li; Jiayuan Liu; Tiange Fang; Jinsheng Zhang; Lin Wu; Qijun Zhang; et al. (Waste Management, 2024)

Natural product-derived ferroptosis mediators - Yi-Li Chen; Lin-An Xiong; Lie-Feng Ma; Luo Fang; Zha-Jun Zhan (Phytochemistry, 2024)

Facile synthesis of hydroxylated triazine-based magnetic microporous organic network for ultrahigh adsorption of phenylurea herbicides: An experimental and density-functional theory study - Lu Liu; Lu-Qin Qiao; Feng Liu; Qian-Yun Sun; Yan-Fang Zhao; Xiao-Li Wang; Na Li; Hai-Long Jiang; Xiang-Feng Chen; Ming-Lin Wang; Yong-Ning Wu; Ru-Song Zhao (Journal of Hazardous Materials, 2024)

Co-occurrence of organophosphate esters and phosphorus fractions in river sediments: Implications for pollution prediction and environment risk assessment - Lingfang Fu; Yuxin Liu; Shu Lin; Jieer Xiao; Weijie Li; Yang Yu; Hailong Zeng; Ping Li; Huaiyang Fang (Journal of Hazardous Materials, 2024)

Characteristics and fractionations of sediment oxygen demand in a complex tidal river network area - Zhiwei Huang; Xiaochen Liu; Jing Wen; Huaiyang Fang; Shu Lin; Weijie Li; Jie Wang; Fantang Zeng; Hongwei Du; Lei Shi (Journal of Environmental Management, 2024)

Estimation on strength parameters of sediments with hydrate layered distribution based on triaxial shearing tests - Lin Dong; Nengyou Wu; Fang Liu; Zhiwen Sun; Minhui Qi; Gaowei Hu; Yanlong Li (Gas Science and Engineering, 2024)

Flutter control optimization for a 5000 m suspension bridge with active aerodynamic flaps: a CFD-enabled strategy - Zilong Wang; Lin Zhao; Yiheng Fu; Genshen Fang; Wei Cui; Ke Li; Yaojun Ge (Engineering Structures, 2024)

A top-down and in situ strategy for intrinsic acicular nanostructure enhanced ultradurable superhydrophobic and anti-icing aramid fabric - Jin-Le Li; Fang Wang; Chun-Bo Li; Ren-Yi Sun; Mei-Lin Guo; Gang Wu; Fei Song; Yu-Zhong Wang (Chemical Engineering Journal, 2024)

Defect-promoted nanoparticles−nanorod Ni−NiMoO4 heterogeneous nanostructures as efficient electrocatalysts to overall water/urea splitting in fresh/sea water - Caihong Fang; Ran Li; Xin Wang; Fei Duan; Junfeng Lin; Yunqin Hu; Zhiqing Cui (Chemical Engineering Journal, 2024)

High resolution osteoclast-targeted imaging-guided osteoporosis alleviation via persistent luminescence nanocomposite - Xiao Lin; Kewen Zhang; Yang Li; Fang Nan; Jun Li; Hui Zhang; Wei Deng; Weihang Ding; Kaixuan Li; Nur Jarhen; Yitong Zhou; Xiao Yu; et al. (Chemical Engineering Journal, 2024)

Assessment of Crop Yield in China Simulated by Thirteen Global Gridded Crop Models - Dezhen Yin; Fang Li; Yaqiong Lu; Xiaodong Zeng; Zhongda Lin; Yanqing Zhou (Advances in Atmospheric Sciences, 2024)

Virgin coconut oil: A comprehensive review of antioxidant activity and mechanisms contributed by phenolic compounds - Yu-Qing Zeng; Jin-Tao He; Bo-Yong Hu; Wen Li; Jing Deng; Qin-Lu Lin; Yong Fang (Critical Reviews in Food Science and Nutrition, 2024)

Methionine redox regulation of actin-interacting proteins primarily governs antioxidative signaling and response to the salvianolic acid B treatment in EA.hy926 cells - Ai-Cheng Wang; Xiao-Ming Qi; Qing-Fang Li; Yi-Jia Feng; Yuan-Lin Zhang; Hui-Zhi Wei; Jin-Shan Li; Yuan-Biao Qiao; Qing-Shan Li (Toxicology and Applied Pharmacology, 2024)

Efficiency and equality of the multimodal travel between public transit and bike-sharing accounting for multiscale - Zhihang Liu; Chenyu Fang; Hao Li; Jinlin Wu; Lin Zhou; Martin Werner (Sustainable Cities and Society, 2024)

Historical variability of cotton yield and response to climate and agronomic management in Xinjiang, China - Yanqing Zhou; Fang Li; Qinchuan Xin; Yaoming Li; Zhongda Lin (Science of The Total Environment, 2024)

Large-n quasi-phase-pure two-dimensional halide perovskite: A toolbox from materials to devices - Zijia Li; Yuexin Lin; Hao Gu; Nan Zhang; Bin Wang; Hairui Cai; Jinfeng Liao; Dejian Yu; Yiwang Chen; Guojia Fang; Chao Liang; Shengchun Yang; et al. (Science Bulletin, 2024)

Four pairs of neolignan enantiomers with distinctive isochroman moiety from the fruits of Crataegus pinnatifida and their protective activities against H2O2-induced SH-SY5Y cells - Peng Zhao; Shi-Fang Li; Jiao-Yang Hou; Shu-Yan Qin; Jia-Yi Li; Xiao-Fang Zhou; Xuan Liu; Jin-Le Hao; Bin Lin; Xiao-Xiao Huang; Shao-Jiang Song (Phytochemistry, 2024)

A novel index for assessing the rural population hollowing at fine spatial resolutions based on Tencent social media big data: A case study in Guangdong Province, China - Fang Wang; Shaoying Li; Lin Liu; Feng Gao; Yanfen Feng; Zilong Chen (Land Use Policy, 2024)

CO2 enrichment and excess nitrogen supply synergistically increase toxicity of marine dinoflagellate Alexandrium minutum - Fang Li; Lin Guo; Junhui Chen; Ziru Lian; Ren-Cheng Yu (Journal of Hazardous Materials, 2024)

A facile, green strategy to synthesize N/P self-doped, biomass-derived, hierarchical porous carbon from water hyacinth for efficient VOCs adsorption - Chenglong Yu; Junhui Dan; Zewei Liu; Jinliang Wang; Jiayang Wang; Hansun Fang; Fayin Lai; Danping Li; Lin Li; Fengying Li; Chunhuo Zhou; Bichun Huang (Fuel, 2024)

Water-ultrastable perovskite CsPbBr3 nanocrystals tailored by surface-confined strategy for amaranth sensing in food samples - Lei Hu; Kai-Qi Liu; Feng Li; Heng-Ye Li; Wei Wang; Hai-Lin Fang; Hang Gao; Zhong-Xia Wang (Food Chemistry, 2024)

Slow-release fertilizer deep placement increased rice yield and reduced the ecological and environmental impact in Southeast China: A life-cycle perspective - Chaojie Lan; Jingnan Zou; Jinying Li; Hailong Xu; Weiwei Lin; Peiying Weng; Changxun Fang; Zhixing Zhang; Hongfei Chen; Wenxiong Lin (Field Crops Research, 2024)

Scalable, bio-inspired and self-floating bi-layer polyurethane foam solar evaporator with excellent capillary hydrodynamic effect - Jing Lin; Mei Wu; Hao Fang; Mengyue Wu; Shikuo Li; Hui Zhang; Yu Jiang; Fangzhi Huang (Chemical Engineering Journal, 2024)

Unraveling fluorescent mechanism of biomass-sourced carbon dots based on three major components: Cellulose, lignin, and protein - Tian-xiang Li; De-fang Zhao; Lin Li; Yang Meng; Yu-hui Xie; Dong Feng; Feng Wu; Delong Xie; Yuxin Liu; Yi Mei (Bioresource Technology, 2024)

Quantifying the effects of viral load on multistate COVID-19 infection and the progression of the Alpha and Omicron VOCs: a Bayesian competing Markov exponential regression model - Yen-Po Yeh; Amy Ming-Fang Yen; Ting-Yu Lin; Chen-Yang Hsu; Sam Li-Sheng Chen; Tony Hsiu-Hsi Chen (Stochastic Environmental Research and Risk Assessment, 2024)

Hydrogeochemistry and indicators of flowback and produced water from wells that are hydraulically fractured with recycled wastewater: A case study of the Changning gas field in the Sichuan Basin - Dan Liu; Wei Xiong; Xiaowei Zhang; Wei Guo; Wanting Li; Jinliang Gao; Lixia Kang; Yuyang Liu; Zhaoyuan Shao; Lin Zhang; Cong Yu; Fengrong Liao; et al. (Applied Geochemistry, 2024)

Highly sensitive biosensor for specific miRNA detection based on cascade signal amplification and magnetic electrochemiluminescence nanoparticles - Jiawen Li; Cheng Chen; Fang Luo; Zhenyu Lin; Jian Wang; Aiwen Huang; Ying Sun; Bin Qiu (Analytica Chimica Acta, 2024)

Human milk oligosaccharides and the association with microbiota in colostrum: a pilot study - Wen Sun; Lin Tao; Chen Qian; Peipei Xue; Xiankun Tong; Li Yang; Fang Lu; Hua Wan; Yingna Tao (Archives of Microbiology, 2024)
HMOs (Human milk oligosaccharide) has an impact on maternal and infant health. Colostrum samples of 70 breastfeeding women in China were collected and recorded clinical characteristics. The major oligosaccharides and microbiota were quantitated in colostrum. The concentration of fucosylated HMOs in primipara was higher than that of multipara ( p = 0.030). The concentration of N-acetylated HMOs in vaginal delivery milk was less than that of cesarean ( p = 0.038). Non-fucosylated HMOs of breastfeeding women were less than that of breast pump ( p = 0.038). Meanwhile, the concentration of LNT was positively correlated with Lactobacillus ( r = 0.250, p = 0.037). DS-LNT was negatively correlated with Staphylococcus ( r = – 0.240, p = 0.045). There was a positive correlation of Streptococcus with LNFP II ( r = 0.314, p = 0.011) and 3-SL ( r = 0.322, p = 0.009). In addition, there was a negative correlation between 2'-FL and 3-FL ( r = – 0.465, p = 0.001). There was a positive correlation between LNT and LNnT ( r = 0.778, p = 0.001). Therefore, the concentration of HMOs is related to number of deliveries, delivery mode, lactation mode and perinatal antibiotic. The concentration of HMOs is related to Lactobacillus , Streptococcus and Streptococcus in colostrum. In addition, there are connections between different oligosaccharides in content. The study protocol was also registered in the ClinicalTrails.gov (ChiCTR2200064454) (Oct. 2022).

Positive impacts of dietary prebiotic inulin on growth performance, antioxidant capacity, immunity, and intestinal microbiota of red swamp crayfish (Procambarus clarkii) - Qian Wang; Yanbin Lin; Heng Zhang; Wenhao Fan; Shengxuan Li; Guoliang Ruan; Liu Fang (Aquaculture International, 2024)

Oncogenic and immunological roles of RACGAP1 in pan-cancer and its potential value in nasopharyngeal carcinoma - Cheng-shan Zheng; Wei-mei Huang; Hong-mei Xia; Jing-lin Mi; Yuan-qing Li; Hui-qing Liang; Li Zhou; Zhou-xue Lu; Fang Wu (Apoptosis, 2024)

The survival strategy of direct interspecies electron transfer-capable coculture under electron donor-limited environments - Guiqin Yang; Canfen Lin; Tiqun Hou; Xian Wu; Yanlun Fang; Sijie Yao; Li Zhuang; Yong Yuan (Science of The Total Environment, 2024)

A model of hybrid speciation process drawn from three new poplar species originating from distant hybridization between sections - Yu-Jie Shi; Jin-Liang Huang; Jia-Xuan Mi; Jing Li; Fan-Yu Meng; Yu Zhong; Fang He; Fei-Fei Tian; Fan Zhang; Liang-Hua Chen; Han-Bo Yang; Hong-Lin Hu; et al. (Molecular Phylogenetics and Evolution, 2024)

Garnet geochemistry reveals late-stage oxidation of tin-bearing fractionated granite - Jin-Xiang Li; Lin Ding; Noreen J. Evans; Fang Xu; Wei-Ming Fan; Li-Yun Zhang; Fu-Long Cai; Qiu-Yun Guan; Ya-Hui Yue; Jing Xie (Lithos, 2024)

Synthesis of gel crosslinked composite material from spent cathode carbon blocks and its application in modified asphalt binders - Xinyu Li; Denghui Ren; Shencheng Fan; Zibo Lin; Fanyu Meng; Haisheng Wu; Fang Lai; Jing Li (Journal of Cleaner Production, 2024)

Dissolved organic matter and Fe/Mn enhance the combination and transformation of As in Lake Chaohu Basin - Youru Yao; Kang Ma; Shiyin Li; Yong Zhang; Zhiming Zhang; Fengman Fang; Yuesheng Lin; Li Yin; Lian Sun; Chonghong Zhang (Journal of Environmental Management, 2024)

Systematic assessment of the antifungal mechanism of soil fumigant methyl isothiocyanate against Fusarium oxysporum - Daqi Zhang; Lirui Ren; Qing Wang; Wenjing Li; Zhaoxin Song; Xi Jin; Wensheng Fang; Dongdong Yan; Yuan Li; Qiuxia Wang; Lin He; Aocheng Cao (Environmental Pollution, 2024)

Boosting the charge transport and stability of metal halide perovskite with boron nitride nanosheets for X-ray detection and imaging - Fang Yao; Zhenglin Jia; Junqi Dong; Ruiming Li; Yujie Yang; Haitao Tang; Wusheng Zou; Jiangbin Zhao; Yong Liu; Zhu Wang; Gaokui He; Qianqian Lin (Chemical Engineering Journal, 2024)

The designation of intrinsic flame-retarding vinyl ester resins with high mechanical property, optical transparency and degradability - Ying-Ming Li; Shuang-Lin Hu; Hang-Ping Fang; Yao Deng; Chang-De Yang; De-Yi Wang (Chemical Engineering Journal, 2024)

Investigation and optimization of outdoor thermal comfort in elementary school campuses: Example from a humid-hot area in China - Tongye Guo; Zhaoxia Lin; Yang Zhao; Zhaosong Fang; Yini Fan; Xiang Zhang; Jiahao Yang; Yuankui Li (Building and Environment, 2024)

A colorimetric sensing platform with smartphone for organophosphorus pesticides detection based on PANI-MnO2 nanozyme - Cheng-Lin Yang; Li-Hong Yu; Yue-Hong Pang; Xiao-Fang Shen (Analytica Chimica Acta, 2024)

Response of distributions and emissions of summer biogenic sulfur in the Pacific Arctic to enhanced Pacific Water inflow - Cheng‐Xuan Li; Bao‐Dong Wang; Kan Chen; Gui‐Peng Yang; Jian‐Fang Chen; Li‐Na Lin; Zi‐Cheng Wang (Limnology and Oceanography, 2024)
The inflow of warm and nutrient‐rich Pacific Water (PW) through the Bering Strait into the Arctic Ocean is likely to have far‐reaching consequences for the ecosystem and biogenic sulfur cycle in the Earth's sensitive subarctic–arctic region of the Pacific sector, even impacting climate change under global warming scenarios. We performed a detailed biogeochemical study of summer biogenic sulfur cycling from cold (2012) to warm (2014) years in the Bering Strait and the Chukchi Sea, so as to highlight the importance of enhanced Pacific inflow in driving dimethylsulfide (DMS) variability. In the Bering Strait, the enhanced Pacific inflow led to the vertical expansion of the eastern high‐DMS regions due to the vertical extension of Alaska Coastal Water, and the horizontal expansion of the western surface high‐DMS regions due to the westward intrusion of Bering Shelf Water. The enhanced extension of PW potentially stimulated seawater warming, the northward retreat of the ice edge, and the enlargement of sea ice‐free areas in the Chukchi Sea. The northern ice melting zone at 71°N with a bloom of phytoplankton was an area of locally high dimethylsulfoniopropionate concentrations and slow DMS consumption in 2012. A hotspot for dimethylated sulfur compound concentrations and DMS sea–air flux occurred in the convergence region near 67.7°N during 2014, due to enhanced mixing caused by increased Bering Sea Water. Owing to the increased advection of PW during 2012–2014, surface DMS and its emission to the atmosphere increased sharply by threefold in the Chukchi Sea.

An insight into the health beneficial of probiotics dairy products: a critical review - JinTao He; Wen Li; Jing Deng; QinLu Lin; Jie Bai; Lin Zhang; Yong Fang (Critical Reviews in Food Science and Nutrition, 2023)

Self-assembly construction of 1D carbon nitride nanotubes and cobalt-modified for superior photocatalytic degradation of sulfonamide antibiotics - Zifeng Lin; Zhongquan Wang; Zihong Xu; Zhenjun Xiao; Zheng Fang; Jin Luo; Ping Li; Ping Chen; Wenying Lv; Guoguang Liu (Chemosphere, 2023)

Surveillance of COVID-19 and influenza A(H1N1) prevalence in China via medicine-based wastewater biomarkers - Xue-Ting Shao; Yan-Song Wang; Zhen-Fang Gong; Yan-Ying Li; Dong-Qin Tan; Jian-Guo Lin; Wei Pei; De-Gao Wang (Water Research, 2023)

Eco-friendly approach for enhancing the floatability of non-metallic components in waste printed circuit boards: Adding gutter oil during dry grinding - Chun-chen Nie; Si-qi Jiang; Xi-guang Li; Xiao-ru Wang; Zhi-hao Li; Xiang-nan Zhu; Xian-jun Lyu; Xiao-fang You; Lin Li (Waste Management, 2023)

The comparison of mortality burden between exposure to dry-cold events and wet-cold events: A nationwide study in China - Muyun Li; Wen Fang; Ruilin Meng; Jianxiong Hu; Guanhao He; Zhulin Hou; Maigeng Zhou; Chunliang Zhou; Sui Zhu; Yize Xiao; Min Yu; Biao Huang; et al. (Science of The Total Environment, 2023)

Yuexiconcha nov. gen. – A resilifer-bearing palaeotaxodont (Bivalvia, Protobranchia) from the Ordovician of Guangdong, South China - Zhi-jun Niu; Ren-jie Zhang; Paul A. Johnston; Chu-an Li; Zhi-hong Wang; Kun Hu; Fang Song; Yao-yan He; Jin-lan He; Xiao-ming Lin; Wen-qiang Yang (Geobios, 2023)

Plant flavonoids bioavailability in vivo and mechanisms of benefits on chronic kidney disease: a comprehensive review - Yang Lin; Jingyu Fang; Zhiyu Zhang; Mohamed A. Farag; Zhenhao Li; Ping Shao (Phytochemistry Reviews, 2023)

Multifunctional regulation of NADPH oxidase in growth, microsclerotia formation and virulence in Metarhizium rileyi - Liqin Fan; Bingjie Li; Jiahui Wang; Xinxin Li; Feilong Ma; Fang Du; Hongli Li; Yunlong Lin (Biotechnology Letters, 2023)

Characteristics and Geological Significance of High-precision Aeromagnetic Data in LinFen-YunCheng - Ming Wang; Jin-hong Qu; Xiao-xing Lin; Zhen-jun Liu; Fang Li (Applied Geophysics, 2023)

Traditional Chinese medicine bufalin inhibits infectious pancreatic necrosis virus genogroups I and V infection in vitro and in vivo - Jing-Zhuang Zhao; Lin-Fang Li; Li-Ming Xu; Yi-Zhi Shao; Guang-Ming Ren; Qi Liu; Tong-Yan Lu (Aquaculture, 2023)

Activation of estrogen-related receptor: An alternative mechanism of hexafluoropropylene oxide homologs estrogenic effects - Lu Chen; Xicha Lin; Sha Shi; Minjie Li; Monika Mortimer; Wendi Fang; Fangfang Li; Liang-Hong Guo (Science of The Total Environment, 2023)

The Dof transcription factor COG1 acts as a key regulator of plant biomass by promoting photosynthesis and starch accumulation - Zhuoyun Wei; Haoyong Zhang; Meng Fang; Shuyuan Lin; Mingsong Zhu; Yuxiu Li; Limin Jiang; Tianliang Cui; Yanwei Cui; Hong Kui; Liang Peng; Xiaoping Gou; et al. (Molecular Plant, 2023)

Polyphenols modulate microalgae metabolism with a particular increment in lipid accumulation - Li-Gong Zou; Dan-Lin Zheng; Yi-Tong Yao; Fu-Fang Wen; Da-Wei Li; Yu-Feng Yang; Wei-Dong Yang; Srinivasan Balamurugan; Hang Fai Kwok; Hong-Ye Li (Fuel, 2023)

Constructing year-round energy-efficient fresh air handling unit with exhaust air heat recovery using multi-condition design - Chenjiyu Liang; Xianting Li; Lin Fang; Takema Nakazawa; Toshio Tanaka (Energy and Buildings, 2023)

Dynamical Predictability of Leading Interannual Variability Modes of the Asian-Australian Monsoon in Climate Models - Lin Wang; Hong-Li Ren; Fang Zhou; Nick Dunstone; Xiangde Xu (Advances in Atmospheric Sciences, 2023)

Progress in biological activities and biosynthesis of edible fungi terpenoids - Hai-Ying Chen; Jin-Yu Lei; Shu-Li Li; Li-Qiong Guo; Jun-Fang Lin; Guang-Hong Wu; Jun Lu; Zhi-Wei Ye (Critical Reviews in Food Science and Nutrition, 2023)

Efflux transport proteins of Tetrahymena thermophila play important roles in resistance to perfluorooctane sulfonate exposure - Mengmeng Wang; Bingyu Song; Tianyu Song; Kailun Sun; Jin He; Jiewei Deng; Ling Fang; Tiangang Luan; Li Lin (Journal of Hazardous Materials, 2023)

Polystyrene microplastic attenuated the toxic effects of florfenicol on rice (Oryza sativa L.) seedlings in hydroponics: From the perspective of oxidative response, phototoxicity and molecular metabolism - Luoqin Shen; Ping Zhang; Yanyao Lin; Xinting Huang; Siyi Zhang; Zhiheng Li; Zhiguo Fang; Yuezhong Wen; Huijun Liu (Journal of Hazardous Materials, 2023)

Cellulose supported and strengthened shear stiffening gel with enhanced impact-resistant performance - Zhen Zhang; Xiaoming Lin; Junyi Lin; Nana Liu; Bolin Wan; Xiong Fang; Lingling Shui; Yingzhan Li; Kam C. Tam; Jin Huang; Guofu Zhou (Chemical Engineering Journal, 2023)

Fixation of CO2 by soil fungi: contribution to organic carbon pool and destination of fixed carbon products - Fang Li; Zhong-Jun Jia; Lin Chen; Yan-Lai Han; Yuan-Feng Cai; Brajesh K. Singh; Jia-Bao Zhang (Biology and Fertility of Soils, 2023)

Co-exposure to iron, copper, zinc, selenium and titanium is associated with the prevention of gastric precancerous lesions - Tingting Wang; Fang Xu; Xiao Lin; Yaning Lv; Xiaohui Zhang; Wenli Cheng; Li Wang; Min Wang; Meng Zhang; Tao Xia; Shiqing Qian; Min Tang; et al. (BioMetals, 2023)

Rhizosphere microbiome assembly mediated by consecutive monoculture triggers the replant disease of Rehmannia glutinosa - Qian Li; Sisi Cai; Yuan Fang; Muhammad Umar Khan; Bianhong Zhang; Xuzhong Duan; Shutong Fan; Cuihong Lu; Mingjie Li; Li Gu; Juanying Wang; Jun Xiong; et al. (Applied Soil Ecology, 2023)

One-pot preparation of bi-functional POSS-based hybrid monolith via photo-initiated polymerization for isolation of extracellular vesicles - Qi Zhang; Mengxi Chen; Fang Xu; Wen Wu; Xintong Luo; Ying Wang; Jiaxi Li; Xuanhao Cui; Yujia Tan; Zhi Li; Yujie Lin; Haiyang Zhang; et al. (Analytica Chimica Acta, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Metal sulfide-based Z-scheme heterojunctions in photocatalytic removal of contaminants, H2 evolution and CO2 reduction: Current status and future perspectives - Fang Deng; Junlong Peng; Xibao Li; Xubiao Luo; Priyanka Ganguly; Suresh C. Pillai; Bangxing Ren; Lin Ding; Dionysios D. Dionysiou (Journal of Cleaner Production, 2023)

Maternal di-(2-ethylhexyl) phthalate exposure elicits offspring IFN-λ upregulation: Insights from birth cohort, murine model, and in vitro mechanistic analysis - Fu-Chen Kuo; Mei-Lan Tsai; Shin-Ting Wu; Sih-Syuan Li; Chia-Fang Wu; Shu-Lin Wang; Michael W.Y. Chan; Jau-Ling Suen; Ming-Tsang Wu; Chih-Hsing Hung (Food and Chemical Toxicology, 2023)

Cation-deficient perovskite Sr1-xTi1-yNiyO3-δ anodes with in-situ exsolution of Ni nanoparticles for direct ammonia solid oxide fuel cells - Fulan Zhong; Lei Wang; Huihuang Fang; Yu Luo; Chongqi Chen; Li Lin; Kongfa Chen; Lilong Jiang (Chemical Engineering Journal, 2023)

An anaerobic dynamic membrane bioreactor (AnDMBR) system enhanced the biogas conversion efficiency and stability of mesophilic codigestion with waste activated sludge and food waste - Bao-Shan Xing; Yi Zhang; Rui-Qi Zhang; Jing Ma; Xiang-Lin Chang; Xi-Fang Tang; Yu-You Li; Xiaochang C. Wang; Rong Chen (Chemical Engineering Journal, 2023)

Dual cross-linked starch hydrogel for eugenol encapsulation and the formation of hydrogen bonds on textural hydrogel - Ruikang Lin; Ruoxuan Xu; Huiyi Chen; Bo Liu; Chao Yuan; Li Guo; Bo Cui; Yishan Fang (Carbohydrate Polymers, 2023)

The associations of non-essential metal mixture with fasting plasma glucose among Chinese older adults without diabetes - Jing-Yuan Lei; Pan-Pan Wang; Hong-Li Wang; Yuan Wang; Liang Sun; Bing Hu; Su-Fang Wang; Dong-Mei Zhang; Gui-Mei Chen; Chun-Mei Liang; Fang-Biao Tao; Lin-Sheng Yang; et al. (Environmental Science and Pollution Research, 2023)

Antimony(III) removal by biogenic manganese oxides formed by Pseudomonas aeruginosa PA-1: kinetics and mechanisms - Qing Li; Yun He; Aijiang Yang; Xia Hu; Fang Liu; Jincheng Mu; Shixue Mei; Lin-Ping Yang (Environmental Science and Pollution Research, 2023)

Bidirectional crosstalk of the cAMP/ROS-dependent signaling pathways in inflammatory macrophage: An activation of formononetin - Lan-Fang Zhang; Xiao-Yan Zhang; Ai-Cheng Wang; Yi-Jia Feng; Xiao-Ming Qi; Yuan-Lin Zhang; Qing-Fang Li; Yuan-Biao Qiao; Qing-Shan Li (Toxicology and Applied Pharmacology, 2023)

Enhanced photochemical degradation and transformation of ciprofloxacin in a UV/calcium peroxide system: pH effects, defluorination kinetics, and different components numerical analysis - Zheng Fang; Zifeng Lin; Ping Chen; Mengying Feng; Haijin Liu; Zhenjun Xiao; Zili Lin; Dagaung Li; Dezhu Liu; Yudan Zhang; Wenying Lv; Guoguang Liu (Journal of Cleaner Production, 2023)

Association of the components of ambient fine particulate matter (PM2.5) and chronic kidney disease prevalence in China - Xingyuan Zhang; Jiayi Tao; Fang Lei; Tao Sun; Lijin Lin; Xuewei Huang; Peng Zhang; Yan-Xiao Ji; Jingjing Cai; Xiao-Jing Zhang; Hongliang Li (Journal of Environmental Management, 2023)

Lateral performance of mortise-tenon jointed frames in multi-story traditional heavy timber structures: Mechanism and quantification - Ya-Jie Wu; He-Shou Lin; Lei Wang; Qi-Fang Xie; Li-Peng Zhang (Engineering Structures, 2023)

Water-dispersible and stable polydopamine coated cellulose nanocrystal-MXene composites for high transparent, adhesive and conductive hydrogels - Bolin Wan; Nana Liu; Zhen Zhang; Xiong Fang; Yugao Ding; Haosheng Xiang; Yunqing He; Mingxian Liu; Xiaoming Lin; Juntao Tang; Yingzhan Li; Biao Tang; et al. (Carbohydrate Polymers, 2023)

Dust storm forecasting through coupling LOTOS-EUROS with localized ensemble Kalman filter - Mijie Pang; Jianbing Jin; Arjo Segers; Huiya Jiang; Li Fang; Hai Xiang Lin; Hong Liao (Atmospheric Environment, 2023)

Dual stimuli interface with logical division using local move stimuli - Mengfan Li; Lingyu Wu; Fang Lin; Miaomiao Guo; Guizhi Xu (Cognitive Neurodynamics, 2023)

Ammoniated straw incorporation increases maize grain yield while decreasing net greenhouse gas budget on the Loess Plateau, China - Jinchao Li; Yue Li; Zhipeng Yang; Yanxin Fang; Cheng Li; Yulong Shi; Nanping Lin; Qinge Dong; Kadambot H.M. Siddique; Hao Feng; Naijiang Wang (Agriculture, Ecosystems & Environment, 2023)

A rapid and effective method for obtaining ardicrenin from Ardisia crenata Sims var. bicolor plants - Zhen Lin; Xiuling Yang; Lin Li; Chunyan Ma; Lingjuan Kong; Huancheng Li; Shican Xiong; Haiyan Zhong; Shangrao Pu; Fang Liang; Ju Hu (Brazilian Journal of Botany, 2023)

Spatiotemporal dynamics of near-surface ozone concentration and potential source areas in northern China during 2015—2020 - Kang Ma; Yuesheng Lin; Fengman Fang; Huarong Tan; Jingwen Li; Lei Ge; Fei Wang; Youru Yao (Environmental Science and Pollution Research, 2023)

Long-term in-situ starvation and reactivation of co-digestion with food waste and corn straw in a continuous AnDMBR: Performance, sludge characteristics, and microorganism community - Bao-Shan Xing; Xiang-Lin Chang; Sifan Cao; Dong Wu; Yi Zhang; Xi-Fang Tang; Yu-You Li; Xiaochang C. Wang; Rong Chen (Science of The Total Environment, 2023)

Dietary exposure to nTiO2 reduces byssus performance of mussels under ocean warming - Saishuai Li; Hui Chen; Chunhua Liu; Inna M. Sokolova; Yuchuan Chen; Fujing Deng; Zhe Xie; Li'ang Li; Wei Liu; James Kar-Hei Fang; Daohui Lin; Menghong Hu; et al. (Science of The Total Environment, 2023)

Biogeographic distribution, ecotype partitioning and controlling factors of Chloroflexi in the sediments of six hadal trenches of the Pacific Ocean - Jiaxin Wu; Li Wang; Jiangtao Du; Yuheng Liu; Lin Hu; Hui Wei; Jiasong Fang; Rulong Liu (Science of The Total Environment, 2023)

Sinomenine ameliorates rheumatoid arthritis by modulating tryptophan metabolism and activating aryl hydrocarbon receptor via gut microbiota regulation - Zheng-Meng Jiang; Su-Ling Zeng; Tian-Qing Huang; Yang Lin; Fang-Fang Wang; Xing-Jiao Gao; Jing Li; Ping Li; E-Hu Liu (Science Bulletin, 2023)

A novel water disinfection method via cuprous ion generation in a copper ferrite/sulfite system and associated mechanism - Lu Qin; Dongqi Wang; Cong Liu; Guodong Chai; Mingliang Fang; Jiake Li; Hui Wang; Zhe Wang; Haiyu Meng; Xing Zheng; Mengbo Huang; Yi Xiao; et al. (Journal of Water Process Engineering, 2023)

Purification and identification of xanthine oxidase inhibitory peptides from enzymatic hydrolysate of α-lactalbumin and bovine colostrum casein - Yi-Fang Gao; Meng-Qi Liu; Zhong-Han Li; Han-Lin Zhang; Jia-Qi Hao; Bo-Hao Liu; Xiao-Yan Li; Yu-Qi Yin; Xiao-Hui Wang; Qian Zhou; Di Xu; Bao-Ming Shi; et al. (Food Research International, 2023)

The PIWI-specific insertion module helps load longer piRNAs for translational activation essential for male fertility - Xin Wang; Di-Hang Lin; Yue Yan; An-Hui Wang; Jiaoyang Liao; Qian Meng; Wen-Qing Yang; Heng Zuo; Min-Min Hua; Fengjuan Zhang; Hongwen Zhu; Hu Zhou; et al. (Science China Life Sciences, 2023)

Plasma cell-free DNA promise monitoring and tissue injury assessment of COVID-19 - Xin Jin; Yanqun Wang; Jinjin Xu; Yimin Li; Fanjun Cheng; Yuxue Luo; Haibo Zhou; Shanwen Lin; Fei Xiao; Lu Zhang; Yu Lin; Zhaoyong Zhang; et al. (Molecular Genetics and Genomics, 2023)
Coronavirus 2019 (COVID-19) is a complex disease that affects billions of people worldwide. Currently, effective etiological treatment of COVID-19 is still lacking; COVID-19 also causes damages to various organs that affects therapeutics and mortality of the patients. Surveillance of the treatment responses and organ injury assessment of COVID-19 patients are of high clinical value. In this study, we investigated the characteristic fragmentation patterns and explored the potential in tissue injury assessment of plasma cell-free DNA in COVID-19 patients. Through recruitment of 37 COVID-19 patients, 32 controls and analysis of 208 blood samples upon diagnosis and during treatment, we report gross abnormalities in cfDNA of COVID-19 patients, including elevated GC content, altered molecule size and end motif patterns. More importantly, such cfDNA fragmentation characteristics reflect patient-specific physiological changes during treatment. Further analysis on cfDNA tissue-of-origin tracing reveals frequent tissue injuries in COVID-19 patients, which is supported by clinical diagnoses. Hence, our work demonstrates and extends the translational merit of cfDNA fragmentation pattern as valuable analyte for effective treatment monitoring, as well as tissue injury assessment in COVID-19.

SHP2: its association and roles in systemic lupus erythematosus - Chan Yang; Rong Li; Lin-Chong Su; You-Yu Lan; You-Qiang Wang; Wang-Dong Xu; An-Fang Huang (Inflammation Research, 2023)

Calcium-dependent activation of CPK12 facilitates its cytoplasm-to-nucleus translocation to potentiate plant hypoxia sensing by phosphorylating ERF-VII transcription factors - Biao Fan; Ke Liao; Lin-Na Wang; Li-Li Shi; Yi Zhang; Ling-Jing Xu; Ying Zhou; Jian-Feng Li; Yue-Qin Chen; Qin-Fang Chen; Shi Xiao (Molecular Plant, 2023)

Corrigendum to “Mechanism of PM2.5-induced human bronchial epithelial cell toxicity in central China” [J Hazard Mater 396 (2020) 122747] - Shuyin Duan; Meihua Zhang; Yaqiong Sun; Zhenya Fang; Hefeng Wang; Shuxian Li; Yanze Peng; Juan Li; Junxia Li; Jiaqi Tian; Haoyu Yin; Sanqiao Yao; et al. (Journal of Hazardous Materials, 2023)

Enhanced crude oil degradation and reshaped microbial community structure using straw-sludge biochar-persulfate oxidative system in oil-contaminated soil - Qiyou Liu; Fang Tang; Shuo Sun; Yaru Wang; Yuhua Su; Chaocheng Zhao; Xiuxia Zhang; Yingying Gu; Lin Li (Journal of Environmental Chemical Engineering, 2023)

Coaxial electrospun nanofibrous substrates with tunable wettability for constructing cucurbit[n]uril-embedded organic solvent nanofiltration membranes - Qian Wang; Qin-Yuan He; Liu-Lin Zhao; Yue Wang; Rong Fang; Cong Luo; Wei-Tong Lu; Hong-Ya Jiang; Shi-Peng Sun; Xue-Li Cao (Chemical Engineering Journal, 2023)

Integrated physiological and metabolomic analysis reveals new insights into toxicity pathways of paraquat to Microcystis aeruginosa - Fang Bai; Guangbin Gao; Tianli Li; Jin Liu; Lin Li; Yunlu Jia; Lirong Song (Aquatic Toxicology, 2023)

Genome-wide Association Study of Root Hair Length in Maize - Li Xuhui; Lu Siqi; Chen Weiwei; Zhu Hang; Lin Huanzhang; Fu Danwen; Fan Lina; Fang Junteng; Hu Yuanqiang; Zhang Xiangbo; Chang Hailong; Qi Yongwen (Tropical Plant Biology, 2023)

Isoquinoline alkaloids from Corydalis edulis Maxim. Exhibiting insulinotropic action - Zhi-Tian Peng; Hui-Xia Huo; Ling-Hui Chao; Yue-Lin Song; Di-Fa Liu; Zhang-Wei Wang; Yuan Zhang; Yun-Fang Zhao; Peng-Fei Tu; Jiao Zheng; Jun Li (Phytochemistry, 2023)

High fructose-induced skeletal muscle insulin resistance could be alleviated by berberine via AMPD1 and ADSL - Juanjuan Cheng; Xingdong Ma; Guangtao Yan; Qiuxia Yu; Zhen Huang; Guoshu Lin; Mengyao Li; Fengkun Guan; Ziren Su; Fang Yan; Yuhong Liu; Qingfeng Xie (Food and Chemical Toxicology, 2023)

Intercropped soybean boosts nitrogen benefits and amends nitrogen use pattern under plastic film mulching in the semiarid maize field - Wei Zhang; Yong-Xian Wei; Aziz Khan; Jun-Sheng Lu; Jun-Lan Xiong; Shuang-Guo Zhu; Xiang-Wen Fang; Wei Wang; Meng Hao; Ling Zhao; Xiao-Lin Zhang; Jian-Ming Deng; et al. (Field Crops Research, 2023)

Ag quantum dots decorated ultrathin g-C3N4 nanosheets for boosting degradation of pharmaceutical contaminants: Insight from interfacial electric field induced by local surface plasma resonance - Zhenzhou Wang; Danqi Wang; Fang Deng; Xinggang Liu; Xibao Li; Xubiao Luo; Yanzhi Peng; Jian Zhang; Jianping Zou; Lin Ding; Longshuai Zhang (Chemical Engineering Journal, 2023)

Salinibacterium sedimenticola sp. nov., Isolated from Tidal Flat Sediment - Chun-Yan Lu; Lei Dong; Shuai Li; Wen-Hui Lian; Zhi-Liang Lin; Zhuo-Huan Zheng; Lei Gao; Bao-Zhu Fang; Wen-Jun Li (Current Microbiology, 2023)

Stress response characteristics of BFRP anchors on loess mudstone slope under rainfall conditions - Hong Wei; Hong-gang Wu; Dao-yong Wu; Lin Tang; Li-fang Pai; Wei Guan (Journal of Mountain Science, 2023)

HAI-1 is required for the novel role of FGFBP1 in maintenance of cell morphology and F-actin rearrangement in human keratinocytes - Dajun D. Lu; Nanxi Huang; Sheng-Wen A. Li; Jessica R. Fang; Chih-Hsin Lai; Jehng-Kang Wang; Khee-Siang Chan; Michael D. Johnson; Chen-Yong Lin (Human Cell, 2023)

Interconnected versus unconnected microorganisms: Does it matter in anaerobic digestion functioning - Qiang Lin; Jo De Vrieze; Lingjuan Li; Xiaoyu Fang; Xiangzhen Li (Journal of Environmental Management, 2023)

A novel dehydrocoenzyme activator combined with a composite microbial agent TY for enhanced bioremediation of crude oil-contaminated soil - Qiyou Liu; Shuo Sun; Shuiquan Chen; Yuhua Su; Yaru Wang; Fang Tang; Chaocheng Zhao; Lin Li (Journal of Environmental Management, 2023)

Magnetic ternary layered double hydroxides for efficient removal of 1-naphthalene acetic acid from waters: Adsorption behavior and mechanism - Ti-Bo Fang; Hua Xiao; Ling-Xi Zhao; Na Li; Ling-Yu Luan; Zhao-Xing Yan; Jin-Ming Lin; Ru-Song Zhao (Journal of Environmental Chemical Engineering, 2023)

Lactobacillus plantarum isolated from kefir enhances immune responses and survival of white shrimp (Penaeus vannamei) challenged with Vibrio alginolyticus - Kuo-Chun Tseng; Huai-Ting Huang; Shu-Ning Huang; Fang-Yi Yang; Wen-Hsiung Li; Fan-Hua Nan; Yu-Ju Lin (Fish & Shellfish Immunology, 2023)

The eradication of biofilm for therapy of bacterial infected chronic wound based on pH-responsive micelle of antimicrobial peptide derived biodegradable microneedle patch - Xiao-Ling Lei; Kai Cheng; Yong Li; Zi-Tao Zhong; Xiao-Lin Hou; Lai-Bo Song; Fang Zhang; Jian-Hao Wang; Yuan-Di Zhao; Qiu-Ran Xu (Chemical Engineering Journal, 2023)

Composition, Distribution, and Source Apportionment of Organochlorine Pesticides (OCPs) in Soil of a Chemical Industrial Park and its Surrounding in the Northeast of Qinghai-Tibet Plateau - Xiaojun Li; Lixia Cao; Xin Lin; Wanlong Fu; Zongqiang Gong; Xiangfeng Zeng; Huajun Fang; Zhiheng Li (Water, Air, & Soil Pollution, 2023)

Activating α7nAChR helps post-myocardial infarction healing by regulating macrophage polarization via the STAT3 signaling pathway - Xiao-Hui Niu; Rong-Hua Liu; Xiao Lv; Rui-Lin He; Fang-Zhou Lv; Shu-Jie Wu; Xu-Qing Li; Lei Li; Jia-Feng Lin (Inflammation Research, 2023)

Anti-inflammatory flavonoid derivatives from the heartwood of Dalbergia odorifera T. Chen - Ni-li Zan; Zi-Han Lu; Xin-Yu Wang; Rong-Ye Wang; Nai-Yun Liang; Hui-Xia Huo; Yun-Fang Zhao; Yue-Lin Song; Peng-Fei Tu; Jiao Zheng; Jun Li (Natural Product Research, 2023)

The changes of chemical molecular components in soil organic matter are associated with fungus Mortierella capitata K. - Fang Li; Lin Chen; Zhan-Hui Zhao; Yue Li; Hai-You Yu; Yi Wang; Jia-Bao Zhang; Yan-Lai Han (Soil and Tillage Research, 2023)

Corrigendum to “Induction of core symptoms of autism spectrum disorders by in vivo CRISPR/Cas9-based gene editing in the brain of adolescent rhesus monkeys” [Sci. Bull. 66(9) (2021) 937–946] - Shi-Hao Wu; Xiao Li; Dong-Dong Qin; Lin-Heng Zhang; Tian-Lin Cheng; Zhi-Fang Chen; Bin-Bin Nie; Xiao-Feng Ren; Jing Wu; Wen-Chao Wang; Ying-Zhou Hu; Yi-lin Gu; et al. (Science Bulletin, 2023)

Rapid expansion of wetlands on the Central Tibetan Plateau by global warming and El Niño - Yang Li; Zhengyang Hou; Liqiang Zhang; Changqing Song; Shilong Piao; Jintai Lin; Shushi Peng; Keyan Fang; Jing Yang; Ying Qu; Yuebin Wang; Jingwen Li; et al. (Science Bulletin, 2023)

Bioaccumulation of emerging persistent organic pollutants in the deep-sea cold seep ecosystems: Evidence from chlorinated paraffin - Lina Lyu; Kejing Fang; Zhenchang Zhu; Jie Li; Yu Chen; Lin Wang; Zhimao Mai; Qiqi Li; Si Zhang (Journal of Hazardous Materials, 2023)

Exposure of ambient PM2.5 during gametogenesis period affects the birth outcome: Results from the project ELEFANT - Liqiong Guo; Huishu Lin; Hongyu Li; Xiaobin Jin; Lei Zhao; Penghui Li; Naiwei Xu; Song Xu; Junkai Fang; Shaowei Wu; Qisijing Liu (Environmental Research, 2023)

Gold − Titanium dioxide heterojunction for enhanced sonodynamic mediated biofilm eradication and peri-implant infection treatment - Fang Li; Qiyuan Pan; Yun Ling; Jingying Guo; Yaru Huo; Chao Xu; Manwen Xiong; Meng Yuan; Ziyong Cheng; Min Liu; Jun Lin (Chemical Engineering Journal, 2023)

Hydraulic determinants of drought-induced tree mortality and changes in tree abundance between two tropical forests with different water availability - Yong-Qiang Wang; Hui-Qing Song; Ya-Jun Chen; Pei-Li Fu; Jiao-Lin Zhang; Kun-Fang Cao; Shi-Dan Zhu (Agricultural and Forest Meteorology, 2023)

Risk assessment and environmental determinants of urinary phthalate metabolites in pregnant women in Southwest China - Nian Wu; Lin Tao; Kunming Tian; Xia Wang; Caidie He; Songlin An; Yingkuan Tian; Xiang Liu; Wei Chen; Haonan Zhang; Pei Xu; Dengqing Liao; et al. (Environmental Science and Pollution Research, 2023)

Highly selective adsorption of Hg (II) from aqueous solution by three-dimensional porous N-doped starch-based carbon - Chao Geng; Ruikang Lin; Peilin Yang; Pengfei Liu; Li Guo; Bo Cui; Yishan Fang (Environmental Science and Pollution Research, 2023)

Polysaccharide extracted from pomelo fruitlets attenuate hepatic lipid accumulation in hybrid groupers (Epinephelus lanceolatus♂ × Epinephelus fuscoguttatus♀) - Cuiyun Zou; Yuke Fang; Nuoyi Lin; Gengsheng Xiao; Li Lin; Huifan Liu (Frontiers in Marine Science, 2023)
Introduction Pomelo is one of the most consumed fruits due to its distinct flavor and sour taste, while large quantities of pomelo fruitlets discard during cultivation and most of them are disposed of as wastes. Such an issue has led to some research on how to make a high value-added reutilization of these fruitlets. Therefore, it was aimed to determine the structural characteristics of the polysaccharide of pomelo fruitlets and evaluate its attenuating effect on the hepatic lipid accumulation in hybrid groupers ( Epinephelus lanceolatus♂ × Epinephelus fuscoguttatus♀ ). Methods and results In this research, YZ-0.5A is a 15,332 Da NaCl-soluble polysaccharide extracted from pomelo fruitlet which was characterized to mainly contain galactose and galacturonic acid and its putative structure was proven to be →2,4)- α-L-Rhap-(1→4)-α-D-GalAp-(1→4)-α-D-GalAp-(1→ with 3 branches. In vivo study, five isolipidic diets (containing 15% lipid) were fed to the groupers with an initial weight of 13.46 ± 0.08 g for 8 weeks, of which the dietary level of YZ-0.5A was 0 mg/kg (control), 150 mg/kg, 300 mg/kg, 600 mg/kg and 1200 mg/kg respectively. We found that the treatment of YZ-0.5A, especially 600 mg/kg, exerted an improved effect on the excessive lipid accumulation in grouper fed with a high-fat diet. In vitro , three graded concentrations of YZ-0.5A (75, 150 or 300 μg/ml) were added to the grouper primary hepatocytes respectively after incubation with 20% lipid emulsion (2 ml/L). The signs of recovery on morphological features observed under examined by histological evaluation supported the lipid lowering effect of YZ0.5-A. Further investigation showed that YZ0.5-A mitigated lipid emulsion-induced irregular lipid deposition by regulating various lipometabolism-related indicators, thereby alleviating oxidative stress and apoptosis. Discussion Overall results exhibited the therapeutic potential of YZ0.5-A and elucidated its underlying mechanism in the fish with excessive lipid deposition, which first suggested the feasibility of reprocessing discarded pomelo fruitlet as medicine in aquaculture.

RNA sequencing provides insights into the effect of dietary ingestion of microplastics and cadmium in the sea cucumber Apostichopus japonicus - Chenxi Zhang; Libin Zhang; Lingling Li; Mohamed Mohsen; Fang Su; Xu Wang; Chenggang Lin (Frontiers in Marine Science, 2023)
Introduction Microplastics (MPs) and cadmium (Cd) are persistent pollutants in aquatic environments. Sea cucumbers are susceptible to MPs and Cd due to their feeding behavior. Methods This study, based on Illumina sequencing, compared the transcriptomes of A. japonicus before and after Cd and/or MPs exposure. Additionally, we detected the changes of catalase (CAT), and superoxide dismutase (SOD) activity, glutathione (GSH), and malondialdehyde (MDA) content in sea cucumbers. Results and Discussion High concentration of MPs caused the increase of SOD activity. High concentration combined treatment resulted in significant up regulation of these four indicators in A. japonicus and had the largest number of differential expression genes (DEGs) reaching 1,618 DEGs, consisting of 789 up regulated along with 829 down regulated DEGs. Transcriptome results showed that Cd induced up regulation of intestinal FAS associated death domain protein (FADD) expression, which may cause apoptosis and inflammation. The increase of intestinal putative heparan sulfate 2-O-sulfotransferase in cadmium treatment groups provided a mechanism for host defense. The imbalance of expression of the NOD-like receptor (NLR) family inflammatory bodies and caspase 6 in the microplastic treatment group also led to the inflammatory reaction in the intestine of sea cucumber. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis showed that in the process of fatty acid metabolism, MPs and Cd showed antagonistic effects, mainly in the inconsistent expression of Stearoyl CoA Ddesaturase (SCD1) protein. The significant changes of Toll interacting protein (TOLLIP) and E-selectin (SELE) in all Cd and MPs treatment groups may indicate the key immune response genes of sea cucumber to Cd exposure and MPs exposure. These genes were involved in the immune defense of sea cucumber exposed to different levels of Cd and MPs. This study provided insights into the mechanism of dietary MPs and Cd intake in an economically and ecologically important invertebrate species.

A novel chitosan-biochar immobilized microorganism strategy to enhance bioremediation of crude oil in soil - Qiyou Liu; Yaru Wang; Shuo Sun; Fang Tang; Hongxu Chen; Shuiquan Chen; Chaocheng Zhao; Lin Li (Chemosphere, 2023)

Co-hydrothermal carbonization of polyvinyl chloride and lignocellulose biomasses for chlorine and inorganics removal - Jing Zhang; Yuhan Chen; Xu Xia; Binbin Fu; Chuanjin Lin; Guangchao Jia; Xin Cui; Fang Liu; Peitao Zhao; Yimin Li (Waste Management, 2023)

ARSCP: An antimicrobial residue surveillance cloud platform for animal-derived foods - Jun-Jun Yu; Ya-Lin Hu; Cheng-Zheng Liu; Shuai-Bin Wu; Zi-Jian Zheng; Ze-Hua Cui; Li Chen; Tian Wei; Shi-Kai Sun; Jun Ning; Xiang Wen; Qiu-Yue Diao; et al. (Science of The Total Environment, 2023)

Generating Sentinel-2 all-band 10-m data by sharpening 20/60-m bands: A hierarchical fusion network - Jingan Wu; Liupeng Lin; Chi Zhang; Tongwen Li; Xiao Cheng; Fang Nan (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Heat transfer behavior of an immersed tube with sCO2 working fluid in a hot fluidized bed at high pressure - Yu Huang; Xu Bao; Yuanqiang Duan; Lin Li; Dongdong Fang; Yueming Wang; Lunbo Duan (Fuel, 2023)

Sulfur isotope, fluid inclusions, and quartz solubility model decipher multistage hydrothermal fluids evolution and ore precipitation mechanism at the Nantai porphyry Mo deposit, Qinling, Central China - Zhong-Yu Zhang; Yin-Hong Wang; Jia-Jun Liu; Shan-Yuan Lin; Fang-Fang Zhang; Wei Zhang; Zhen-Yu Bo; Hui Zhang; Hong-Yu Li (Chemical Geology, 2023)

Application of the rapid leaf A–Ci response (RACiR) technique: examples from evergreen broadleaved species - Quanhong Lin; Di Tian; Changti Zhao; Bin Wang; Zhengbing Yan; Benjamin D. Stocker; Yu’e Li; Jingyun Fang (Photosynthesis Research, 2023)

In situ phytostabilization of arable soils severely contaminated with cadmium at Yangshuo, Southern China, using cash crops and amendments: a comprehensive performance evaluation - Bo-Fang Yan; Mei-Lin Yan; Xue Xiao; Rong-Liang Qiu; Yuan-Qing Chao; Yin-Xin Li; Su-Lian Lv; Zhong-Xin Tan; Ye-Tao Tang (Journal of Soils and Sediments, 2023)

Correction to: Microplastic pollution and its impact on marine microbes in Zhanjiang, China - Qing-Lang Song; Fang-Hong Nie; Di-Hua Zhu; Yun-Li Wei; Min Zhang; Yao Hu; Meng-Meng Chen; Dan-Ju Kang; Zhi-Bao Chen; Hong-Ying Lin; Jin-Jun Chen (Journal of Coastal Conservation, 2023)

Dexmedetomidine alleviates acute lung injury by promoting Tregs differentiation via activation of AMPK/SIRT1 pathway - Zheng-tao Zhang; Ke Xie; Ren-jie Luo; Dan-ying Zhang; Zhi-wei He; Ke-feng Li; Shi-hui Lin; Fang Xu (Inflammopharmacology, 2023)

Spatiotemporal Characteristics and Future Scenario Simulation of the Trade-offs and Synergies of Mountain Ecosystem Services: A Case Study of the Dabie Mountains Area, China - Lin Fang; Yanxiao Liu; Canfeng Li; Jun Cai (Chinese Geographical Science, 2023)

Antiherbivore effect of Cuscuta campestris against Spodoptera frugiperda - Chang-Lin Sung; Fang-Yu Hu; Yi Li; Shin-Fu Tsai; Wen-Po Chuang (Arthropod-Plant Interactions, 2023)

Associations between temperature variations and tourist arrivals: analysis based on Baidu Index of hot-spring tourism in 44 cities in China - Li Wang; Ling Xin; Yongjian Zhu; Yanyan Fang; Lin Zhu (Environmental Science and Pollution Research, 2023)

Effective immobilization of Cd(II) in soil by biotic zero-valent iron and coexisting sulfate - Weiquan Li; Yuhang Yang; Xueying Lin; Weizhao Yin; Zhanqiang Fang; Ping Li; Jinhua Wu (Chemosphere, 2023)

Water microecology is affected by seasons but not sediments: A spatiotemporal dynamics survey of bacterial community composition in Lake Changshou—The largest artificial lake in southwest China - Ai-ling Chen; Fu-qing Xu; Xia Su; Fu-pan Zhang; Wan-chao Tian; Shang-jie Chen; Fang Gou; Zhi-lin Xing; Jin-xin Xiang; Juan Li; Tian-tao Zhao (Marine Pollution Bulletin, 2023)

Composition of dissolved organic matter (DOM) in wastewater treatment plants influent affects the efficiency of carbon and nitrogen removal - Ling Wen; Fang Yang; Xuan Li; Siwan Liu; Yuye Lin; En Hu; Li Gao; Ming Li (Science of The Total Environment, 2023)

Rapid and sensitive detection of quizalofop-p-ethyl by gold nanoparticle-based lateral flow immunoassay in agriproducts and environmental samples - Xue Liu; Jiao Li; Yue Huang; Zhongrong Zhang; Qing Lin; Pengliang Xia; Fanyu Kong; Jun Qiu; Song Fang; Xiude Hua (Science of The Total Environment, 2023)

Rational design of ordered porous nanoparticles for selective extraction of nitrobenzene compounds - Sheng Peng; Minhui Shen; Xiang Li; Yuan-Jun Tong; Jing Guo; Wei Lin; Yu-Xin Ye; Jianqiao Xu; Ningbo Zhou; Fang Zhu; Gangfeng Ouyang (Journal of Hazardous Materials, 2023)

Assessment of algae and greenhouse gases in different reservoirs worldwide by reactor model - Yi-Xuan Li; Kai-Kai Deng; Shu-Qing Zhang; Gui-Jiao Lin; Fang Fang; Jin-Song Guo (Journal of Cleaner Production, 2023)

Emerging biosensors to detect aflatoxin M1 in milk and dairy products - Qi Chen; Meng Meng; Wang Li; Ying Xiong; Yong Fang; Qinlu Lin (Food Chemistry, 2023)

Large-flake graphene-modified biochar for the removal of bisphenol S from water: rapid oxygen escape mechanism for synthesis and improved adsorption performance - Yurong Gao; Zheng Fang; Wenhui Lin; Hanbo Chen; Amit Bhatnagar; Jianhong Li; Yanhai Xie; Yanping Bao; Junfeng Chen; Hongting Zhao; Jun Meng; Wenfu Chen; et al. (Environmental Pollution, 2023)

Effects of physiologic activities of plankton on CO2 flux in the Three Gorges Reservoir after rainfall during algal blooms - Yi-Xuan Li; Kai-Kai Deng; Gui-Jiao Lin; Bin Chen; Fang Fang; Jin-Song Guo (Environmental Research, 2023)

Screening of structural and functional alterations in duckweed (Lemna minor) induced by per- and polyfluoroalkyl substances (PFASs) with FTIR spectroscopy - Ying-Lin Wu; Qian Xiong; Ben Wang; You-Sheng Liu; Pei-Liang Zhou; Li-Xin Hu; Fang Liu; Guang-Guo Ying (Environmental Pollution, 2023)

Developing membrane reactors with suspended polyphthalocyanine nanoplatelets for upscaling syntheses of protein-polymer bioconjugates - Wen Fang Wei; Wan Lin Guo; Min Jian; Liu Shu Qin; Xue Li; Tao Cai (Chemical Engineering Journal, 2023)

Temperature tolerant all-solid-state touch panel with high stretchablity, transparency and self-healing ability - Zhenglin Chen; Fang Li; Likun Zhang; Zhengyang Lei; Canhui Yang; Chufan Xiao; Lijin Lian; Xi Yuan; Gul Ijaz; Jia'e Yang; Zijun Lin; Yunfeng He; et al. (Chemical Engineering Journal, 2023)

Insights into CQDs-doped perylene diimide photocatalysts for the degradation of naproxen - Zheng Fang; Yang Liu; Ping Chen; Daguang Li; Haijin Liu; Zhenjun Xiao; Yixun Zheng; Zifeng Lin; Jin Luo; Wenying Lv; Guoguang Liu (Chemical Engineering Journal, 2023)

Associations between gastrointestinal infection and urinary phthalate metabolite concentrations in US children and adolescents from NHANES 2005–2016 - Chuang Zhang; Weirui Ren; Chi Sun; Lin Liu; Meng Li; Wenbo Wang; Yanbin Fang; Lin Liu; Xiaofeng Yang; Xiangjian Zhang; Suolin Li (Environmental Science and Pollution Research, 2023)

Transcriptome Analysis Provides an Overview of Genes Involved in the Peculiar Food Preference at First-Feeding Stage in Mandarin Fish (Siniperca chuatsi) - Ling Li; Shu-Lin Tang; Shan He; Xu-Fang Liang (Fishes, 2022)
The mandarin fish (Siniperca chuatsi) is an important economic fish species in China. Many carnivorous fish larvae feed on zooplankton or microdiets. However, the mandarin fish larvae feed on live prey fish exclusively, while refusing zooplankton or microdiets. A stable supply of palatable live prey fish results in high costs. Moreover, the application of live prey fish might bring the risk of pathogens. However, little is known about the genes underlying the food preference of mandarin fish larvae. Partial offspring of the domesticated strain could feed brine shrimp from three days post-hatching (dph), the open mouth day. In the present study, the mandarin fish larvae were randomly divided into three groups, then treated differently at 3 dph: (1) unfed; (2) fed with live prey fish; (3) fed with brine shrimp (Artemia). Differentially expressed genes were identified by RNA-seq. The differential expression of the transcription factors involved in retinal photoreceptor development and differentiation might contribute to the intake of brine shrimp in mandarin fish larvae. Meanwhile, the digestive enzyme genes involved in protein, fat, and carbohydrate digestion have been expressed in mandarin fish larvae at 3 dph, contributing to the digestion of ingested food. Our study provides an overview of genes and biological processes involved in the peculiar food preference at the first-feeding stage in mandarin fish larvae and has critical importance to the future application of non-fish live feeds in the culture of mandarin fish larvae.

Selenium attenuates the association of co-exposure to arsenic, cadmium, and lead with cognitive function among Chinese community-dwelling older adults - Bei-Jing Cheng; Jie Sheng; Hong-Li Wang; Yuan Wang; Hong-Juan Cao; Xiu-De Li; Ting-Ting Zhou; Xiang-Long Meng; Huan-Huan Nie; Su-Fang Wang; Dong-Mei Zhang; Gui-Mei Chen; et al. (Environmental Science and Pollution Research, 2022)

Effects of exposure to phthalate during early pregnancy on gestational diabetes mellitus: a nested case–control study with propensity score matching - Wei Chen; Caidie He; Xiang Liu; Songlin An; Xia Wang; Lin Tao; Haonan Zhang; Yingkuan Tian; Nian Wu; Pei Xu; Dengqing Liao; Juan Liao; et al. (Environmental Science and Pollution Research, 2022)

AIoT-Based Ergometer for Physical Training in Frail Elderly with Cognitive Decline: A Pilot Randomized Control Trial - Chih-Chun Lin; Li-Chieh Kuo; Yu-Sheng Lin; Chia-Ming Chang; Fang Wen Hu; Yi-Jing Chen; Chun-Tse Lin; Fong-Chin Su (Journal of Medical and Biological Engineering, 2022)
Purpose Reduced physical activity is reported in the elderly, especially in institutional residents. Institutionalized older adults exhibit a high prevalence of frailty. In this work, we developed an artificial intelligence of things (AIoT)-based feedback assistive strengthening ergometer (AIFASE), for the physical strengthening of the elderly with intelligent assistance. Methods We conducted a 12-week intervention in a long-term care facility. In total, 16 participants (84.38 ± 6.0 years; 4 males and 12 females) were recruited with 1:1 randomization of exercise to control groups. The muscle strength of the lower extremities, timed up and go test (TUG), and Short-form Physical Performance Battery (SPPB) of the participants were measured. The AIFASE system allows the clinical staff to record the personal physical performance of the elderly and generates personalized exercise prescriptions accordingly. AIFASE also displays the current usage status of all ergometers and the users’ physiological conditions. The algorithms were developed to generate warning alerts when the training workload was too large by personal physiological detection. AIFASE automatically customized the exercise prescription according to the user’s exercise performance. Results After a 12-week AIFASE intervention, the intervention group exhibited significant improvements in the strength of the hip flexor, Semi-Tandem Stand, and Tandem Stand. Conclusion In this study, we developed an AIoT ergometer that delivered customized physical training prescriptions to improve the physical performance of long-term care facility residents. We believe that the application of AIFASE will help improve the quality of institutional care.

Microplastic pollution and its impact on marine microbes in Zhanjiang, China - Qing-Lang Song; Fang-Hong Nie; Di-Hua Zhu; Yun-Li Wei; Min Zhang; Yao Hu; Meng-Meng Chen; Dan-Ju Kang; Zhi-Bao Chen; Hong-Ying Lin; Jin-Jun Chen (Journal of Coastal Conservation, 2022)

The association between essential trace element mixture and atherosclerotic cardiovascular disease risk among Chinese community-dwelling older adults - Xiang-long Meng; Yuan Wang; Hong-li Wang; Huan-huan Nie; Bei-jing Cheng; Hong-juan Cao; Xiu-de Li; Su-fang Wang; Gui-mei Chen; Fang-biao Tao; Jie Sheng; Lin-sheng Yang (Environmental Science and Pollution Research, 2022)

A flocculation tensor to monitor water quality using a deep learning model - Guocheng Zhu; Jialin Lin; Haiquan Fang; Fang Yuan; Xiaoshang Li; Cheng Yuan; Andrew S. Hursthouse (Environmental Chemistry Letters, 2022)
The increasing quantities of polluted waters are calling for advanced purification methods. Flocculation is an essential component of the water purification process, yet flocculation is commonly not optimal due to our poor understanding of the flocculation process. In particular, there is little knowledge on the mechanisms ruling the migration of pollutants during treatment. Here we have created the first tensor diagram, a mathematical framework for the flocculation process, analyzed its properties with a deep learning model, and developed a classification scheme for its relationship with pollutants. The tensor was constructed by combining pixel matrices from a variety of floc images, each with a particular flocculation period. Changing the factors used to make flocs images, such as coagulant dose and pH, resulted in tensors, which were used to generate matrices, that is the tensor diagram. Our deep learning algorithm employed a tensor diagram to identify pollution levels. Results show tensor map attributes with over 98% of sample images correctly classified. This approach offers potential to reduce the time delay of feedback from the flocculation process with deep learning categorization based on its clustering capabilities. The advantage of the tensor data from the flocculation process improves the efficiency and speed of response for commercial water treatment.

Recent development in zebrafish model for bioactivity and safety evaluation of natural products - Fang-Jun Lin; Hang Li; Ding-Tao Wu; Qi-Guo Zhuang; Hua-Bin Li; Fang Geng; Ren-You Gan (Critical Reviews in Food Science and Nutrition, 2022)

Enhanced soil respiration, vegetation and monsoon precipitation at Lantian, East Asia during Pliocene warmth - Kexin Wang; Huayu Lu; Carmala N. Garzione; Lin Zhao; Chenghong Liang; Shuyue Li; Daniel O. Breecker; Fang Lei; Hongyan Zhang (Climate Dynamics, 2022)

Effect of gravel content on the detachment of colluvial deposits in Benggang - Li-ting Zhang; Fang Shuai; Li-bo Chen; Yan-he Huang; Jin-shi Lin; Yue Zhang; Hong-li Ge; Fang-shi Jiang (Journal of Mountain Science, 2022)

A histological study of vascular wall resident stem cells in venous malformations - Hou-Fu Xia; Wen-Qiang Lai; Gao-Hong Chen; Ye Li; Qi-Hui Xie; Yu-Lin Jia; Gang Chen; Yi-Fang Zhao (Cell and Tissue Research, 2022)

Two new physalins from Physalis alkekengi L. var. franchetii (Mast.) Makino - Jia-Min Sun; Ji-Xiang He; Min Huang; Hui-Xin Hu; Lin-Tao Xu; Kai-Li Fang; Xiao-Ning Wang; Tao Shen (Natural Product Research, 2022)

Evaluation of the Potential of the Hard Clam (Meretrix meretrix) Shell Which Can Be Used as the Bioindicator for Heavy Metal Accumulation - Yen-Ting Lin; Fang-Chi Chang; Ming-Tsung Chung; Ze-Kai Li; Chang-Chuan Chan; Ying-Sheng Huang; Kuo-Fang Huang; Yu-San Han (Fishes, 2022)
Clams, Meretrix meretrix, were one of the favorite aquatic products in Taiwan and the world. It was reported that the water pollutants such as heavy metals and chemicals might accumulate in the clam body and shell through filter-feeding behavior. Thus, the bivalves could be used as bioindicators in the aquatic environment. The present study analyzed 20 trace elements, Mg, Sr, Li, Cd, Ba, Mn, Al, U, Ti, Pb, Nd, B, S, Zn, Fe, P, Na, K, Cu, and Ni, in the shells of the clams collected from the wild coastal area and cultured ponds to evaluate which elements have the potential to be biomarkers. The concentrations of 20 elements were detected by Solution-Based Inductively Coupled Plasma Mass Spectrometry (SB-ICPMS). Among them, Cd, Al, U, Ti, Nd, S, and K were below the detection limit. The remaining elements were analyzed for accumulation. The levels of Zn, Fe, and Ni possess high variation in an identical environment; so, a PCA was conducted without these three elements to reduce noise. The PCA result proved that the clam could absorb specific trace elements from the habitat. After a period of time, the contents of the absorption in the shells of the clams living in an identical environment became more similar. The analyzed element, Pb, was not found with a special difference in this study. The levels of Na, Sr, Mg, B, Mn, P, Ba, Li, and Cu reflected different sampling sites, which suggested that these elements in the species M. meretrix had the potential to be used as biomarkers for assessing heavy metal accumulation in the environment.

The full-length genome sequence of a novel amalgavirus in Lilium spp. in China - Yanyan Huo; Xiaoting Li; Jiale Zhou; Shengjie Lin; Jiahao Ding; Huan Liu; Jianglian Yu; Ni Hong; Guoping Wang; Fang Ding (Archives of Virology, 2022)

Effect modification by aging on the associations of nicotine exposure with cognitive impairment among Chinese elderly - Jian Hou; Chao Huang; Bo Zhu; Wei Liu; Qing-qing Zhu; Lu Wang; Tian Li; Chun-jie Yuan; Shao-yang Lai; De-sheng Wu; Fei-qi Zhu; Jia-fei Zhang; et al. (Environmental Science and Pollution Research, 2022)

Transgenic expression of rice OsPHR2 increases phosphorus uptake and yield in wheat - Yan Li; Yuhui Fang; Chaojun Peng; Xia Hua; Yu Zhang; Xueli Qi; Zhengling Li; Yumin Wang; Lin Hu; Weigang Xu (Protoplasma, 2022)

The Chinese species of skipper butterflies in the tribe Tagiadini Mabille, 1878 (Lepidoptera: Hesperiidae): insights from phylogeny, hostplants, and biogeography - Li Shen; Jianqing Zhu; Yuxiang Lin; Jie Fang; Yongqiang Wang; Liying Tang; Qinghao Zhao; Mengqi Xiao; Feiyu Duan; Qunxiu Liu; Weidong Yu; Weibin Jiang (Organisms Diversity & Evolution, 2022)

Geochronology and structural deformation of Precambrian metamorphic basement in the eastern Jiangnan orogenic belt: constraints on the assembly time of the Yangtze and Cathaysia blocks - Yangyang Wang; Chuanzhong Song; Jiahao Li; Shoufa Lin; Zhenwei Li; Fang Yuan; Shenglian Ren (Earth Science Informatics, 2022)

A strategy for establishing an efficient somatic embryo regeneration system in Castanea mollissima Blume - Xiao-wei Li; Zhi-lin Sun; Yue-rong Gao; Jing-yi Ge; Yu-zhen Tian; Bing Liu; Shi-kan Sun; Ke-feng Fang; Ling Qin; Qing-qin Cao (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

Activation of the TREK-1 Potassium Channel Improved Cognitive Deficits in a Mouse Model of Alzheimer’s Disease by Modulating Glutamate Metabolism - Fang Li; Shu-ning Zhou; Xin Zeng; Zhen Li; Rui Yang; Xue-xi Wang; Bin Meng; Wei-lin Pei; Li Lu (Molecular Neurobiology, 2022)

Chemical and biological diversity of new natural products from marine sponges: a review (2009–2018) - Li-Li Hong; Ya-Fang Ding; Wei Zhang; Hou-Wen Lin (Marine Life Science & Technology, 2022)
Marine sponges are productive sources of bioactive secondary metabolites with over 200 new compounds isolated each year, contributing 23% of approved marine drugs so far. This review describes statistical research, structural diversity, and pharmacological activity of sponge derived new natural products from 2009 to 2018. Approximately 2762 new metabolites have been reported from 180 genera of sponges this decade, of which the main structural types are alkaloids and terpenoids, accounting for 50% of the total. More than half of new molecules showed biological activities including cytotoxic, antibacterial, antifungal, antiviral, anti-inflammatory, antioxidant, enzyme inhibition, and antimalarial activities. As summarized in this review, macrolides and peptides had higher proportions of new bioactive compounds in new compounds than other chemical classes. Every chemical class displayed cytotoxicity as the dominant activity. Alkaloids were the major contributors to antibacterial, antifungal, and antioxidant activities while steroids were primarily responsible for pest resistance activity. Alkaloids, terpenoids, and steroids displayed the most diverse biological activities. The statistic research of new compounds by published year, chemical class, sponge taxonomy, and biological activity are presented. Structural novelty and significant bioactivities of some representative compounds are highlighted. Marine sponges are rich sources of novel bioactive compounds and serve as animal hosts for microorganisms, highlighting the undisputed potential of sponges in the marine drugs research and development.

PLXDC2 enhances invadopodium formation to promote invasion and metastasis of gastric cancer cells via interacting with PTP1B - Bin Wu; Yan-xia Wang; Jun-jie Wang; Dong-fang Xiang; Meng-si Zhang; Ze-xuan Yan; Wen-ying Wang; Jing-ya Miao; Xi Lan; Jia-jia Liu; Zheng-yan Li; Chuan Li; et al. (Clinical & Experimental Metastasis, 2022)
Plexin-domain containing 2 (PLXDC2) has been reported as an oncoprotein in several human malignancies. However, its expression and roles in gastric cancer remain largely unclear. In this study, we found that PLXDC2 was highly expressed in gastric cancer tissues, and the expression levels were positively correlated with clinicopathological features, but negatively with the patients’ outcome. Cox regression analysis identified PLXDC2 as an independent prognostic indicator for the patients. Knockdown of PLXDC2 markedly suppressed the in vitro invasion and in vivo metastasis of gastric cancer cells, while overexpression of PLXDC2 resulted in opposite effects. Mechanistically, PLXDC2 enhanced the level of phosphorylated Cortactin (p-Cortactin) by physically interacting with protein tyrosine phosphatase 1B (PTP1B), an important dephosphorylase, to prevent its dephosphorylating of p-Cortactin, thereby promoting the formation of invadopodia. Collectively, our results indicate that PLXDC2 contributes to the invasion and metastasis of gastric cancer by inhibiting PTP1B to facilitate the invadopodium formation, and may serve as a potential prognostic biomarker and a therapeutic target for this disease.

Nematicidal activity of volatile organic compounds produced by Bacillus altitudinis AMCC 1040 against Meloidogyne incognita - Lin Ye; Jian-Yu Wang; Xiao-Fang Liu; Qi Guan; Nong-Xiao Dou; Jian Li; Qian Zhang; Yan-Ming Gao; Min Wang; Jian-She Li; Bo Zhou (Archives of Microbiology, 2022)

Halomonas salinarum sp. nov., a moderately halophilic bacterium isolated from saline soil in Yingkou, China - Ya-Lin Yin; Fang-Ling Li; Lei Wang (Archives of Microbiology, 2022)

Vertical patterns of chlorophyll a in the euphotic layer are related to mesoscale eddies in the South China Sea - Mei-Lin Wu; You-Shao Wang; Yu-Tu Wang; Fu-Lin Sun; Xiaomei Li; Fang-Fang Gu; Jing-Chang Xiang (Frontiers in Marine Science, 2022)
Phytoplankton closely connects with the hydrodynamics and biogeochemical environment of the ocean. While research focusing on both the physiochemical factors and hydrodynamics regulating phytoplankton has already been conducted, the coupling mechanism between mesoscale eddies and the vertical distribution of phyto plankton in the South China Sea (SCS) is still not well understood. Here, phytoplankton was studied under one weak-cold and two warm eddies along the 18°N transect in the SCS. The results show that the vertical distribution of chlorophyll (chl- a ) presented a similar pattern at all four sampling stations. The mixed layer is less than 50 m. It is the same as the meridional salinity gradients that may be distinguished above a depth of 60 m. The subsurface chlorophyll maximum at the edge of a warm (WI) and cold eddy (CI) at E413 and E411 was shallower than that at the edge of a warm eddy (WII) at E407 and E409, indicating that temperature and salinity may be the important driving factors. On the whole, mesoscale eddies had a significant influence on the vertical pattern of chl- a in the SCS during the study period.

Transcriptome study on immune response against Vibrio parahaemolyticus challenge in gill of abalone Haliotis discus hannai Ino - Yan Fang; Xiyun Yang; Shujuan Zhang; Xuyang Chen; Gang Lin; Yuqing Zhang; Mengjiao Wang; Mingzhu Li (Frontiers in Marine Science, 2022)
Abalone ( Haliotis discus hannai Ino) is one of the most vital economic shellfish cultured in China. However, bacterial and viral infection often leads to its high mortality and serious economic losses. In this study, transcriptome sequencing was performed on gill of abalone challenged by Vibrio parahaemolyticus for 0 h (control group, A0h), 8 h (A8h), and 48 h (A48h), respectively. Each library has an average of 53,361,675 clean reads. Approximately 85.71% reads were mapped to the reference genome of Haliotis discus hannai Ino. In comparison with A0h group, 7,656 and 2,789 genes were differentially expressed in the A8h and A48h groups, respectively. The differentially expressed genes (DEGs) were mostly enriched in oxidation–reduction process and oxidoreductase activity from GO analysis as well as immunity and metabolism-related pathways from Kyoto Encyclopedia of Genes and Genomes analysis. Cluster analysis demonstrated that all DEGs were categorized into eight subclusters by adopting the gene expression model. Specifically, a total of 1,070 significantly downregulated genes from two clusters were related to some metabolic pathways, ABC transporters, and cell adhesion. Moreover, 212 upregulated genes in one subcluster were enriched in several immune-related pathways, including nucleotide-binding oligomerization domain (NOD)-like receptor signaling pathway and apoptosis. Some members of the pattern recognition receptors family, which can initiate inflammatory signaling and induce apoptosis, were stimulated to upregulate in gill after challenge including C1q, perlucin, and low-density lipoprotein receptor–related protein. In addition, caspase-dependent apoptosis pathway was inactive, whereas caspase-independent apoptosis pathway was stimulating in response to Vibrio challenge. To eliminate invading pathogen, the immune effectors such as interleukin-17, matrix metalloproteinase, lysozyme, superoxide, and ferritin were also stimulated in gill. Moreover, this study also provides more information for comprehending the immunity and defense mechanisms against V. parahaemolyticus infection in abalone.

Three new sesquiterpene lactones from the whole plants of Elephantopus scaber - Ding-Chai Lin; Qing Tang; Xue-Fang Zhuo; Wen-Zhi Wang; Can-Jie Li; Guang-Kai Kuang; Zhong-Nan Wu; Yu-Bo Zhang; Guo-Cai Wang; Yao-Lan Li (Natural Product Research, 2022)

PPARγ Dysfunction in the Medial Prefrontal Cortex Mediates High-Fat Diet-Induced Depression - Cong-Cong Fu; Xin-Yi Zhang; Liu Xu; Hui-Xian Huang; Shuang Xu; Qiao-Qi Wu; Zhen Wang; Xi Gu; Li-Fang Lin; Song Lin; Ying-Ying Fang; Xiong Cao; et al. (Molecular Neurobiology, 2022)

Genetic Diversity Evaluation and Population Structure Analysis of Red Swamp Crayfish (Procambarus clarkii) from Lakes and Rice Fields by SSR Markers - Xin-Fen Guo; Min Liu; Yu-Lin Zhou; Wen-Yu Wei; Zhi Li; Li Zhou; Zhong-Wei Wang; Jian-Fang Gui (Fishes, 2022)
The red swamp crayfish (Procambarus clarkii) is an important aquatic animal and has developed as a popular aquaculture species in China. In this study, a total of 72,839 SSR motifs were identified from transcriptional data, and 20 microsatellite markers of them were finally developed to assess the genetic diversities of seven wild populations from natural lakes and nine cultured populations from rice fields. Genetic diversity was slightly higher in the cultured populations than in the wild populations. The degree of genetic differentiation between cultured populations is slight, while a moderate to a large degree of genetic differentiation between wild populations and most of the variations occurred within individuals (79%). The analysis of cluster, principal coordinate analysis and STRUCTURE were similar, and they showed that isolation-by-distance pattern was not significant. The microsatellite markers developed in this study can not only be used for genetic monitoring of population but also provide important information for the management of breeding and cultured population in red swamp crayfish.

Sandstorms cause shrinkage of Haloxylon ammodendron shrubs and limit their self-renewal - Sheng-bo Shi; Dang-wei Zhou; Fang-lin Wang; Rui Shi; Tao Sun; Tian-cai Li; Jia-lin Ma; Xiang Wan; Jian-ping Ma; Jing-nian Tang (Theoretical and Experimental Plant Physiology, 2022)
Haloxylon ammodendron is an excellent windproof and sand-fixing species whose shrubs are widely cultivated in arid desert areas of northwest China but are now at risk of degradation and shrinkage. Using the chlorophyll fluorescence image analysis technique, the response of photosystem II (PSII) photochemical efficiency and non-photochemical quenching capacity to sediment-carrying wind and sand-free wind (both 12 m s −1 ) lasting for 10, 20, and 40 min were studied with seedlings in a wind tunnel. The results indicated that the sand-free wind had little influence on the maximum quantum efficiency of PSII photochemistry, F v / F m , which was approximately 0.80 on average; however, the F v / F m decreased over exposure time in the sediment-carrying wind group, with values smaller than those in the wind-only group. The non-photochemical quenching was sensitive to wind erosion, and sediment-carrying wind could aggravate the reduction in non-photochemical quenching ( NPQ ). Except for the 10 min duration, the maximum quantum efficiency of PSII photochemistry after dark recovery for 15 min, F v r / F m r , was lower in seedlings exposed to sediment-carrying wind than in those in the wind-only group. Compared to wind-only, wind-blown sand led to a water imbalance and withering in seedlings, causing the concentration of photosynthetic pigments (when based on the fresh mass of green branches) to not decrease. With a longer exposure time to sediment-carrying wind, both the probability and extent of lignified spots occurring increased in green assimilative branches. Our results demonstrated that sediment-carrying wind at 12 m s −1 lasting for 20 min or more could cause irreversible damage to the photosynthetic apparatus of H. ammodendron seedlings. Therefore, frequent and strong sandstorms are the main disturbance factors leading to shrinkage of shrubs and limiting their self-renewal.

Combined System of Organic Substrate and Straw-Degrading Microbial Agents Improved Soil Organic Matter Levels and Microbial Abundance in a Rice–Wheat Rotation - Shi-Li Song; Xue Luo; Hao Wu; Xiao-Lin Lu; Fang-Ji Xu; Zhen-Hua Zhang; Yong-Xiang Guan; Chuan-Chao Dai (Current Microbiology, 2022)

Optimization of aquaculture sustainability through ecological intensification in China - Shuang‐lin Dong; Yun‐wei Dong; Ling Cao; Johan Verreth; Yngvar Olsen; Wen‐jing Liu; Qi‐zhi Fang; Yan‐gen Zhou; Li Li; Jing‐yu Li; Yong‐tong Mu; Patrick Sorgeloos (Reviews in Aquaculture, 2022)
As the world's leading producer of farmed aquatic food products, China faces great uncertainty concerning the further sustainable development of its aquaculture industry due to high and increasing pressure from environmental and resource constraints. To realize truly sustainable development, it is imperative to establish an evaluation system that integrates social, economic, environmental and resource criteria, and optimizes aquaculture systems through a holistic approach. Here, we used analytical hierarchy processes combined with expert judgment and objective data to assess the sustainability of 10 major aquaculture production systems (APSs) in China. Based on the evaluation results, we propose the ecological intensification of aquaculture systems (ELIAS), rationally integrating anthropogenic inputs with aquaculture ecosystem services, to improve the sustainability of APSs. The holistic evaluation system and ELIAS are fundamental and critical for the future development of aquaculture in China and globally.

Cover Image, Volume 14, Issue 3 - Shuang‐lin Dong; Yun‐wei Dong; Ling Cao; Johan Verreth; Yngvar Olsen; Wen‐jing Liu; Qi‐zhi Fang; Yan‐gen Zhou; Li Li; Jing‐yu Li; Yong‐tong Mu; Patrick Sorgeloos (Reviews in Aquaculture, 2022)
The cover image is based on the Review Article Optimization of aquaculture sustainability through ecological intensification in China by Shuang‐lin Dong et al., https://doi.org/10.1111/raq.12648 image

Pollution characteristics and emissions of typical organophosphate esters of a wastewater treatment plant - Hongling Yin; Yi Luo; Jiaojiao Song; Shiping Li; Shuyu Lin; Yuanming Xiong; Shuhong Fang; Juan Tang (Environmental Science and Pollution Research, 2022)

Research on gas diffusion of natural gas leakage based on Gaussian plume model - Binbin Wang; Liqiong Chen; Wanxin Lin; Dongrong Wu; Yingchao Fang; Zhao Li (Arabian Journal of Geosciences, 2022)

Preparation and In Vitro and In Vivo Evaluation of a Testosterone Film Forming Gel for the Treatment of Hypoactive Sexual Desire Disorder in Women - Jia Zeng; Tan-Fang Xie; Ting Huang; Fang Li; Zhi-Ping Wang; Ling-Lin Feng (AAPS PharmSciTech, 2022)

Transcriptomic analyses provide insight into adventitious root formation of Euryodendron excelsum H. T. Chang during ex vitro rooting - Yuping Xiong; Shuangyan Chen; Zhenpeng Wei; Xiaohong Chen; Beiyi Guo; Ting Zhang; Yuying Yin; Xincheng Yu; Jinhui Pang; Meiyun Niu; Xinhua Zhang; Yuan Li; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

Identification of epigenetic modifications mediating the antagonistic effect of selenium against cadmium-induced breast carcinogenesis - Zhuo-Zhi Liang; Yi-Xin Zhang; Rui-Mei Zhu; Yue-Lin Li; Hong-Mei Jiang; Ruo-Bi Li; Qian-Xin Chen; Qing Wang; Lu-Ying Tang; Ze-Fang Ren (Environmental Science and Pollution Research, 2022)

Demersal fish diversity and molecular taxonomy in the Bering Sea and Chukchi Sea - Hai Li; Fang Yang; Xuehua Wang; Yuan Li; Nan Zhang; Ran Zhang; Cheng Liu; Hushun Zhang; Longshan Lin; Puqing Song (Conservation Genetics Resources, 2022)

Impact of Gibberellin Treatment on the Growth and Nutrient Condition of Vallisneria natans (Lour.) Hara in Substrate with Various Fertility - Baozhu Zhang; Yuanxin Li; Zhangjian Liu; Clare Fuya Auld-Brokish; Marek Kolenčík; Yuhong Fang; Yishuai Lin; Yu Qian (Water, Air, & Soil Pollution, 2022)

Oxygen Metabolism-induced Stress Response Underlies Heart–brain Interaction Governing Human Consciousness-breaking and Attention - Xiao-Juan Xue; Rui Su; Ze-Feng Li; Xiao-Ou Bu; Peng Dang; Si-Fang Yu; Zhi-Xin Wang; Dong-Mei Chen; Tong-Ao Zeng; Ming Liu; Hai-Lin Ma; De-Long Zhang (Neuroscience Bulletin, 2022)

Interferon-induced transmembrane protein 2 promotes epithelial-mesenchymal transition by activating transforming growth factor-β1/small mother against decapentaplegic 2 signaling in gastric cancer - Yonggang Liu; Minyu Zhou; Jianhua Wu; Zhaowei Wen; Yisheng Fang; Li Lin; Meihua Luo; Li Sun; Wangjun Liao (Molecular Biology Reports, 2022)

Identification and bioinformatics analysis of differentially expressed milk exosomal microRNAs in milk exosomes of heat-stressed Holstein cows - Yue Wang; Jian Fang; Han-Fang Zeng; Ji-Feng Zhong; Hui-Xia Li; Kun-Lin Chen (Functional & Integrative Genomics, 2022)

Detection of pulmonary tuberculosis in children using the Xpert MTB/RIF Ultra assay on sputum: a multicenter study - Xiaoshan Peng; Qiong Liao; Min Fang; Yu Zhu; Yan Shi; Shuting Quan; Yacui Wang; Li Duan; Xiaomei Shi; Yang Liu; Manzhi Wang; Qingsong Wei; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2022)

Advenella mandrilli sp. nov., a bacterium isolated from the faeces of Mandrillus sphinx - Qiong Wang; Xiu-Lin Han; Zhi-Qin Fang; Chen-Lu Zhang; Chun Li; Tao Lu (Antonie van Leeuwenhoek, 2022)

Performance and mechanisms of fly ash for graphene oxide removal from aqueous solution - Ping Jiang; Lin Zhou; Wei Wang; Na Li; Fang Zhang (Environmental Science and Pollution Research, 2022)

Bioactive compounds derived from the marine-derived fungus MCCC3A00951 and their influenza neuraminidase inhibition activity in vitro and in silico - Shun-Zhi Liu; Feng-Ming He; Yan-lin Bin; Chu-Fang Li; Bao-Ying Xie; Xi-Xiang Tang; Ying-Kun Qiu (Natural Product Research, 2021)

Characterization on the P-associated and agronomic traits as well as associated molecular processes in wheat under Pi deprivation condition - Ying-Jia Zhao; Xin-Yang Bai; Rui-Ze Lin; Fang-fang Li; Kai Xiao (Plant Cell, Tissue and Organ Culture (PCTOC), 2021)

Serum Neurofilament Light: a Potential Diagnostic and Prognostic Biomarker in Obstetric Posterior Reversible Encephalopathy Syndrome - Xiaobo Fang; Yanling Liang; Weixi Zhang; Qiong Wang; Jingsi Chen; Jia Chen; Yongqiang Lin; Yanli Chen; Li Yu; Haibin Wang; Dunjin Chen (Molecular Neurobiology, 2021)

External evaluation of published population pharmacokinetic models of polymyxin B - Ya-qian Li; Kai-feng Chen; Jun-jie Ding; Hong-yi Tan; Nan Yang; Ya-qi Lin; Cui-fang Wu; Yue-liang Xie; Guo-ping Yang; Jing-Jing Liu; Qi Pei (European Journal of Clinical Pharmacology, 2021)

Sodium P-aminosalicylic Acid Attenuates Manganese-Induced Neuroinflammation in BV2 Microglia by Modulating NF-κB Pathway - Junyan Li; Yue Deng; Dongjie Peng; Lin Zhao; Yuanyuan Fang; Xiaojuan Zhu; Shaojun Li; Michael Aschner; Shiyan Ou; Yueming Jiang (Biological Trace Element Research, 2021)

Identification and Characterization of Gene SpDMRT99B and Its Sex-Biased Expression Profile in the Mud Crab, Scylla paramamosain - Yin Zhang; Shaobin Fang; Fei Lin; Shengkang Li; Huaiping Zheng; Yueling Zhang; Mhd Ikhwanuddin; Hongyu Ma (Journal of Ocean University of China, 2021)

Identification and antimicrobial properties of a new alkaloid produced by marine-derived Verrucosispora sp. FIM06-0036 - Ming-Hong Chen; Yun-Yang Lian; Dong-Sheng Fang; Li Chen; Jia Jia; Wen-Long Zhang; Ru Lin; Yang Xie; Hong-Kai Bi; Hong Jiang (Natural Product Research, 2021)

Strategies of cadmium and copper uptake and translocation in different plant species growing near an E-waste dismantling site at Wenling, China - Jiao Jiao Li; Xue Qiang Zhao; Jia Lin Wang; Ren Fang Shen (Environmental Science and Pollution Research, 2021)

MS1 is essential for male fertility by regulating the microsporocyte cell plate expansion in soybean - Xiaolong Fang; Xiaoyuan Sun; Xiangdong Yang; Qing Li; Chunjing Lin; Jie Xu; Wenjun Gong; Yifan Wang; Lu Liu; Limei Zhao; Baohui Liu; Jun Qin; et al. (Science China Life Sciences, 2021)

Sodium P-aminosalicylic Acid Inhibits Manganese-Induced Neuroinflammation in BV2 Microglial Cells via NLRP3-CASP1 Inflammasome Pathway - Yuanyuan Fang; Dongjie Peng; Yuan Liang; Lili Lu; Junyan Li; Lin Zhao; Shiyan Ou; Shaojun Li; Michael Aschner; Yueming Jiang (Biological Trace Element Research, 2021)

Genipin Attenuates Tau Phosphorylation and Aβ Levels in Cellular Models of Alzheimer’s Disease - Meiting Li; Nan Cai; Liang Gu; Lijun Yao; Decheng Bi; Weishan Fang; Zhijian Lin; Yan Wu; Hong Xu; Hui Li; Zhangli Hu; Xu Xu (Molecular Neurobiology, 2021)

RSF1 requires CEBP/β and hSNF2H to promote IL-1β-mediated angiogenesis: the clinical and therapeutic relevance of RSF1 overexpression and amplification in myxofibrosarcomas - Chien-Feng Li; Ti-Chen Chan; Cheng-I. Wang; Fu-Min Fang; Po-Chun Lin; Shih-Chen Yu; Hsuan-Ying Huang (Angiogenesis, 2021)

Soil Bacterial Characteristics Under Four Habitats with Different Vegetation Communities on the Qinghai-Tibetan Plateau - Rui Wang; Miao Wang; Jing Wang; Jiahe Yao; Xinwei Li; Yinghua Lin; Fang K. Du (Wetlands, 2021)

Five matrine-type alkaloids from Sophora tonkinensis - Qing Tang; Ding Luo; Ding-Chai Lin; Wen-Zhi Wang; Can-Jie Li; Xue-Fang Zhuo; Zhong-Nan Wu; Yu-Bo Zhang; Guo-Cai Wang; Yao-Lan Li (Journal of Natural Medicines, 2021)

Dynamic Anthropometrics of Preschool Children in Taiwan for Playground Equipment Designs - I-Fang Cheng; Chien-Ju Lin; Li-Chieh Kuo; Bih-Jen Hsue; Fong-Chin Su (Journal of Medical and Biological Engineering, 2021)

Effects of multi-phase inoculation on the fungal community related with the improvement of medicinal herbal residues composting - Xiao-Lin Lu; Hao Wu; Shi-Li Song; Hong-Yan Bai; Meng-Jun Tang; Fang-Ji Xu; Yan Ma; Chuan-Chao Dai; Yong Jia (Environmental Science and Pollution Research, 2021)

Identification of two UDP-glycosyltransferases involved in the main oleanane-type ginsenosides in Panax japonicus var. major - Jun-Rong Tang; Geng Chen; Ying-Chun Lu; Qing-Yan Tang; Wan-Ling Song; Yuan Lin; Ying Li; Su-Fang Peng; Sheng-Chao Yang; Guang-Hui Zhang; Bing Hao (Planta, 2021)

Restraint of Bagging on Fruit Skin Coloration in on-Tree Kiwifruit (Actinidia arguta) - Yukuo Li; Xiujuan Qi; Wen Cui; Miaomiao Lin; Chengkui Qiao; Yunpeng Zhong; Jinbao Fang; Chungen Hu (Journal of Plant Growth Regulation, 2021)

Increased depression risk for elderly women with high blood levels of strontium and barium - Jia Lv; Yan-ling Li; Wen-qiang Ren; Rong Li; Jian-rong Chen; Chao Bao; Zhi-ping Du; Shun Feng; Ling Gu; Hui Gao; Kai-yong Liu; Lin-sheng Yang; et al. (Environmental Chemistry Letters, 2021)

Crenobacter intestini sp. nov., Isolated from the Intestinal Tract of Konosirus punctatus - Song-Biao Shi; Jia-Fa Wu; Li-Fang Yang; Ming-Guo Jiang; Cai-Mi Gao; Cheng-Lin Jiang; Yi Jiang (Current Microbiology, 2021)

Biopharmaceutics Applications of Physiologically Based Pharmacokinetic Absorption Modeling and Simulation in Regulatory Submissions to the U.S. Food and Drug Administration for New Drugs - Fang Wu; Heta Shah; Min Li; Peng Duan; Ping Zhao; Sandra Suarez; Kimberly Raines; Yang Zhao; Meng Wang; Ho-pi Lin; John Duan; Lawrence Yu; et al. (The AAPS Journal, 2021)

RING-finger protein 5 promotes hepatocellular carcinoma progression and predicts poor prognosis - Yi Zhang; Jie Li; Huayang Chen; Changmao Zhang; Song You; Yue Zhao; Xiaoning Lin; Yaqi Yu; Fei Fang; Ting Fang; Xiaomin Wang (Human Cell, 2021)

Effects of degradation succession of alpine wetland on soil organic carbon and total nitrogen in the Yellow River source zone, west China - Chun-ying Lin; Xi-lai Li; Jing Zhang; Hua-fang Sun; Juan Zhang; Hui-bang Han; Qi-hua Wang; Cheng-biao Ma; Cheng-yi Li; Yu-xing Zhang; Xue-qian Ma (Journal of Mountain Science, 2021)

Prevalence and outcomes of re-positive nucleic acid tests in discharged COVID-19 patients - Hou-wei Du; Jun-nian Chen; Xiao-bin Pan; Xiao-ling Chen; Yixian-Zhang; Shuang-fang Fang; Xiao-qing Li; Pin-cang Xia; Lei Gao; Hai-long Lin; Li-min Chen; Nan Liu (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Land use and land cover change within the Koshi River Basin of the central Himalayas since 1990 - Fang-di Xie; Xue Wu; Lin-shan Liu; Yi-li Zhang; Basanta Paudel (Journal of Mountain Science, 2021)

Isolation and characterization of two new chroman-4-ones from the endophytic fungus Penicillium chrysogenum obtained from Eucommia ulmoides Oliver - Sheng-Yue Liu; Li-Zhi Wang; Yue-Fei Wang; Lin Li; Guo-Ying Han; Bing-Yang Zhang; Ying Guo; Yong-Zhi He; Shi-Ming Fang; Han Zhang (Natural Product Research, 2020)

AMPK Ameliorates Tau Acetylation and Memory Impairment Through Sirt1 - Lin Wang; Fang-Xiao Shi; Na Li; Yun Cao; Ying Lei; Jian-Zhi Wang; Qing Tian; Xin-Wen Zhou (Molecular Neurobiology, 2020)

Valine acts as a nutritional signal in brain to activate TORC1 and attenuate postprandial ammonia-N excretion in Chinese perch (Siniperca chuatsi) - Jie Wang; Xu-Fang Liang; Shan He; Yan-Peng Zhang; Jiao Li; Kang Huang; Lin-Jie Shi; Ping Ren (Fish Physiology and Biochemistry, 2020)

Relationship Between Plasma Copper Concentration and Body Fat Distribution in Children in China: a Cross-Sectional Study - Jingjing Liang; Fengyan Chen; Guoqing Fang; Xin Zhang; Yan Li; Bingjie Ma; Suifang Lin; Jialiang Pan; Zheqing Zhang (Biological Trace Element Research, 2020)

Greater promotion of DNRA rates and nrfA gene transcriptional activity by straw incorporation in alkaline than in acidic paddy soils - Ren Bai; Yun-Ting Fang; Liu-Ying Mo; Ju-Pei Shen; Lin-Lin Song; Ya-Qi Wang; Li-Mei Zhang; Ji-Zheng He (Soil Ecology Letters, 2020)

Transcriptome analysis of strawberry fruit in response to exogenous arginine - Jinhua Lv; Qianqian Pang; Xueqin Chen; Teng Li; Jinggui Fang; Shaoyan Lin; Haifeng Jia (Planta, 2020)

Activation of p62-Keap1-Nrf2 Pathway Protects 6-Hydroxydopamine-Induced Ferroptosis in Dopaminergic Cells - Yiran Sun; Libo He; Taoyu Wang; Wan Hua; Huan Qin; Jingjin Wang; Li Wang; Wanqin Gu; Tingting Li; Na Li; Xinanbei Liu; Fang Chen; et al. (Molecular Neurobiology, 2020)

Complete genome sequence of a novel recombinant avian leukosis virus isolated from a three-yellow chicken - Tao Sun; Ximei Wang; Wei Han; Xiaoling Ma; Weili Yin; Baohai Fang; Xiao Lin; Yang Li (Archives of Virology, 2020)

Comparative analysis of physiological traits of three Actinidia valvata Dunn genotypes during waterlogging and post-waterlogging recovery - Zhi Li; Yunpeng Zhong; Danfeng Bai; Miaomiao Lin; Xiujuan Qi; Jinbao Fang (Horticulture, Environment, and Biotechnology, 2020)

Sodium Para-aminosalicylic Acid Reverses Changes of Glutamate Turnover in Manganese-Exposed Rats - Zhao-Cong Li; Fang Wang; Shao-Jun Li; Lin Zhao; Jun-Yan Li; Yue Deng; Xiao-Juan Zhu; Yu-Wen Zhang; Dong-Jie Peng; Yue-Ming Jiang (Biological Trace Element Research, 2020)

Simulation of oyster ecological carrying capacity in Sanggou Bay in the ecosystem context - Yaping Gao; Jianguang Fang; Fan Lin; Fengxue Li; Wenhao Li; Xiaoqin Wang; Meirong Du; Jinghui Fang; Weiwei Jiang; Hui Liu; Yitao Zhang; Junwei Wang; et al. (Aquaculture International, 2020)

Upregulation of AMPK Ameliorates Alzheimer’s Disease-Like Tau Pathology and Memory Impairment - Lin Wang; Na Li; Fang-Xiao Shi; Wei-Qi Xu; Yun Cao; Ying Lei; Jian-Zhi Wang; Qing Tian; Xin-Wen Zhou (Molecular Neurobiology, 2020)

Interferon-α2b spray inhalation did not shorten virus shedding time of SARS-CoV-2 in hospitalized patients: a preliminary matched case-control study - Shao-rui Hao; Ren Yan; Shan-yan Zhang; Jiang-shan Lian; Huan Cai; Xiao-li Zhang; Lin Zheng; Hong-yu Jia; Jian-hua Hu; Guo-dong Yu; Jue-qing Gu; Chan-yuan Ye; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Different experiences of two PRRT2-associated self-limited familial infantile epilepsy - Qianlei Zhao; Zhenwei Liu; Ying Hu; Shiyu Fang; Feixia Zheng; Xiucui Li; Feng Li; Zhongdong Lin (Acta Neurologica Belgica, 2020)
To analyze the clinical characteristics and PRRT2 gene mutation of self-limited familial infantile epilepsy and evaluate the treatment responses of different antiepileptic drugs in self-limited familial infantile epilepsy. We reviewed the clinical feature and genetic mutation results and treatment responses of two sibling sisters. They were detected with the PRRT2 gene mutation through Sanger sequencing. Elder sister was treated with oxcarbazepine oral suspension, while younger sister was treated with levetiracetam oral solution. The two sibling sisters exhibited PRRT2 heterozygous mutation inherited from their mother in c.649dupC p.(Arg217fs). Oxcarbazepine oral suspension had an immediate effect on the elder sister who was treated with it. However, levetiracetam oral solution had no effect on younger sister even though the dose was increased, but she got seizure-free after turning to oxcarbazepine oral suspension. Oxcarbazepine, which plays the mechanism of the sodium channel blockers, has a more significant effect than levetiracetam, which has no mechanism of the sodium channel blockers in self-limited familial infantile epilepsy. The PRRT2 gene of infantile epileptic patients with a family history of infantile convulsions or paroxysmal kinesigenic dyskinesia(PKD) could be detected by sanger sequencing and a biomarker to select antiepileptic drugs which play the mechanism of the sodium channel blockers could be utilized.

Gelsemine, a natural alkaloid extracted from Gelsemium elegans Benth. alleviates neuroinflammation and cognitive impairments in Aβ oligomer-treated mice - Liping Chen; Hanbo Pan; Yujing Bai; Huiqin Li; Wen Yang; Zhi-Xiu Lin; Wei Cui; Yan-Fang Xian (Psychopharmacology, 2020)

Detection of serum IgM and IgG for COVID-19 diagnosis - Ling Zhong; Junlan Chuan; Bo Gong; Ping Shuai; Yu Zhou; Yi Zhang; Zhilin Jiang; Dingding Zhang; Xiaoqi Liu; Shi Ma; Yi Huang; He Lin; et al. (Science China Life Sciences, 2020)

Comparison of epidemiological and clinical characteristics of COVID-19 patients with and without Wuhan exposure - Jiang-shan Lian; Huan Cai; Shao-rui Hao; Xi Jin; Xiao-li Zhang; Lin Zheng; Hong-yu Jia; Jian-hua Hu; Shan-yan Zhang; Guo-dong Yu; Jue-qing Gu; Chan-yuan Ye; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Liver X receptor activation induces podocyte injury via inhibiting autophagic activity - Ziyi Zhang; Shengjie Tang; Weiwei Gui; Xihua Lin; Fenping Zheng; Fang Wu; Hong Li (Journal of Physiology and Biochemistry, 2020)

Nanochemoprevention with therapeutic benefits: An updated review focused on epigallocatechin gallate delivery - Qiong-Qiong Yang; Xin-Lin Wei; Ya-Peng Fang; Ren-You Gan; Min Wang; Ying-Ying Ge; Dan Zhang; Li-Zeng Cheng; Harold Corke (Critical Reviews in Food Science and Nutrition, 2020)

Association Between the Polymorphism of Aldehyde Dehydrogenase 2 Gene and Cerebral Infarction in a Hakka Population in Southern China - Jing-yuan Hou; Zhi-xiong Zhong; Qiao-ting Deng; Su-dong Liu; Li-fang Lin (Biochemical Genetics, 2020)

Protective Effect of (−)Epigallocatechin-3-gallate on Rotenone-Induced Parkinsonism-like Symptoms in Rats - Hsiang-Chien Tseng; Mao-Hsien Wang; Kuo-Chi Chang; Hung-Sheng Soung; Chih-Hsiang Fang; Yi-Wen Lin; Keng-Yuan Li; Chih-Chuan Yang; Cheng-Chia Tsai (Neurotoxicity Research, 2020)

Hostaflavanol A, a new anti-inflammatory and antioxidant activities flavanol from the flowers of Hosta plantaginea - Li Yang; Yi-min Lin; Zhong-wei He; Ting-fang Zhang; Yu Li; Xiao-tong Xie; Yi-feng Wu; Jun-wei He (Medicinal Chemistry Research, 2020)

(±)-Quassidine K, a pair of cytotoxic bis- β -carboline alkaloid enantiomers from Picrasma quassioides - Xin-Ming Guo; Fei Li; Fang-Fang Zheng; Na-Na Gong; Yan Li; Wen-Zhou Feng; Lin Tian (Natural Product Research, 2020)

Metabolome and transcriptome profiling reveals quality variation and underlying regulation of three ecotypes for Cistanche deserticola - Xiao Sun; Lin Li; Jin Pei; Chang Liu; Lin-Fang Huang (Plant Molecular Biology, 2020)

Simulation of Yesso scallop, Patinopecten yessoensis, growth with a dynamic energy budget (DEB) model in the mariculture area of Zhangzidao Island - Weiwei Jiang; Fan Lin; Meirong Du; Jianguang Fang; Jinghui Fang; Yaping Gao; Xiaoqin Wang; Fengxue Li; Shipeng Dong; Xing Hou; Zengjie Jiang (Aquaculture International, 2020)

The Arabidopsis kinase-associated protein phosphatase KAPP, interacting with protein kinases SnRK2.2/2.3/2.6, negatively regulates abscisic acid signaling - Kai Lu; Ya-Dong Zhang; Chun-Fang Zhao; Li-Hui Zhou; Qing-Yong Zhao; Tao Chen; Cai-Lin Wang (Plant Molecular Biology, 2020)

Agrobacterium-mediated genetic transformation of Chinese chestnut (Castanea mollissima Blume) - Zhi-lin Sun; Xiao Li; Wan Zhou; Jun-di Yan; Yue-rong Gao; Xiao-wei Li; Jia-chen Sun; Ke-feng Fang; Qing Zhang; Yu Xing; Ling Qin; Qing-qin Cao (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)
Chinese chestnut ( Castanea mollissima ) is an important germplasm resource for the breeding of Castanea species worldwide with vital ecological and economic value. Biotechnology overcomes the limitations of traditional breeding and accelerates germplasm improvement. However, a genetic transformation system for Chinese chestnut has not yet been established. In this study, a stable and efficient Agrobacterium -mediated genetic transformation method for Chinese chestnut is described. Embryogenic calli of C. mollissima cv. ‘Yanshanhongli’ were used as the target material. The sensitivity of embryogenic calli to kanamycin was determined, whereby the proliferation of non-transformed calli was completely inhibited at 180 mg/L. Antibiotic inhibition results for Chinese chestnut embryogenic calli showed that 50 mg/L cefotaxime and 500 μM timentin completely inhibited the growth of Agrobacterium tumefaciens but did not affect the normal growth of Chinese chestnut embryogenic calli. When embryogenic calli were co-cultured for 2 days with Agrobacterium tumefaciens strain AGL1 harboring the PBI121-EGFP plasmid, an embryogenic callus transformation efficiency of 4.55% was obtained, and two transgenic chimera were acquired. This Agrobacterium -mediated transformation system for Chinese chestnut provides a fundamental platform for genetic improvement of core germplasm and for further verification of gene function.

Quantitatively ranking the influencing factors of ammonia volatilization from paddy soils by grey relational entropy - Wen-Ming Xie; Shi-Jun Li; Wei-Ming Shi; Hai-Lin Zhang; Fang Fang; Guo-Xiang Wang; Li-Min Zhang (Environmental Science and Pollution Research, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Bifidobacterium bifidum TMC3115 Can Characteristically Influence Glucose and Lipid Profile and Intestinal Microbiota in the Middle-Aged and Elderly - Ke Wang; Xiaohong Yu; Yi Li; Yun Guo; Lin Ge; Fangfang Pu; Xinying Ma; Wenjing Cui; Francesco Marrota; Fang He; Ming Li (Probiotics and Antimicrobial Proteins, 2019)

Characteristics and Prognosis of Talaromyces marneffei Infection in Non-HIV-Infected Children in Southern China - Jing Guo; Bing-Kun Li; Tian-Min Li; Fang-Lin Wei; Yu-Jiao Fu; Yan-Qing Zheng; Kai-Su Pan; Chun-Yang Huang; Cun-Wei Cao (Mycopathologia, 2019)

Model test for water inrush caused by karst caves filled with confined water in tunnels - Weimin Yang; Xin Yang; Zhongdong Fang; Shaoshuai Shi; Hao Wang; Lin Bu; Liping Li; Zongqing Zhou (Arabian Journal of Geosciences, 2019)

Expression of AHI1 Rescues Amyloidogenic Pathology in Alzheimer’s Disease Model Cells - Lai-Lei Ting; Hsien-Tsung Lu; Shu-Fen Yen; Thi Huong Ngo; Fang-Yu Tu; I-Shih Tsai; Yi-Hua Tsai; Fu-Yen Chang; Xiao-Jiang Li; Shihua Li; Ching-Kuo Lee; Shu-Huei Kao; et al. (Molecular Neurobiology, 2019)

Insights into transcriptional characteristics and homoeolog expression bias of embryo and de-embryonated kernels in developing grain through RNA-Seq and Iso-Seq - Jun Wei; Hong Cao; Jing-dong Liu; Jing-hong Zuo; Yu Fang; Chih-Ta Lin; Run-ze Sun; Wen-long Li; Yong-xiu Liu (Functional & Integrative Genomics, 2019)

A new phenolic glycoside from the Idesia polycarpa Maxim. leaves - Lei Huang; Tong Peng; Yu Li; Yunyun He; Li Wang; Shiyan Zhang; Yiran Sun; Fang Chen; Lin Tang (Natural Product Research, 2019)

Isolation, purification and identification of two new alkaloids metabolites from marine-derived Verrucosispora sp. FIM06025 - Ming-Hong Chen; Wen-Long Zhang; Li Chen; Ru Lin; Yang Xie; Dong-Sheng Fang; Yun-Yang Lian; Hong Jiang (Natural Product Research, 2019)

Resource (Light and Nitrogen) and Density-Dependence of Seaweed Growth - Xi Xiao; Susana Agusti; Fang Lin; Caicai Xu; Yan Yu; Yaoru Pan; Ke Li; Jiaping Wu; Carlos M. Duarte (Frontiers in Marine Science, 2019)

X-linked hyper-IgM syndrome complicated with interstitial pneumonia and liver injury: a new mutation locus in the CD40LG gene - Tian-Jiao Wang; Li-Fang Wu; Junguo Chen; Wen Zhu; Hua Wang; Xiao-Lin Liu; Yi-Qun Teng (Immunologic Research, 2019)

Shallow Genetic Structure of Pholis fangi in Bohai Sea and Yellow Sea Inferred from mtDNA Control Region - Tianxiang Gao; Lin Li; Rundong Fang; Guanghui Liu; Lei Wang; Hanxiang Xu; Na Song (Journal of Ocean University of China, 2019)

Ottowia flava sp. nov., isolated from fish intestines - Song-Biao Shi; Gui-Ding Li; Li-Fang Yang; Cong Liu; Ming-Guo Jiang; Qin-Yuan Li; Jia-Fa Wu; Kun Zhang; Long-Qian Jiang; Nai-Kun Shen; Cheng-Lin Jiang; Yi Jiang (Antonie van Leeuwenhoek, 2019)

Rab18 Collaborates with Rab7 to Modulate Lysosomal and Autophagy Activities in the Nervous System: an Overlapping Mechanism for Warburg Micro Syndrome and Charcot-Marie-Tooth Neuropathy Type 2B - Fang-Shin Nian; Lei-Li Li; Chih-Ya Cheng; Pei-Chun Wu; You-Tai Lin; Cheng-Yung Tang; Bo-Shiun Ren; Chin-Yin Tai; Ming-Ji Fann; Lung-Sen Kao; Chen-Jee Hong; Jin-Wu Tsai (Molecular Neurobiology, 2019)

Correction to: Antidepressant-Like Action of Single Facial Injection of Botulinum Neurotoxin A is Associated with Augmented 5-HT Levels and BDNF/ERK/CREB Pathways in Mouse Brain - Yang Li; Jing Liu; Xu Liu; Cun-Jin Su; Qi-Lin Zhang; Zhi-Hong Wang; Lei-Fang Cao; Xue-Yan Guo; Ya Huang; Weifeng Luo; Tong Liu (Neuroscience Bulletin, 2019)

Antidepressant-Like Action of Single Facial Injection of Botulinum Neurotoxin A is Associated with Augmented 5-HT Levels and BDNF/ERK/CREB Pathways in Mouse Brain - Yang Li; Jing Liu; Xu Liu; Cun-Jin Su; Qi-Lin Zhang; Zhi-Hong Wang; Lei-Fang Cao; Xue-Yan Guo; Ya Huang; Weifeng Luo; Tong Liu (Neuroscience Bulletin, 2019)

Comparative Transcriptome Analysis Reveals Differentially Expressed Genes and Signaling Pathways Between Male and Female Red-Tail Catfish (Mystus wyckioides) - Jun-Jie Wu; Yu-Lin Zhou; Zhong-Wei Wang; Guang-Hua Li; Fang-Peng Jin; Li-Li Cui; Hai-Tao Gao; Xin-Ping Li; Li Zhou; Jian-Fang Gui (Marine Biotechnology, 2019)

Anthropometric Database of the Preschool Children from 2 to 6 Years in Taiwan - I-Fang Cheng; Li-Chieh Kuo; Chien-Ju Lin; Hsiao-Feng Chieh; Fong-Chin Su (Journal of Medical and Biological Engineering, 2019)

Quadruplex PCR detection of three quarantine Phytophthora pathogens of berries - Fang Liao; Guo-Ming Huang; Lin-Hui Zhu; Dajin Lv; Doudou Zhang; Jia-Feng Luo; Guan-Rong Li (European Journal of Plant Pathology, 2019)

Evaluation of the eco-efficiency of four major urban agglomerations in coastal eastern China - Yufei Ren; Chuangling Fang; Xueqin Lin; Siao Sun; Guangdong Li; Beili Fan (Journal of Geographical Sciences, 2019)

The analysis of clinical and laboratory data: a large outbreak of dengue fever in Chaozhou, Guangdong province, China - Fen Lin; Hui Yang; Lin Zhang; Sen-Hai Fang; Xiao-Fen Zhan; Li-Ye Yang (Archives of Virology, 2019)

Environment‐ and trait‐mediated scaling of tree occupancy in forests worldwide - Haibao Ren; Petr Keil; Xiangcheng Mi; Keping Ma; Zhanqing Hao; Wanhui Ye; Luxiang Lin; Renato Valencia; Christine Dawn Fletcher; Duncan W. Thomas; Robert W. Howe; James Lutz; et al. (Global Ecology and Biogeography, 2019)
Aim The relationship between the proportion of sites occupied by a species and the area of a site [occupancy–area relationship (OAR)] offers key information for biodiversity management and has long fascinated ecologists. We quantified the variation in OAR for 3,157 woody species in 17 forest plots worldwide and tested the relative importance of environment and species traits for explaining this variation and evaluated overall model predictive ability. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We used mixed‐effect regression to examine the observed shape of the OAR (its “slope”) against species‐specific and plot‐wide predictors: coarse‐grain occupancy, tree size, plot species richness, energy availability and topographic complexity. Results We found large variation in OAR slopes, and the variation was strongest among species within plots. The OAR slopes showed a latitudinal trend and were steeper near the equator. As predicted, coarse‐grain occupancy and tree size negatively affected OAR slopes, whereas species richness had a positive effect and explained most of the variance between plots. Although hypothesized directionalities were broadly confirmed, traits and environment had relatively limited overall predictive power. Main conclusions These results document the variation of the OAR for 3,157 species at near‐global extent. We found a latitudinal gradient in OAR slopes and confirmed key hypothesized predictors. But at this global extent and over the large set of species analysed, the remaining unexplained variation in OAR slopes was substantial. Nevertheless, this large‐scale empirical analysis of the OAR offers an initial step towards a more general use of OARs for the fine‐scale prediction of species distributions and abundance.

Distinct evolutionary origins of common multi-drug resistance phenotypes in Salmonella typhimurium DT104: a convergent process for adaptation under stress - Le Tang; Song-Ling Zhu; Xin Fang; Yong-Guo Li; Cornelis Poppe; Randal N. Johnston; Gui-Rong Liu; Shu-Lin Liu (Molecular Genetics and Genomics, 2019)

The LRP6 functional mutation rs2302685 contributes to individual susceptibility to alcoholic liver injury related to the Wnt/β-catenin-TCF1-CYP2E1 signaling pathway - Ying Xu; Dan Chen; Xiu-Xian Lin; Qing Zhao; Jing Guo; Li-jie Chen; Wei Zhang; Jian Xiao; Guang-Hui Lian; Shi-Fang Peng; Dong Guo; Hong Yang; et al. (Archives of Toxicology, 2019)

Chronic stress impairs the aquaporin-4-mediated glymphatic transport through glucocorticoid signaling - Fang Wei; Jian Song; Cui Zhang; Jun Lin; Rong Xue; Li-Dong Shan; Shan Gong; Guo-Xing Zhang; Zheng-Hong Qin; Guang-Yin Xu; Lin-Hui Wang (Psychopharmacology, 2019)

Klotho recovery by genistein via promoter histone acetylation and DNA demethylation mitigates renal fibrosis in mice - Yanning Li; Fang Chen; Ai Wei; Fangfang Bi; Xiaobo Zhu; Shasha Yin; Wenjun Lin; Wangsen Cao (Journal of Molecular Medicine, 2019)

Agricultural Development and Implication for Wetlands Sustainability: A Case from Baoqing County, Northeast China - Chong Fang; Zhidan Wen; Lin Li; Jia Du; Ge Liu; Xiaodi Wang; Kaishan Song (Chinese Geographical Science, 2019)

Quaternary phosphonium cationic ionic liquid/porous metal–organic framework as an efficient catalytic system for cycloaddition of carbon dioxide into cyclic carbonates - Yu Lin Hu; Rui Li Zhang; Dong Fang (Environmental Chemistry Letters, 2019)

Complete genome sequence of an alternavirus from the phytopathogenic fungus Fusarium incarnatum - Xiaoting Zhang; Yuan Xie; Fang Zhang; Hangjun Sun; Yingying Zhai; Songbai Zhang; Hongxia Yuan; Lin Zhou; Fei Gao; Honglian Li (Archives of Virology, 2019)

Dereplication and targeted isolation of bioactive sulphur compound from bacteria isolated from a hydrothermal field - Xiuping Lin; Kunlong Li; Lilin Yang; Xiaoying Peng; Wei Fang; Xinpeng Tian; Yonghong Liu; Xuefeng Zhou (Natural Product Research, 2019)

Provenance of the Langjiexue Group to the south of the Yarlung-Tsangpo Suture Zone in southeastern Tibet: Insights on the evolution of the Neo-Tethys Ocean in the Late Triassic - Da-Ren Fang; Gen-Hou Wang; Ken-ichiro Hisada; Guo-Li Yuan; Fang-Lin Han; Dian Li; Yu Tang; Qiu-Ming Pei; Liang-Liang Zhang (International Geology Review, 2019)

Loop-mediated isothermal amplification (LAMP) detection of Phytophthora hibernalis, P. syringae and P. cambivora - Guan-Rong Li; Guo-Ming Huang; Lin-Hui Zhu; Dajin Lv; Baohong Cao; Fang Liao; Jia-Feng Luo (Journal of Plant Pathology, 2019)

Programmed cell death induced by cadmium stress and/or boron deprivation in tobacco (Nicotiana tabacum L.) cultivar Bright Yellow 2 cells - Li Ping Jiang; Lin Zi; Xiao Fang Liu; Zi-Xi Liu; Lai Fu Zhong; Xiang Xin Xue (In Vitro Cellular & Developmental Biology - Plant, 2019)

Ornithinimicrobium cavernae sp. nov., an actinobacterium isolated from a karst cave - Ling-Yu Zhang; Hong Ming; Xiao-Lin Meng; Bao-Zhu Fang; Jian-Yu Jiao; Nimaichand Salam; Xiao-Tong Zhang; Wen-Jun Li; Guo-Xing Nie (Antonie van Leeuwenhoek, 2019)

Direct and indirect effects of climate on richness drive the latitudinal diversity gradient in forest trees - Chengjin Chu; James A. Lutz; Kamil Král; Tomáš Vrška; Xue Yin; Jonathan A. Myers; Iveren Abiem; Alfonso Alonso; Norm Bourg; David F.R.P. Burslem; Min Cao; Hazel Chapman; et al. (Ecology Letters, 2019)
Climate is widely recognised as an important determinant of the latitudinal diversity gradient. However, most existing studies make no distinction between direct and indirect effects of climate, which substantially hinders our understanding of how climate constrains biodiversity globally. Using data from 35 large forest plots, we test hypothesised relationships amongst climate, topography, forest structural attributes (stem abundance, tree size variation and stand basal area) and tree species richness to better understand drivers of latitudinal tree diversity patterns. Climate influences tree richness both directly, with more species in warm, moist, aseasonal climates and indirectly, with more species at higher stem abundance. These results imply direct limitation of species diversity by climatic stress and more rapid (co‐)evolution and narrower niche partitioning in warm climates. They also support the idea that increased numbers of individuals associated with high primary productivity are partitioned to support a greater number of species.

Isolation and characterization of mineral-dissolving bacteria from different levels of altered mica schist surfaces and the adjacent soil - Yuan Li Wang; Qi Wang; Rui Yuan; Xia Fang Sheng; Lin Yan He (World Journal of Microbiology and Biotechnology, 2019)

Detection and quantification of Aeromonas schubertii in Channa maculata by TaqMan MGB probe fluorescence real‐time quantitative PCR - Chun Liu; Yanming M. Guo; Jizhen Z. Cao; De‐Feng Zhang; Ou‐Qin Chang; Kaibin Li; Fang Wang; Cun‐Bin Shi; Lan Jiang; Qing Wang; Li Lin (Journal of Fish Diseases, 2019)
Aeromonas schubertii is a major epidemiological agent that threatens cultured snakeheads ( Channidae ) and has caused great economic losses in fish‐farming industries in China in recent years. In present study, a specific TaqMan minor groove binder ( MGB ) probe fluorescence real‐time quantitative PCR ( qPCR ) assay was developed to rapidly detect and quantify A. schubertii . A pair of qPCR primers and a TaqMan MGB probe were selected from the rpoD gene, which were shown to be specific for A. schubertii . A high correlation coefficient ( R 2 = 0.9998) in a standard curve with a 103% efficiency was obtained. Moreover, the qPCR method's detection limit was as low as 18 copies/μl, which was 100 times more sensitive than that of conventional PCR . The detection results for the A. schubertii in pond water and fish tissue were consistent with those of the viable counts. Bacterial load changes detected by qPCR in different tissues of snakeheads infected with A. schubertii showed that the gills and intestines may be the entry for A. schubertii , and the spleen and kidney are major sites for A. schubertii replication. The established method in present study should be a useful tool for the early surveillance and quantitation of A. schubertii .

Effects of topographic factors and aboveground vegetation carbon stocks on soil organic carbon in Moso bamboo forests - Huiyun Fang; Biyong Ji; Xu Deng; Jiayang Ying; Guomo Zhou; Yongjun Shi; Lin Xu; Jixing Tao; Yufeng Zhou; Chong Li; Hao Zheng (Plant and Soil, 2018)

Immune Cells After Ischemic Stroke Onset: Roles, Migration, and Target Intervention - Lu-yao Ao; Yun-Yi Yan; Lin Zhou; Cheng-yuan Li; Wan-Ting Li; Wei-rong Fang; Yun-man Li (Journal of Molecular Neuroscience, 2018)

The complete genomic sequence of a novel megabirnavirus from Fusarium pseudograminearum, the causal agent of wheat crown rot - Xiaoting Zhang; Fei Gao; Fang Zhang; Yuan Xie; Lin Zhou; Hongxia Yuan; Songbai Zhang; Honglian Li (Archives of Virology, 2018)

Lack of Association Between DNMT3B Polymorphisms and Sporadic Parkinson’s Disease in a Han Chinese Population - Hong Pan; Jun-Yi Shen; Juan-Juan Du; Shi-Shuang Cui; Jin Liu; Yi-Qi Lin; Yi-Xi He; Yang Fu; Chao Gao; Gen Li; Sheng-Di Chen; Jian-Fang Ma (Neuroscience Bulletin, 2018)

Dopamine receptor D2 polymorphism is associated with alleviation of obesity after 8-year follow-up: a retrospective cohort study in obese Chinese children and adolescents - Jian-fang Zhu; Lian-hui Chen; Ke Yuan; Li Liang; Chun-lin Wang (Journal of Zhejiang University-SCIENCE B, 2018)

Identification and Field Evaluation of the Sex Pheromone of Orthaga achatina (Lepidoptera: Pyralidae) - Qi Yan; Hai-Dong Li; Yan Chen; Zhan-Feng Ye; Xi-Yu You; Jun Zhou; Lan-Fang Mu; Shi-Jing Liu; Xiang-Bo Kong; Sajjad Ali Khuhro; Shuang-Lin Dong (Journal of Chemical Ecology, 2018)

Leaching of metals from asphalt pavement incorporating municipal solid waste incineration fly ash - Jin-Zhong Yang; Yufei Yang; Ying Li; Lin Chen; Jing Zhang; Qingqi Die; Yanyan Fang; Yueyi Pan; Qifei Huang (Environmental Science and Pollution Research, 2018)

Three-dimensional reconstructed eccrine sweat glands with vascularization and cholinergic and adrenergic innervation - Mingjun Zhang; Haihong Li; Liyun Chen; Shuhua Fang; Sitian Xie; Changmin Lin (Journal of Molecular Histology, 2018)

Enhanced catalytic activities and modified substrate preferences for taxoid 10β-O-acetyl transferase mutants by engineering catalytic histidine residues - Lin-Feng You; Jia-Jun Huang; Tao Wei; Shu-Ling Lin; Bing-Hua Jiang; Li-Qiong Guo; Jun-Fang Lin (Biotechnology Letters, 2018)

Expression of BC1 Impairs Spatial Learning and Memory in Alzheimer’s Disease Via APP Translation - Tongmei Zhang; Pei Pang; Zemin Fang; Yu Guo; Hao Li; Xinyan Li; Tian Tian; Xin Yang; Wenting Chen; Shu Shu; Na Tang; Jianhua Wu; et al. (Molecular Neurobiology, 2018)

MiR-519d-3p suppresses breast cancer cell growth and motility via targeting LIM domain kinase 1 - Dengfeng Li; Hongming Song; Tianqi Wu; Dan Xie; Jiashu Hu; Junyong Zhao; Qiang Shen; Lin Fang (Molecular and Cellular Biochemistry, 2018)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

The effect of temperature on the developmental rates of seedling emergence and leaf-unfolding in two dwarf bamboo species - Shuyan Lin; Lijuan Shao; Cang Hui; Hardev S. Sandhu; Tingting Fan; Li Zhang; Fang Li; Yulong Ding; Peijian Shi (Trees, 2018)

Deletion of Type-2 Cannabinoid Receptor Induces Alzheimer’s Disease-Like Tau Pathology and Memory Impairment Through AMPK/GSK3β Pathway - Lin Wang; Bing-Jin Liu; Yun Cao; Wei-Qi Xu; Dong-Sheng Sun; Meng-Zhu Li; Fang-Xiao Shi; Man Li; Qing Tian; Jian-Zhi Wang; Xin-Wen Zhou (Molecular Neurobiology, 2018)

Identifying potentially common genes between dyslipidemia and osteoporosis using novel analytical approaches - Xu Lin; Cheng Peng; Jonathan Greenbaum; Zhang-Fang Li; Ke-Hao Wu; Zeng-Xin Ao; Tong Zhang; Jie Shen; Hong-Wen Deng (Molecular Genetics and Genomics, 2018)

Triplex real-time PCR detection of three quarantine Phytophthora pathogens infecting Malus Miller - Fang Liao; Ying Zhang; Lin-Hui Zhu; Baohong Cao; Dajin Lv; Jia-Feng Luo; Guan-Rong Li (Journal of Plant Diseases and Protection, 2018)

Impact of International Collaborative Training Programs on Medical Students’ Research Ability - Remila Rezhake; Shang-Ying Hu; Yu-Qian Zhao; Li Zhang; Xue-Lian Zhao; Ayling Z. Dominguez; You-Lin Qiao; Cai-Hong Zhou; Fang-Hui Zhao (Journal of Cancer Education, 2018)

A large lung gene expression study identifying IL1B as a novel player in airway inflammation in COPD airway epithelial cells - Gao Yi; Min Liang; Ming Li; Xiangming Fang; Jifang Liu; Yuxiong Lai; Jitao Chen; Wenxia Yao; Xiao Feng; La Hu; Chunyi Lin; Xinke Zhou; et al. (Inflammation Research, 2018)

Screening of seaweeds in the East China Sea as potential bio-monitors of heavy metals - Yaoru Pan; Thomas Wernberg; Thibaut de Bettignies; Marianne Holmer; Ke Li; Jiaping Wu; Fang Lin; Yan Yu; Jiang Xu; Chaosheng Zhou; Zhixing Huang; Xi Xiao (Environmental Science and Pollution Research, 2018)

A Quninolylthiazole Derivatives as an ICT-Based Fluorescent Probe of Hg(II) and its Application in Ratiometric Imaging in Live HeLa Cells - Jian-Ying Bai; Yu-Zhong Xie; Chang-Jiang Wang; Shu-Qing Fang; Lin-Nan Cao; Ling-Li Wang; Jing-Yi Jin (Journal of Fluorescence, 2018)

Structures and bioactivities of seven flavonoids from Osmanthus fragrans ‘Jinqiu’ essential oil extraction residues - Jiang-Lian Zhou; Xian-Ying Fang; Jing-Qiu Wang; Lin-Guo Zhao; Yi Li; Feng Tang; Yong-De Yue (Natural Product Research, 2018)

CyberConnector: a service-oriented system for automatically tailoring multisource Earth observation data to feed Earth science models - Ziheng Sun; Liping Di; Haosheng Hao; Xiaoqing Wu; Daniel Q. Tong; Chen Zhang; Cora Virgei; Hui Fang; Eugene Yu; Xicheng Tan; Peng Yue; Li Lin (Earth Science Informatics, 2018)

Histone 3 lysine 36 to methionine mutations stably interact with and sequester SDG8 in Arabidopsis thaliana - Guang Lin; Ying Zhou; Min Li; Yuda Fang (Science China Life Sciences, 2018)

The Distal Gut Bacterial Community of Some Primates and Carnivora - Xiu Chen; Qin-Yuan Li; Gui-Ding Li; Fang-Ji Xu; Li Han; Yi Jiang; Xue-Shi Huang; Cheng-Lin Jiang (Current Microbiology, 2018)

Erratum to: Forskolin Induces Hyperphosphorylation of Tau Accompanied by Cell Cycle Reactivation in Primary Hippocampal Neurons - Hai-Hong Wang; Yan Li; Ang Li; Fang Yan; Zhen-Lin Li; Zhong-Ying Liu; Lei Zhang; Jian Zhang; Wei-Ren Dong; Lin Zhang (Molecular Neurobiology, 2018)

Gender-Related Hippocampal Proteomics Study from Young Rats After Chronic Unpredicted Mild Stress Exposure - Lin-Na Ning; Teng Zhang; Jiang Chu; Na Qu; Li Lin; Ying-Yan Fang; Yan Shi; Peng Zeng; Er-Li Cai; Xiao-Ming Wang; Qun Wang; You-Ming Lu; et al. (Molecular Neurobiology, 2018)

Forskolin Induces Hyperphosphorylation of Tau Accompanied by Cell Cycle Reactivation in Primary Hippocampal Neurons - Hai-Hong Wang; Yan Li; Ang Li; Fang Yan; Zhen-Lin Li; Zhong-Ying Liu; Lei Zhang; Jian Zhang; Wei-Ren Dong; Lin Zhang (Molecular Neurobiology, 2018)

Effects of prenatal caffeine exposure on glucose homeostasis of adult offspring rats - Hao Kou; Gui-hua Wang; Lin-guo Pei; Li Zhang; Chai Shi; Yu Guo; Dong-fang Wu; Hui Wang (The Science of Nature, 2017)

Relationship Between Perisylvian Essential Language Sites and Arcuate Fasciculus in the Left Hemisphere of Healthy Adults - Yu Lin; Kai Zhang; Shuai Li; Song Li; Jingna Jin; Fang Jin; Wen Qin; Long Hai; Meng Zhu; Chunshui Yu; Zhipeng Liu; Tao Yin; et al. (Neuroscience Bulletin, 2017)

Efficient Using Durian Shell Hydrolysate as Low-Cost Substrate for Bacterial Cellulose Production by Gluconacetobacter xylinus - Mu-Tan Luo; Cheng Zhao; Chao Huang; Xue-Fang Chen; Qian-Lin Huang; Gao-Xiang Qi; Lan-Lan Tian; Lian Xiong; Hai-Long Li; Xin-De Chen (Indian Journal of Microbiology, 2017)

Analysis of miRNA-seq combined with gene expression profile reveals the complexity of salinity stress response in Oryza sativa - Qingwei Wang; Tianlong Geng; Shuhua Zhu; Rui Li; Yongao Tong; Shenghua Wang; Fang Chen; Lin Tang; Yang He (Acta Physiologiae Plantarum, 2017)

Yangonindimers A-C, three new kavalactone dimers from Piper methysticum (kava) - Jia-Ling Song; Bai-Lin Li; Yao Yuan; Ling-Hui Nie; Jia Niu; David Chiu; Zhi-Fang Xu; Jie-Wei Wu; Sheng-Xiang Qiu (Natural Product Research, 2017)

Interannual variation in methane emissions from tropical wetlands triggered by repeated El Niño Southern Oscillation - Qiuan Zhu; Changhui Peng; Philippe Ciais; Hong Jiang; Jinxun Liu; Philippe Bousquet; Shiqin Li; Jie Chang; Xiuqin Fang; Xiaolu Zhou; Huai Chen; Shirong Liu; et al. (Global Change Biology, 2017)
Methane (CH 4 ) emissions from tropical wetlands contribute 60%–80% of global natural wetland CH 4 emissions. Decreased wetland CH 4 emissions can act as a negative feedback mechanism for future climate warming and vice versa. The impact of the El Niño–Southern Oscillation (ENSO) on CH 4 emissions from wetlands remains poorly quantified at both regional and global scales, and El Niño events are expected to become more severe based on climate models’ projections. We use a process‐based model of global wetland CH 4 emissions to investigate the impacts of the ENSO on CH 4 emissions in tropical wetlands for the period from 1950 to 2012. The results show that CH 4 emissions from tropical wetlands respond strongly to repeated ENSO events, with negative anomalies occurring during El Niño periods and with positive anomalies occurring during La Niña periods. An approximately 8‐month time lag was detected between tropical wetland CH 4 emissions and ENSO events, which was caused by the combined time lag effects of ENSO events on precipitation and temperature over tropical wetlands. The ENSO can explain 49% of interannual variations for tropical wetland CH 4 emissions. Furthermore, relative to neutral years, changes in temperature have much stronger effects on tropical wetland CH 4 emissions than the changes in precipitation during ENSO periods. The occurrence of several El Niño events contributed to a lower decadal mean growth rate in atmospheric CH 4 concentrations throughout the 1980s and 1990s and to stable atmospheric CH 4 concentrations from 1999 to 2006, resulting in negative feedback to global warming.

Spatial and temporal evolution of community resilience to natural hazards in the coastal areas of China - Wenmin Qin; Aiwen Lin; Jian Fang; Lunche Wang; Man Li (Natural Hazards, 2017)

Impacts of precipitation variation and soil and water conservation measures on runoff and sediment yield in the Loess Plateau Gully Region, China - Lu Xia; Xiao-yu Song; Na Fu; Chun-fang Meng; Huai-you Li; Yao-lin Li (Journal of Mountain Science, 2017)

Reduced weed seed shattering by silencing a cultivated rice gene: strategic mitigation for escaped transgenes - Huanxin Yan; Lei Li; Ping Liu; Xiaoqi Jiang; Lei Wang; Jia Fang; Zhimin Lin; Feng Wang; Jun Su; Bao-Rong Lu (Transgenic Research, 2017)

Taxonomy of the order Mononegavirales: update 2017 - Gaya K. Amarasinghe; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Martin Beer; Nicolás Bejerman; Kim R. Blasdell; Alisa Bochnowski; Thomas Briese; Alexander Bukreyev; Charles H. Calisher; Kartik Chandran; et al. (Archives of Virology, 2017)

Effect of culture conditions on metabolites produced by the crinoid-derived fungus Aspergillus ruber 1017 - Yong-Fang Li; Xue-Bin Wu; Shah-Iram Niaz; Liu-Hong Zhang; Zhi-Jian Huang; Yong-Cheng Lin; Jing Li; Lan Liu (Natural Product Research, 2017)

A CRISPR/Cas9 toolkit for efficient targeted base editing to induce genetic variations in rice - Bin Ren; Fang Yan; Yongjie Kuang; Na Li; Dawei Zhang; Honghui Lin; Huanbin Zhou (Science China Life Sciences, 2017)

Furofuran lignan glucosides from the leaves of Vitex negundo var. cannabifolia - Yue-Ting Li; Man-Man Li; Jing Sun; Zhi-Xiang Zhu; Yue-Lin Song; Dao-Ran Pang; Jiao Zheng; Yun-Fang Zhao; Peng-Fei Tu; Jun Li (Natural Product Research, 2017)

Global protein expression profile response of planktonic Aeromonas hydrophila exposed to chlortetracycline - Wanxin Li; Zujie Yao; Xiangyu Zhang; Fang Huang; Wenxiong Lin; Xiangmin Lin (World Journal of Microbiology and Biotechnology, 2017)

Molecular and morphological identification of a human biting tick, Amblyomma testudinarium (Acari: Ixodidae), in Taiwan - Li-Lian Chao; Chun-Wei Lu; Ying-Fang Lin; Chien-Ming Shih (Experimental and Applied Acarology, 2017)

Geological characteristics and main controlling factors of Permian lacustrine tight oil in the eastern part of the Junggar Basin - Junwei Zhao; Huaimin Xu; Cui He; Lin Li; Zhen Yi; Huijing Fang; Zhicheng Lei (Geosciences Journal, 2017)

Effects of soybean meal processing treatments on growth performance, nutrient digestibility, nitrogen and phosphorus excretion in red swamp crayfish, Procambarus clarkii - Jin-juan Wan; Mei-fang Shen; Jian-qing Tang; Hai Lin; Wei-hui Yan; Jia-jia Li; Lin Zhu (Aquaculture International, 2017)

Anti-neuroinflammatory constituents from the fungus Penicillium purpurogenum MHZ 111 - Jing Sun; Zhi-Xiang Zhu; Yue-Lin Song; Yi Ren; Dan Dong; Jiao Zheng; Ting Liu; Yun-Fang Zhao; Peng-Fei Tu; Jun Li (Natural Product Research, 2017)

NLRP3 is Required for Complement-Mediated Caspase-1 and IL-1beta Activation in ICH - Sheng-Tao Yao; Fang Cao; Jia-Lin Chen; Wei Chen; Rui-Ming Fan; Gang Li; You-Chao Zeng; Song Jiao; Xiang-Ping Xia; Chong Han; Qi-Shan Ran (Journal of Molecular Neuroscience, 2017)

Complete genomic characterization of two European-genotype porcine reproductive and respiratory syndrome virus isolates in Fujian province of China - Jian-Kui Liu; Chun-Hua Wei; AI-Ling Dai; Ke-Wei Fan; Bing-Hui Yang; Chun-Fang Huang; Xiao-Hua Li; Xiao-Yan Yang; Man-Lin Luo (Archives of Virology, 2017)

Impacts of sediment type on the performance and composition of submerged macrophyte communities - Lin Liu; Xiang-Qi Bu; Jun-Yan Wan; Bi-Cheng Dong; Fang-Li Luo; Hong-Li Li; Fei-Hai Yu (Aquatic Ecology, 2017)

A novel thymidine phosphorylase mutation in a Chinese MNGIE patient - Hui-Fang Wang; Juan Wang; Yan-Ling Wang; Jian-Jian Fan; Gui-Lin Mo; Feng-Yin Gong; Zhi-Ming Chai; Jin Zhang; Hua-Xing Meng; Chang-Xin Li; Jun-Hong Guo; Chuan-Qiang Pu (Acta Neurologica Belgica, 2017)

Antimicrobial mechanism of the major active essential oil compounds and their structure–activity relationship - Xian Hui; Ge Yan; Fang-Lin Tian; Heng Li; Wen-Yun Gao (Medicinal Chemistry Research, 2017)

Identification and characterization of miRNAs involved in adventitious branches formation of Gracilaria lichenoides in vitro - Wenlei Wang; Huanqin Li; Xiangzhi Lin; Zhaokai Wang; Baishan Fang (Journal of Applied Phycology, 2017)

In vitro reprogramming of rat bmMSCs into pancreatic endocrine-like cells - Hong-Tu Li; Fang-Xu Jiang; Ping Shi; Tao Zhang; Xiao-Yu Liu; Xue-Wen Lin; Zhong-Yan San; Xi-Ning Pang (In Vitro Cellular & Developmental Biology - Animal, 2017)

Inoculation with endophytic Bacillus megaterium H3 increases Cd phytostabilization and alleviates Cd toxicity to hybrid pennisetum in Cd-contaminated aquatic environments - Ya Li; Hui Han; Lin Yan He; Qi Wang; Xia Fang Sheng (Environmental Science and Pollution Research, 2017)

Design, synthesis, and antimicrobial activities of new tanshinone IIA esters - Lin-Wei Zeng; Chang-Xin Zhou; Jia-Dong Liu; Chang-Hong Liu; Jian-Xia Mo; A-Fang Hou; Wei Yao; Zhen-Zhen Wang; Li-She Gan (Natural Product Research, 2016)

A GWA study reveals genetic loci for body conformation traits in Chinese Laiwu pigs and its implications for human BMI - Lisheng Zhou; Jiuxiu Ji; Song Peng; Zhen Zhang; Shaoming Fang; Lin Li; Yaling Zhu; Lusheng Huang; Congying Chen; Junwu Ma (Mammalian Genome, 2016)

Object-based image analysis for mapping geomorphic zones of coral reefs in the Xisha Islands, China - Jingping Xu; Jianhua Zhao; Fang Li; Lin Wang; Derui Song; Shiyong Wen; Fei Wang; Ning Gao (Acta Oceanologica Sinica, 2016)

Erratum to: Drought tolerance and proteomics studies of transgenic wheat containing the maize C4 phosphoenolpyruvate carboxylase (PEPC) gene - Na Qin; Weigang Xu; Lin Hu; Yan Li; Huiwei Wang; Xueli Qi; Yuhui Fang; Xia Hua (Protoplasma, 2016)

Drought tolerance and proteomics studies of transgenic wheat containing the maize C4 phosphoenolpyruvate carboxylase (PEPC) gene - Na Qin; Weigang Xu; Lin Hu; Yan Li; Huiwei Wang; Xueli Qi; Yuhui Fang; Xia Hua (Protoplasma, 2016)

Molecular detection and genome characterization of porcine circovirus type 2 in rats captured on commercial swine farms - Shao-Lun Zhai; Sheng-Nan Chen; Wei Liu; Xiao-Peng Li; Su-Fang Deng; Xiao-Hui Wen; Man-Lin Luo; Dian-Hong Lv; Wen-Kang Wei; Rui-Ai Chen (Archives of Virology, 2016)

Associations of TNF-α and IL-6 polymorphisms with osteoporosis through joint effects and interactions with LEPR gene in Taiwan: Taichung Community Health Study for Elders (TCHS-E) - Cheng-Chieh Lin; Tsai-Chung Li; Chiu-Shong Liu; Chuan-Wei Yang; Chih-Hsueh Lin; Jen-Hao Hsiao; Nai-Hsin Meng; Wen-Yuan Lin; Li-Na Liao; Chia-Ing Li; Fang-Yang Wu (Molecular Biology Reports, 2016)

Netrin-1 Contributes to Myelinated Afferent Fiber Sprouting and Neuropathic Pain - Cai-Hua Wu; Xiao-Cui Yuan; Fang Gao; Hong-Ping Li; Jie Cao; Yan-Shen Liu; Wei Yu; Bo Tian; Xian-Fang Meng; Jing Shi; Hui-Lin Pan; Man Li (Molecular Neurobiology, 2016)

Sonic Hedgehog Signaling Affected by Promoter Hypermethylation Induces Aberrant Gli2 Expression in Spina Bifida - Xiao-Lin Lu; Li Wang; Shao-Yan Chang; Shao-Fang Shangguan; Zhen Wang; Li-Hua Wu; Ji-Zhen Zou; Ping Xiao; Rui Li; Yi-Hua Bao; Z-Y Qiu; Ting Zhang (Molecular Neurobiology, 2016)

The P450 oxidoreductase (POR) rs2868177 and cytochrome P450 (CYP) 2B6*6 polymorphisms contribute to the interindividual variability in human CYP2B6 activity - Li-chen Gao; Fang-qun Liu; Li Yang; Lin Cheng; Hai-ying Dai; Ran Tao; Shi-Peng Cao; Di Wang; Jie Tang (European Journal of Clinical Pharmacology, 2016)

Synergistic antitumor activity of triple-regulated oncolytic adenovirus with VSTM1 and daunorubicin in leukemic cells - Jiao Zhou; Qiu-Mei Yao; Jin-Lan Li; Yan Chang; Ting Li; Wen-Ling Han; Hong-Ping Wu; Lin-Fang Li; Qi-Jun Qian; Guo-Rui Ruan (Apoptosis, 2016)

Microsatellite records for volume 8, issue 3 - Yan-Ling Cao; Lívia Izabela Caputo; Hongyi Cheng; Fausto Moreira da Silva Carmo; Leiliane Campos de Carvalho; Gabriel de Menezes Yazbeck; Zélia de Oliveira Teixeira; Jiaxin Fu; José Antonio Guerrero; Guibing Hu; Jun Li; Zhihua Lin; et al. (Conservation Genetics Resources, 2016)

Microbacterium gilvum sp. nov., isolated from civet faeces - Xiu Chen; Qin-Yuan Li; Gui-Ding Li; Fang-Ji Xu; Yi Jiang; Li Han; Cheng-Lin Jiang; Xue-Shi Huang (Antonie van Leeuwenhoek, 2016)

Signaling Mechanism of Cannabinoid Receptor-2 Activation-Induced β-Endorphin Release - Fang Gao; Ling-Hong Zhang; Tang-Feng Su; Lin Li; Rui Zhou; Miao Peng; Cai-Hua Wu; Xiao-Cui Yuan; Ning Sun; Xian-Fang Meng; Bo Tian; Jing Shi; et al. (Molecular Neurobiology, 2016)

Effect of silicon on grain yield of rice under cadmium-stress - Hongmei Lin; Changxun Fang; Yingzhe Li; Weiwei Lin; Jianyu He; Ruiyu Lin; Wenxiong Lin (Acta Physiologiae Plantarum, 2016)

A novel process for obtaining pinosylvin using combinatorial bioengineering in Escherichia coli - Jing-long Liang; Li-qiong Guo; Jun-fang Lin; Ze-qi He; Fa-ji Cai; Jun-fei Chen (World Journal of Microbiology and Biotechnology, 2016)

De novo transcriptome analysis of carotenoid and polyunsaturated fatty acid metabolism in Rhodomonas sp. - Huanqin Li; Wenlei Wang; Zhaokai Wang; Xiangzhi Lin; Fang Zhang; Longhe Yang (Journal of Applied Phycology, 2016)

QTL mapping of dehiscence length at the basal part of thecae related to heat tolerance of rice (Oryza sativa L.) - Ling Zhao; Chun-Fang Zhao; Li-Hui Zhou; Jing Lin; Qing-Yong Zhao; Zhen Zhu; Tao Chen; Shu Yao; Toshihiro Hasegawa; Tsutomu Matsui; Cai-Lin Wang (Euphytica, 2016)

Effects of seasonal variations on soil microbial community composition of two typical zonal vegetation types in the Wuyi Mountains - Ze-yan Wu; Wen-xiong Lin; Jian-juan Li; Jin-fu Liu; Bai-lian Li; Lin-kun Wu; Chang-xun Fang; Zhi-xing Zhang (Journal of Mountain Science, 2016)

Discovery of Influenza A virus neuraminidase inhibitors using support vector machine and Naïve Bayesian models - Wenwen Lian; Jiansong Fang; Chao Li; Xiaocong Pang; Ai-Lin Liu; Guan-Hua Du (Molecular Diversity, 2016)

Species-specific differences in the role of L-type Ca2+ channels in the regulation of coronary arterial smooth muscle contraction - Hui Yang; Su-Juan Kuang; Fang Rao; Yu-Mei Xue; Xiao-Ying Liu; Zhi-Xin Shan; Xiao-Hong Li; Jie-Ning Zhu; Zhi-Ling Zhou; Xiao-juan Zhang; Qiu-Xiong Lin; Xi-Yong Yu; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2016)

Isolation, complete genome sequencing, and phylogenetic analysis of the first Chuzan virus in China - Fang Wang; Jun Lin; Jitao Chang; Yingying Cao; Shaomin Qin; Jianmin Wu; Li Yu (Virus Genes, 2016)

Characteristic pollen source area and vertical pollen dispersal and deposition in a mixed coniferous and deciduous broad-leaved woodland in the Changbai mountains, northeast China - Shengrui Zhang; Qinghai Xu; Marie-José Gaillard; Xianyong Cao; Jianyong Li; Liyan Zhang; Yuecong Li; Fang Tian; Liping Zhou; Fengyou Lin; Xiaolan Yang (Vegetation History and Archaeobotany, 2016)

Combined effect of rice genotypes and soil characteristics on iron plaque formation related to Pb uptake by rice in paddy soils - Fang-Lin Li; Ching-Ming Yang; Chien-Hui Syu; Dar-Yuan Lee; Ben-Jei Tsuang; Kai-Wei Juang (Journal of Soils and Sediments, 2016)

Development of single-chain variable fragments (scFv) against influenza virus targeting hemagglutinin subunit 2 (HA2) - Tai-Wei Li; Shu-Fang Cheng; Yen-Tzu Tseng; Yu-Chih Yang; Wen-chun Liu; Sheng-Cyuan Wang; Mei-Ju Chou; Yu-Jen Lin; Yueh Wang; Pei-Wen Hsiao; Suh-Chin Wu; Ding-Kwo Chang (Archives of Virology, 2016)

Separation and identification of a novel tadalafil analogue adulterant in a dietary supplement - Yen-Chun Huang; Hui-Chun Lee; Yun-Lian Lin; Chia-Ying Li; Chia-Fen Tsai; Hwei-Fang Cheng (Food Additives & Contaminants: Part A, 2015)

Heat-induced unfolding of apo-CP43 studied by fluorescence spectroscopy and CD spectroscopy - Qing-Jie Xiao; Zai-Geng Li; Jiao Yang; Qing He; Lei Xi; Lin-Fang Du (Photosynthesis Research, 2015)

Soil labile organic carbon fractions in rhizosphere soil in citrus plantations in the Three Gorges Reservoir Area - Guo-Mei Jia; Bao-Lin Zhang; Jun-Tao Niu; Li-Ming Wang; Fang-Qing Chen (Agroforestry Systems, 2015)

Bergapten promotes bone marrow stromal cell differentiation into osteoblasts in vitro and in vivo - Ji-jie Xiao; Wen-ji Zhao; Xin-tao Zhang; Wen-long Zhao; Xiao-xia Wang; Shu-hui Yin; Fang Jiang; Yin-xia Zhao; Fang-ni Chen; Shao-lin Li (Molecular and Cellular Biochemistry, 2015)

Sphingobacterium rhinocerotis sp. nov., isolated from the faeces of Rhinoceros unicornis - Gui-Ding Li; Xiu Chen; Qin-Yuan Li; Fang-Ji Xu; Shu-Mei Qiu; Yi Jiang; Cheng-Lin Jiang (Antonie van Leeuwenhoek, 2015)

Effect of antioxidants and light stabilisers on silver migration from nanosilver-polyethylene composite packaging films into food simulants - Qi-Zhi Su; Qin-Bao Lin; Chao-Fang Chen; Yu-Mei Wu; Li-Bing Wu; Xiao-Qing Chen; Zhi-Wei Wang (Food Additives & Contaminants: Part A, 2015)

Isolation of a new flavanone from Daidai fruit and hypolipidemic activity of total flavonoids extracts - Ling-Jun Zeng; Dan Chen; Qing-De Huang; Qun Huang; Yun-Fang Lian; Wei-Wei Cai; Hua-Ping Zeng; Yi-Li Lin (Natural Product Research, 2015)

Endoplasmic Reticulum Protein 29 Protects Axotomized Neurons from Apoptosis and Promotes Neuronal Regeneration Associated with Erk Signal - Yun-Hui Zhang; Visar Belegu; Yu Zou; Fang Wang; Bao-Jiang Qian; Ran Liu; Ping Dai; Wei Zhao; Fa-Bao Gao; Lei Wang; Li-Mei Cao; John W. McDonald; et al. (Molecular Neurobiology, 2015)

Characterisation of oligosaccharides from Baizhu by HILIC-MS - Zhe Lin; Yan-Fang Liu; Yang Qu; Li-Ying Shi; De-Qiang Dou; Hai-Xue Kuang (Natural Product Research, 2015)

Altered microRNA Expression in Peripheral Blood Mononuclear Cells from Young Patients with Schizophrenia - Hui-min Fan; Xin-yang Sun; Wei Niu; Lin Zhao; Qiao-Li Zhang; Wan-shuai Li; Ai-fang Zhong; Li-yi Zhang; Jim Lu (Journal of Molecular Neuroscience, 2015)

Tumor-derived microRNA-494 promotes angiogenesis in non-small cell lung cancer - Guangmei Mao; Yan Liu; Xi Fang; Yahan Liu; Li Fang; Lianjun Lin; Xinmin Liu; Nanping Wang (Angiogenesis, 2015)

The potential roles of bacterial communities in coral defence: A case study at Talang-talang reef - Felicity W. I. Kuek; Li-Fang Lim; Lin-Hui Ngu; Aazani Mujahid; Po-Teen Lim; Chui-Pin Leaw; Moritz Müller (Ocean Science Journal, 2015)

Gender differences in affective sharing and self–other distinction during empathic neural responses to others’ sadness - Pinchao Luo; Junfang Wang; Yan Jin; Shanshan Huang; Mengshu Xie; Lin Deng; Juncong Fang; Xiaochun Zheng; Xiaoying Chen; Yue Li; Yijie Jiang; Xifu Zheng (Brain Imaging and Behavior, 2015)

A Novel Oral Preparation of Hydroxysafflor Yellow A Base on a Chitosan Complex: A Strategy to Enhance the Oral Bioavailability - Guan-nan Ma; Fang-lin Yu; Shan Wang; Zhi-ping Li; Xiang-yang Xie; Xing-guo Mei (AAPS PharmSciTech, 2015)

JcCBF2 gene from Jatropha curcas improves freezing tolerance of Arabidopsis thaliana during the early stage of stress - Linghui Wang; Jihai Gao; Xiaobo Qin; Xiaodong Shi; Lin Luo; Guozhen Zhang; Hongwu Yu; Chenyang Li; Minchao Hu; Qifan Liu; Ying Xu; Fang Chen (Molecular Biology Reports, 2015)

Ectopic expression of a phytochrome B gene from Chinese cabbage (Brassica rapa L. ssp. pekinensis) in Arabidopsis thaliana promotes seedling de-etiolation, dwarfing in mature plants, and delayed flowering - Mei-Fang Song; Shu Zhang; Pei Hou; Hong-Zhong Shang; Hai-Ke Gu; Jing-Juan Li; Yang Xiao; Lin Guo; Liang Su; Jian-Wei Gao; Jian-Ping Yang (Plant Molecular Biology, 2015)

Phylogenetic and recombination analysis of rice black-streaked dwarf virus segment 9 in China - Yu Zhou; Jian-Feng Weng; Yan-Ping Chen; Chang-Lin Liu; Xiao-Hua Han; Zhuan-Fang Hao; Ming-Shun Li; Hong-Jun Yong; De-Gui Zhang; Shi-Huang Zhang; Xin-Hai Li (Archives of Virology, 2015)

Improving multi-model ensemble probabilistic prediction of Yangtze River valley summer rainfall - Fang Li; Zhongda Lin (Advances in Atmospheric Sciences, 2015)

Interactions between household air pollution and GWAS-identified lung cancer susceptibility markers in the Female Lung Cancer Consortium in Asia (FLCCA) - H. Dean Hosgood; Minsun Song; Chao Agnes Hsiung; Zhihua Yin; Xiao-Ou Shu; Zhaoming Wang; Nilanjan Chatterjee; Wei Zheng; Neil Caporaso; Laurie Burdette; Meredith Yeager; Sonja I. Berndt; et al. (Human Genetics, 2015)

Consensus models for CDK5 inhibitors in silico and their application to inhibitor discovery - Jiansong Fang; Ranyao Yang; Li Gao; Shengqian Yang; Xiaocong Pang; Chao Li; Yangyang He; Ai-Lin Liu; Guan-Hua Du (Molecular Diversity, 2015)

Conjugated linoleic acid alters growth performance, tissue lipid deposition, and fatty acid composition of darkbarbel catfish (Pelteobagrus vachelli) - Gui-Fang Dong; Wen-Zuo Liu; Lin-Zhou Wu; Deng-hang Yu; Feng Huang; Peng-Cheng Li; Yan-ou Yang (Fish Physiology and Biochemistry, 2015)

Bacillus vanillea sp. nov., Isolated from the Cured Vanilla Bean - Yong-gan Chen; Feng-lin Gu; Ji-hua Li; Fei Xu; Shu-zhen He; Yi-ming Fang (Current Microbiology, 2015)

Characterization of white spot syndrome virus VP52B and its interaction with VP26 - Fanyu Lin; Zuliang Jie; Luhong Hou; Fang Li; Feng Yang (Virus Genes, 2015)

A review of seasonal climate prediction research in China - Huijun Wang; Ke Fan; Jianqi Sun; Shuanglin Li; Zhaohui Lin; Guangqing Zhou; Lijuan Chen; Xianmei Lang; Fang Li; Yali Zhu; Hong Chen; Fei Zheng (Advances in Atmospheric Sciences, 2015)

MiR-199a is overexpressed in plasma of type 2 diabetes patients which contributes to type 2 diabetes by targeting GLUT4 - Shuang-Tong Yan; Chun-Lin Li; Hui Tian; Jian Li; Yu Pei; Yu Liu; Yan-Ping Gong; Fu-Sheng Fang; Ban-Ruo Sun (Molecular and Cellular Biochemistry, 2014)

Isolation and characterization of polymorphic microsatellites in the perennial herb Euphorbia kansui using paired-end Illumina shotgun sequencing - Xiao-Hao Yan; Min-Feng Fang; Zeng-Qiang Qian; Zhan-Lin Liu; Ma-Li Wang; Cai-Ping Tian; Meng-Han Du; Yin-Jun Li; Zhong-Hu Li; Gui-Fang Zhao (Conservation Genetics Resources, 2014)

Chemical analysis of aged benzene secondary organic aerosol using aerosol laser time-of-flight mass spectrometer - Mingqiang Huang; Yuehong Lin; Xianying Huang; Xingqiang Liu; Changjin Hu; Xuejun Gu; Weixiong Zhao; Li Fang; Weijun Zhang (Journal of Atmospheric Chemistry, 2014)

Molecular modeling study on the structural basis of binding mechanism of C6-substituted phthalides with monoamine oxidases - Pei Zhen Li; Yue Li Tian; Hong Lin Zhai; Fang Fang Deng; Mei Hong Xie; Xiao Yun Zhang (Medicinal Chemistry Research, 2014)

Molecular cloning and expression analysis of mannose receptor in blunt snout bream (Megalobrama amblycephala) - Xiaoling Liu; Xiaocheng Tang; Li Wang; Jie Li; Hong Wang; Shun Wei; Rui Fang; Wei Ji; Gailing Yuan; Nan Chen; Zemao Gu; Xueqin Liu; et al. (Molecular Biology Reports, 2014)

Expression of bone morphogenetic protein 2, 4, and related components of the BMP signaling pathway in the mouse uterus during the estrous cycle - Yan Li; Quan-wei Wei; Jian-gang Feng; Mu-lin Xu; Rui-hua Huang; Fang-xiong Shi (Journal of Zhejiang University-SCIENCE B, 2014)

Differential proteome analysis of mature and germinated seeds of Magnolia sieboldii K. Koch - Xiao-lin Zhang; Guang-lin Liu; Tian-lai Li; Ming-fang Qi; Mei Mei; Xiu-jun Lu (Trees, 2014)

Cloning and characterization of squalene synthase gene from Poria cocos and its up-regulation by methyl jasmonate - Jian-Rong Wang; Jun-Fang Lin; Li-Qiong Guo; Lin-Feng You; Xian-Lu Zeng; Jia-Ming Wen (World Journal of Microbiology and Biotechnology, 2014)

A study of N-methyl-D-aspartate receptor gene (GRIN2B) variants as predictors of treatment-resistant major depression - Chen Zhang; Zezhi Li; Zhiguo Wu; Jun Chen; Zuowei Wang; Daihui Peng; Wu Hong; Chengmei Yuan; Zhen Wang; Shunying Yu; Yifeng Xu; Lin Xu; et al. (Psychopharmacology, 2014)

HMGB1 Contributes to Regeneration After Spinal Cord Injury in Adult Zebrafish - Ping Fang; Hong-Chao Pan; Stanley Li Lin; Wen-Qing Zhang; Heikki Rauvala; Melitta Schachner; Yan-Qin Shen (Molecular Neurobiology, 2014)

Genome-wide annotation, expression profiling, and protein interaction studies of the core cell-cycle genes in Phalaenopsis aphrodite - Hsiang-Yin Lin; Jhun-Chen Chen; Miao-Ju Wei; Yi-Chen Lien; Huang-Hsien Li; Swee-Suak Ko; Zin-Huang Liu; Su-Chiung Fang (Plant Molecular Biology, 2014)

miR-124 Represses ROCK1 Expression to Promote Neurite Elongation Through Activation of the PI3K/Akt Signal Pathway - Xi Gu; Siying Meng; Shuhu Liu; Chunhong Jia; Yingying Fang; Shuji Li; Congcong Fu; Qiancheng Song; Lifang Lin; Xuemin Wang (Journal of Molecular Neuroscience, 2014)

Deciphering the role of Burkholderia cenocepacia membrane proteins in antimicrobial properties of chitosan - Muhammad Ibrahim; Zhongyun Tao; Annam Hussain; Yang Chunlan; Mehmoona Ilyas; Abdul Waheed; Fang Yuan; Bin Li; Guan-Lin Xie (Archives of Microbiology, 2014)

Variability of atlantic meridional overturning circulation in FGOALS-g2 - Wenyu Huang; Bin Wang; Lijuan Li; Li Dong; Pengfei Lin; Yongqiang Yu; Tianjun Zhou; Li Liu; Shiming Xu; Kun Xia; Ye Pu; Lu Wang; et al. (Advances in Atmospheric Sciences, 2014)

Genetic variation in alkaloid accumulation in leaves of Nicotiana - Bo Sun; Fen Zhang; Guo-jun Zhou; Guo-hai Chu; Fang-fang Huang; Qiao-mei Wang; Li-feng Jin; Fu-cheng Lin; Jun Yang (Journal of Zhejiang University-SCIENCE B, 2013)

The first complete genomic characterization of an Amur virus isolate from China - Yu Zhang; Bo-Hua Liu; Fang Lin; Yong-Guo Zhang; Bing-Yin Si; Xiao-Ping Kang; Yi Hu; Jing Li; Xiao-Yan Wu; Yu-Chang Li; Qing-Yu Zhu; Yin-Hui Yang (Archives of Virology, 2013)

On brain activity mapping: insights and lessons from Brain Decoding Project to map memory patterns in the hippocampus - Joe Z. Tsien; Meng Li; Remus Osan; GuiFen Chen; LongNian Lin; Phillip Lei Wang; Sabine Frey; Julietta Frey; DaJiang Zhu; TianMing Liu; Fang Zhao; Hui Kuang (Science China Life Sciences, 2013)

Profiling of StvacINV1 Expression in Relation to Acid Invertase Activity and Sugar Accumulation in Potato Cold-Stored Tubers - Yongbin Ou; Botao Song; Xun Liu; Yuan Lin; Huiling Zhang; Meng Li; Hui Fang; Jun Liu (Potato Research, 2013)

Isolation and characterization of polymorphic microsatellite loci in Ping’s juniper Juniperus pingii - Zhong-Hu Li; Zhan-Lin Liu; Yu-Jin Wang; Min-Feng Fang; Ma-Li Wang; Zhi-Xuan Li; Gui-Fang Zhao (Conservation Genetics Resources, 2013)

QTL mapping and correlation analysis for 1000-grain weight and percentage of grains with chalkiness in rice - JIAN-MIN BIAN; HUAN SHI; CUI-JUAN LI; CHANG-LAN ZHU; QIU-YING YU; XIAO-SONG PENG; JUN-RU FU; XIAO-PENG HE; XIAO-RONG CHEN; LI-FANG HU; LIN-JUAN OUYANG; HAO-HUA HE (Journal of Genetics, 2013)

Analysis of artificial corner reflector’s radar cross section: a physical optics perspective - Xin-Jian Shan; Jing-Yuan Yin; Dan-Lin Yu; Cheng-Fan Li; Jun-Juan Zhao; Gui-Fang Zhang (Arabian Journal of Geosciences, 2013)

Effects of single and combined genotypes of MC4R and POU1F1 genes on two production traits in Langshan chicken - Lin Jun Yan; Xing Tang Fang; Yao Liu; Chun Lei Zhang; Xuan Xuan Liu; Jing Zhao; Jing Jing Li; Hong Chen (Molecular Biology Reports, 2013)

Proteomic and physiological analyses reveal detoxification and antioxidation induced by Cd stress in Kandelia candel roots - Zhao-Xia Weng; Ling-Xia Wang; Fang-lin Tan; Li Huang; Jian-Hong Xing; Shi-Pin Chen; Chi-Lien Cheng; Wei Chen (Trees, 2013)

Evaluation of Burma Reed as Substrate for Production of Pleurotus eryngii - Xian-lu Zeng; Jun-fang Lin; Li-qiong Guo; Rong-wei Cao; Wei-qiang Zeng (Indian Journal of Microbiology, 2013)

Isolation and characterization of Histone1 gene and its promoter from tea plant (Camellia sinensis) - Wanping Fang; Yue Zhang; Lin Zhou; Weidong Wang; Xinghui Li (Molecular Biology Reports, 2013)

TGFβ1 Treatment Reduces Hippocampal Damage, Spontaneous Recurrent Seizures, and Learning Memory Deficits in Pilocarpine-Treated Rats - Liang-Yong Li; Jia-Lin Li; Hui-Min Zhang; Wen-Ming Yang; Kai Wang; Yuan Fang; Yu Wang (Journal of Molecular Neuroscience, 2013)

Analysis of B-Class Genes NAP3L3 and NAP3L4 in Narcissus tazetta var. chinensis - Xiao-Fang Li; Jing Xu; Ru Yang; Lin-Yan Jia; Xin-Jie Deng; Li-Jun Xiong; Xue-Ping Zhang; Qi Fang; Wei Zhang; Yue Sun; Ling Xu (Plant Molecular Biology Reporter, 2013)

The enhancement of biofilm formation in Group B streptococcal isolates at vaginal pH - Yueh-Ren Ho; Chien-Ming Li; Chen-Hsiang Yu; Yuh-Jyh Lin; Ching-Ming Wu; I-Chen Harn; Ming-Jer Tang; Yi-Ting Chen; Fang-Chi Shen; Chien-Yi Lu; Tai-Chun Tsai; Jiunn-Jong Wu (Medical Microbiology and Immunology, 2013)

Chemical Composition and Sensory Evaluation of Fermented Tea with Medicinal Mushrooms - Wei-Fang Bai; Xin-Yue Guo; Li-Qing Ma; Li-Qiong Guo; Jun-Fang Lin (Indian Journal of Microbiology, 2013)

Lack of effect of continuous glycyrrhizin administration on the pharmacokinetics of the P-glycoprotein substrate talinolol in healthy volunteers - Miao Yan; Ping-Fei Fang; Huan-De Li; Ping Xu; Yi-Ping Liu; Feng Wang; Hua-Lin Cai; Qin-You Tan (European Journal of Clinical Pharmacology, 2013)

Overexpression of ZmAFB2, the maize homologue of AFB2 gene, enhances salt tolerance in transgenic tobacco - Chunwen Yang; Wei Deng; Ning Tang; Xiaomin Wang; Fang Yan; Dongbo Lin; Zhengguo Li (Plant Cell, Tissue and Organ Culture (PCTOC), 2013)

Suggestion of GLYAT gene underlying variation of bone size and body lean mass as revealed by a bivariate genome-wide association study - Yan-Fang Guo; Li-Shu Zhang; Yong-Jun Liu; Hong-Gang Hu; Jian Li; Qing Tian; Ping Yu; Feng Zhang; Tie-Lin Yang; Yan Guo; Xiang-Lei Peng; Meng Dai; et al. (Human Genetics, 2013)

Changes in Rice Allelopathy and Rhizosphere Microflora by Inhibiting Rice Phenylalanine Ammonia-lyase Gene Expression - Changxun Fang; Yuee Zhuang; Tiecheng Xu; Yingzhe Li; Yue Li; Wenxiong Lin (Journal of Chemical Ecology, 2013)

A New Elasto-Viscoplastic Damage Model Combined with the Generalized Hoek–Brown Failure Criterion for Bedded Rock Salt and its Application - Lin-jian Ma; Xin-yu Liu; Qin Fang; Hong-fa Xu; Hui-min Xia; Er-bing Li; Shi-gang Yang; Wen-pei Li (Rock Mechanics and Rock Engineering, 2013)

Bacterial and Archaeal Symbionts in the South China Sea Sponge Phakellia fusca: Community Structure, Relative Abundance, and Ammonia-Oxidizing Populations - Minqi Han; Fang Liu; Fengli Zhang; Zhiyong Li; Houwen Lin (Marine Biotechnology, 2012)

Antioxidant system of tea (Camellia sinensis) leaves in response to phosphorus supply - Zheng-He Lin; Li-Song Chen; Rong-Bing Chen; Fang-Zhou Zhang (Acta Physiologiae Plantarum, 2012)

Increased Th17 cell frequency concomitant with decreased Foxp3+ Treg cell frequency in the peripheral circulation of patients with carotid artery plaques - Zhen-dong Liu; Lin Wang; Fang-hong Lu; Hui Pan; Ying-xin Zhao; Shu-jian Wang; Shang-wen Sun; Cui-ling Li; Xiao-liang Hu (Inflammation Research, 2012)

Complete genome sequence of narcissus late season yellows virus infecting Chinese narcissus in China - Shuang-Qing Lin; Jian-Guo Shen; Fang-Luan Gao; Wei Cai; Zhen Huang; Li-Yan Xie; Zu-Jian Wu (Archives of Virology, 2012)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

Identification of a heat shock cognate protein 70 gene in Chinese soft-shell turtle (Pelodiscus sinensis) and its expression profiles under thermal stress - Xiao-liang Li; Yue Kang; Xiao-yan Zhang; Bing-lin Zhu; Wei-huan Fang (Journal of Zhejiang University-SCIENCE B, 2012)

Diversity of potential pathogenicity and biofilm formation among Burkholderia cepacia complex water, clinical, and agricultural isolates in China - Muhammad Ibrahim; Qiaomei Tang; Yu Shi; Abdulwareth Almoneafy; Yuan Fang; Liuhu Xu; Wen Li; Bin Li; Guan-Lin Xie (World Journal of Microbiology and Biotechnology, 2012)

Interaction between iron plaque and root border cells ameliorates aluminum toxicity of Oryza sativa differing in aluminum tolerance - Miao-Zhen Cai; Shu-Na Zhang; Cheng-Hua Xing; Fang-Mei Wang; Lei Zhu; Ning Wang; Li-Yu Lin (Plant and Soil, 2012)

The expression level of Rosa Terminal Flower 1 (RTFL1) is related with recurrent flowering in roses - Li-Na Wang; Yun-Feng Liu; Yu-Man Zhang; Rong-Xiang Fang; Qing-Lin Liu (Molecular Biology Reports, 2012)

Overexpression of microRNA-378 attenuates ischemia-induced apoptosis by inhibiting caspase-3 expression in cardiac myocytes - Ji Fang; Xiao-Wei Song; Jing Tian; Hu-Yan Chen; Dong-Feng Li; Jian-Fei Wang; An-Jing Ren; Wen-Jun Yuan; Li Lin (Apoptosis, 2012)

Vancomycin-loaded nano-hydroxyapatite pellets to treat MRSA-induced chronic osteomyelitis with bone defect in rabbits - Ji-Le Jiang; Yun-Fei Li; Tao-Lin Fang; Jian Zhou; Xi-Lei Li; Yi-Chao Wang; Jian Dong (Inflammation Research, 2012)

Strontium Ranelate Prevents Bone Loss in a Rat Model of Localized Muscle Paralysis - Zhi-Feng Sheng; Yu-Lin Ma; Dejun Tong; De-Yu Fang; Qing-Chun Liang; Li-Hong Liu; Jian Zhang; Er-Yuan Liao (Annals of Biomedical Engineering, 2012)

Molecular Cloning, Sequence Analysis, and Expression of the Polygalacturonase-inhibiting Protein (PGIP) Gene in Mulberry - Dongqing Hu; Ruiqiang Dai; Yuhua Wang; Yinghua Zhang; Zhaoyue Liu; Rongjun Fang; Weiguo Zhao; Long Li; Qiang Lin; Liu Li (Plant Molecular Biology Reporter, 2012)

In Vitro Toxicity Evaluation of 25-nm Anatase TiO2 Nanoparticles in Immortalized Keratinocyte Cells - Jin Chan; Tang Ying; Yang F. Guang; Li X. Lin; Tang Kai; Zhang Y. Fang; Ye X. Ting; Lin F. Xing; Yang Y. Ji (Biological Trace Element Research, 2011)

Positive allelopathic stimulation and underlying molecular mechanism of achyranthe under continuous monoculture - Zhen-Fang Li; Zi-Guan Zhang; Dong-Feng Xie; Lin-Quan Dai; Lan-Fang Zhu; Ji Li; Zong-Quan Liu; Yan-Qiu Yang; Lin-Kun Wu; Mu-Ji Huang; Zhong-Yi Zhang; Wen-Xiong Lin (Acta Physiologiae Plantarum, 2011)

The relationship between competitive ability and yield stability in an old and a modern winter wheat cultivar - Yan Fang; Lin Liu; Bing-Cheng Xu; Feng-Min Li (Plant and Soil, 2011)

Genome-wide analysis of OCT4 binding sites in glioblastoma cancer cells - Xue-feng Fang; Wei-yi Zhang; Na Zhao; Wei Yu; Dong Ding; Xu Hong; Li-sha Li; Hua-rong Zhang; Shu Zheng; Biao-yang Lin (Journal of Zhejiang University-SCIENCE B, 2011)

A butterfly hotspot in western China, its environmental threats and conservation - Xiu-shan Li; Ya-lin Zhang; Jian-hui Fang; Oliver Schweiger; Josef Settele (Journal of Insect Conservation, 2011)

Modulation of endogenous peroxidase by exogenous peroxidase in chinese red radish seedling - Li Wang; Lan Wang; Fang-Jun Li; Lin-Song Wang; Myeong-Hyeon Wang (Horticulture, Environment, and Biotechnology, 2011)

Calcitonin gene-related peptide released from endothelial progenitor cells inhibits the proliferation of rat vascular smooth muscle cells induced by angiotensin II - Li Fang; Mei-Fang Chen; Zhi-Lin Xiao; Yin Liu; Guo-Long Yu; Xiao-Bin Chen; Xiu-Mei Xie (Molecular and Cellular Biochemistry, 2011)

Identification of three immediate-early genes of white spot syndrome virus - Fanyu Lin; He Huang; Limei Xu; Fang Li; Feng Yang (Archives of Virology, 2011)

Ningdong granule: a complementary and alternative therapy in the treatment of attention deficit/hyperactivity disorder - Ji-Jun Li; Zai-Wang Li; Shu-Zhen Wang; Fang-Hua Qi; Lin Zhao; Hong Lv; An-Yuan Li (Psychopharmacology, 2011)

Estimation of cancer cases and deaths attributable to infection in China - Wang Xiang; Ju-Fang Shi; Ping Li; Jian-Bing Wang; Li-Na Xu; Wen-Qiang Wei; Fang-Hui Zhao; You-Lin Qiao; Paolo Boffetta (Cancer Causes & Control, 2011)

PPARγ Agonist Suppresses TLR4 Expression and TNF-α Production in LPS Stimulated Monocyte Leukemia Cells - Chun-Zhi Wang; Yong Zhang; Xu-Dong Li; Yuan Hu; Zhi-Gang Fang; Dong-Jun Lin; Ruo-Zhi Xiao; Ren-Wei Huang; He-Qing Huang; Pei-Qing Liu; Jia-Jun Liu (Cell Biochemistry and Biophysics, 2011)

Novel Fluorescent Molecular Clips: Selective Recognition Towards Fe3+ in Aqueous Solution - Lin Li; Neng-fang She; Zhuan Fei; Pui-kin So; Yu-zhou Wang; Li-ping Cao; An-xin Wu; Zhong-ping Yao (Journal of Fluorescence, 2011)

Trichodermanin A, a novel diterpenoid from endophytic fungus culture - Pei-Xin Sun; Cheng-Jian Zheng; Wen-Chao Li; Gui-Lin Jin; Fang Huang; Lu-Ping Qin (Journal of Natural Medicines, 2011)

Production, purification and characterization of a thermostable laccase from a tropical white-rot fungus - Li-Qiong Guo; Shuo-Xin Lin; Xiao-Bing Zheng; Zi-Rou Huang; Jun-Fang Lin (World Journal of Microbiology and Biotechnology, 2011)

Prevention of cerebral ischemia-induced memory deficits by inhibition of phosphodiesterase-4 in rats - Ling-Xia Li; Yu-Fang Cheng; Huan-Bing Lin; Chuang Wang; Jiang-Ping Xu; Han-Ting Zhang (Metabolic Brain Disease, 2011)

Geochemical and zircon U–Pb study of the Huangmeijian A-type granite: implications for geological evolution of the Lower Yangtze River belt - He Li; Hong Zhang; Ming-Xing Ling; Fang-Yue Wang; Xing Ding; Ji-Bin Zhou; Xiao-Yong Yang; Xiang-Lin Tu; Weidong Sun (International Geology Review, 2011)

Genotype and host range analysis of infectious spleen and kidney necrosis virus (ISKNV) - Xiaozhe Fu; Ningqiu Li; Lihui Liu; Qiang Lin; Fang Wang; Yingtiao Lai; Haiming Jiang; Houjun Pan; Cunbin Shi; Shuqin Wu (Virus Genes, 2011)

Point patterns of tree distribution determined by habitat heterogeneity and dispersal limitation - Yi-Ching Lin; Li-Wan Chang; Kuoh-Cheng Yang; Hsiang-Hua Wang; I-Fang Sun (Oecologia, 2011)

Molecular phylogeny of Ranunculaceae based on rbc L sequences - Ying-fan Cai; Sheng-wei Li; Min Chen; Ming-feng Jiang; Yi Liu; Yong-fang Xie; Quan Sun; Huai-zhong Jiang; Neng-wen Yin; Ling Wang; Rui Zhang; Cheng-lin Huang; et al. (Biologia, 2010)

Inhibition of phosphodiesterase-4 reverses memory deficits produced by Aβ25–35 or Aβ1–40 peptide in rats - Yu-Fang Cheng; Chuang Wang; Huan-Bing Lin; Yun-Feng Li; Ying Huang; Jiang-Ping Xu; Han-Ting Zhang (Psychopharmacology, 2010)

Angiotensin-converting enzyme 2 (ACE2) proteins of different bat species confer variable susceptibility to SARS-CoV entry - Yuxuan Hou; Cheng Peng; Meng Yu; Yan Li; Zhenggang Han; Fang Li; Lin-Fa Wang; Zhengli Shi (Archives of Virology, 2010)

Characterization of the Scutellaria barbata glycosyltransferase gene and its promoter - Shu-Jiau Chiou; Wen-Yu Liu; Cheng-Li Fang; Tsai-Yun Lin (Planta, 2010)

Isolation and characterization of polymorphic microsatellite loci in Aquilaria sinensis (Lour.) Gilg - Yan-Ting Zhang; Zheng-Feng Wang; Hong-Lin Cao; Xiao-Yi Li; Lin-Fang Wu; Shu-Bin Zhuo; Xiao-Feng Huang (Conservation Genetics Resources, 2010)

Relation of uric acid levels to aortic root dilatation in hypertensive patients with and without metabolic syndrome - Li-jiang Tang; Jian-jun Jiang; Xiao-feng Chen; Jian-an Wang; Xian-fang Lin; Yu-xi Du; Cong-feng Fang; Zhao-xia Pu (Journal of Zhejiang University-SCIENCE B, 2010)

Over-expression of the AtGA2ox8 gene decreases the biomass accumulation and lignification in rapeseed (Brassica napus L.) - Xiao-ying Zhao; Deng-feng Zhu; Bo Zhou; Wu-sheng Peng; Jian-zhong Lin; Xing-qun Huang; Re-qing He; Yu-hong Zhuo; Dan Peng; Dong-ying Tang; Ming-fang Li; Xuan-ming Liu (Journal of Zhejiang University-SCIENCE B, 2010)

Livin abrogates apoptosis of SPC-A1 cell by regulating JNKI signaling pathway - Yu-Sheng Chen; Hong-Ru Li; Ming Lin; Gang Chen; Bao-Song Xie; Neng-Luan Xu; Li-Fang Lin (Molecular Biology Reports, 2010)

Registration of Micro-Computed Tomography and Histological Images of the Guinea Pig Cochlea to Construct an Ear Model Using an Iterative Closest Point Algorithm - Chia-Fone Lee; Gen-Jia Li; Shu-Yen Wan; Wen-Jeng Lee; Kai-Yuan Tzen; Chiung-Hsiang Chen; Yu-Lin Song; Yuan-Fang Chou; Yuh-Shyang Chen; Tien-Chen Liu (Annals of Biomedical Engineering, 2010)

Characterization of Burkholderia cepacia complex from cystic fibrosis patients in China and their chitosan susceptibility - Yuan Fang; Miao-miao Lou; Bin Li; Guan-Lin Xie; Fang Wang; Li-Xin Zhang; Yuan-Chan Luo (World Journal of Microbiology and Biotechnology, 2010)

Subtype identification of the novel A H1N1 and other human influenza A viruses using an oligonucleotide microarray - Xiaoping Kang; Yongqiang Li; Honghe Sun; Weili Wu; Hong Liu; Fang Lin; Chenfeng Qing; Guohui Chang; Qingyu Zhu; Weijun Chen; Yinhui Yang (Archives of Virology, 2010)

Human papillomavirus type-distribution in cervical cancer in China: the importance of HPV 16 and 18 - Wen Chen; Xun Zhang; Anco Molijn; David Jenkins; Ju-Fang Shi; Wim Quint; Johannes E. Schmidt; Ping Wang; Yu-Ling Liu; Lian-Kun Li; Hong Shi; Ji-Hong Liu; et al. (Cancer Causes & Control, 2009)

Gene mapping and expression analysis of a novel mutantreproduce organs absent (roa) in rice - Nan Wang; Xian-Chun Sang; Yun-Feng Li; Ying-Hua Ling; Fang-Ming Zhao; Zheng-Lin Yang; Guang-Hua He (Genes & Genomics, 2009)

A novel triple-regulated oncolytic adenovirus carrying PDCD5 gene exerts potent antitumor efficacy on common human leukemic cell lines - Min Xie; Ji-Hong Niu; Yan Chang; Qi-Jun Qian; Hong-Ping Wu; Lin-Fang Li; Yao Zhang; Jin-Lan Li; Xiao-Jun Huang; Guo-Rui Ruan (Apoptosis, 2009)

Takayasu’s arteritis associated with Crohn’s disease - You-shi Liu; You-hong Fang; Ling-xiang Ruan; You-ming Li; Lin Li; Ling-ling Jiang (Journal of Zhejiang University-SCIENCE B, 2009)

Memory deficits and neurochemical changes induced by C-reactive protein in rats: implication in Alzheimer’s disease - Huan-Bing Lin; Xue-Mei Yang; Tie-Jun Li; Yu-Fang Cheng; Han-Ting Zhang; Jiang-Ping Xu (Psychopharmacology, 2009)

Reversal of coenzyme specificity and improvement of catalytic efficiency of Pichia stipitis xylose reductase by rational site-directed mutagenesis - Qi-Kai Zeng; Hong-Li Du; Jing-Fang Wang; Dong-Qing Wei; Xiao-Ning Wang; Yi-Xue Li; Ying Lin (Biotechnology Letters, 2009)

Comparison of human post-embryonic, multipotent stem cells derived from various tissues - Baijun Fang; Ning Li; Yongping Song; Quande Lin; Robert Chunhua Zhao (Biotechnology Letters, 2009)

Establishment of cell lines using a doxycycline-inducible gene expression system to regulate expression of hepatitis B virus X protein - Hong Tang; Li Liu; Feng-Jun Liu; En-Qiang Chen; Seishi Murakami; Yong Lin; Fang He; Tao-You Zhou; Fei-Jun Huang (Archives of Virology, 2009)

Effects of cannabinoid CB1 receptor antagonist rimonabant in consolidation and reconsolidation of methamphetamine reward memory in mice - Lu-lu Yu; Xue-yi Wang; Mei Zhao; Yu Liu; Yan-qin Li; Fang-qiong Li; Xiaoyi Wang; Yan-xue Xue; Lin Lu (Psychopharmacology, 2009)

Effect of CO2 enrichment on the glucosinolate contents under different nitrogen levels in bolting stem of Chinese kale (Brassica alboglabra L.) - Gui-xiao La; Ping Fang; Yi-bo Teng; Ya-juan Li; Xian-yong Lin (Journal of Zhejiang University-SCIENCE B, 2009)

Recombinant ORF66 and ORFK12 antigens for the detection of human herpesvirus 8 antibodies in HIV-positive and -negative patients - Tsuey-Ching Yang; Chun-Pin Chang; Yu-Ching Lan; Chao-Li Liu; Mu-Chin Shih; Fang-Yang Wu; Cheng-Wen Lin (Biotechnology Letters, 2009)

Spinal cord decompression reduces rat neural cell apoptosis secondary to spinal cord injury - Kan Xu; Qi-xin Chen; Fang-cai Li; Wei-shan Chen; Min Lin; Qiong-hua Wu (Journal of Zhejiang University-SCIENCE B, 2009)

Molecular characterisation of two plasmids from paulownia witches’-broom phytoplasma and detection of a plasmid-encoded protein in infected plants - Cai-Li Lin; Tao Zhou; Huai-Fang Li; Zai-Feng Fan; Yong Li; Chun-Gen Piao; Guo-Zhong Tian (European Journal of Plant Pathology, 2009)

Genome-wide association scan for stature in Chinese: evidence for ethnic specific loci - Shu-Feng Lei; Tie-Lin Yang; Li-Jun Tan; Xiang-Ding Chen; Yan Guo; Yan-Fang Guo; Liang Zhang; Xiao-Gang Liu; Han Yan; Feng Pan; Zhi-Xin Zhang; Yu-Mei Peng; et al. (Human Genetics, 2009)

Occurrence and diversity of Pichia spp. in marine environments - Jing Li; Zhenming Chi; Xianghong Wang; Lin Wang; Jun Sheng; Fang Gong (Journal of Ocean University of China, 2008)

White-spot disease of Chinese soft-shelled turtles (Trionyx sinens) caused by Paecilomyces lilacinus - Xiao-liang Li; Chu-long Zhang; Wei-huan Fang; Fu-cheng Lin (Journal of Zhejiang University-SCIENCE B, 2008)

Evolutionary and functional study of the CDPK gene family in wheat (Triticum aestivum L.) - Ai-Li Li; Yuan-Fang Zhu; Xiao-Mei Tan; Xiang Wang; Bo Wei; Han-Zi Guo; Zeng-Lin Zhang; Xiao-Bo Chen; Guang-Yao Zhao; Xiu-Ying Kong; Ji-Zeng Jia; Long Mao (Plant Molecular Biology, 2008)

Solid Substrate–Room Temperature Phosphorimetry for the Determination of Trace Terbutaline Sulfate Based on Its Inhibition Oxidation of Rhodamine 6G by Sodium Periodate - Jia-Ming Liu; Fei Gao; Wen-Yan Gao; Li-Qing Zeng; Xiao-Mei Huang; Zhi-Ming Li; Xiu-Chai Huang; Wei-Nv Lin; Fang-Mei Wang; Chang-Ling Nie (Journal of Fluorescence, 2008)

A novel thioredoxin reductase inhibitor inhibits cell growth and induces apoptosis in HL-60 and K562 cells - Zuo-fu Peng; Lin-xiang Lan; Fang Zhao; Jing Li; Qiang Tan; Han-wei Yin; Hui-hui Zeng (Journal of Zhejiang University-SCIENCE B, 2008)

Expression and characteristic of synthetic human epidermal growth factor (hEGF) in transgenic tobacco plants - Jie-Ying Bai; Lin Zeng; Yuan-Lei Hu; Yan-Fang Li; Zhong-Ping Lin; Shi-Chen Shang; Yan-Sheng Shi (Biotechnology Letters, 2007)

A rice phenomics study—phenotype scoring and seed propagation of a T-DNA insertion-induced rice mutant population - Chyr-Guan Chern; Ming-Jen Fan; Su-May Yu; Ai-Ling Hour; Po-Chang Lu; Yao-Cheng Lin; Fu-Jin Wei; Sheng-Chung Huang; Shu Chen; Ming-Hsing Lai; Ching-Shan Tseng; Hsing-Mu Yen; et al. (Plant Molecular Biology, 2007)

Selection of Yarrowia lipolytica strains with high protein content from yeasts isolated from different marine environments - Zhenming Chi; Fang Wang; Lin Wang; Jing Li; Xianghong Wang (Journal of Ocean University of China, 2007)

A follow-up study of mortality among the arseniasis patients exposed to indoor combustion of high arsenic coal in Southwest Guizhou Autonomous Prefecture, China - Ji-gang Chen; Yu-gang Chen; Yun-shu Zhou; Guo-fang Lin; Xiu-jie Li; Chao-gang Jia; Wei-chao Guo; Hui Du; Hong-chao Lu; Hong Meng; Xin-jiang Zhang; Klaus Golka; et al. (International Archives of Occupational and Environmental Health, 2007)

Cloning and identification of partial DNA fragment for the B mating-type factor in Lentinula edodes using degenerate PCR - An-Zheng Li; Xue-Feng Xu; Fan-Xue Lin; Shui-Ming Cheng; Fang-Can Lin (World Journal of Microbiology and Biotechnology, 2007)

A rice gene activation/knockout mutant resource for high throughput functional genomics - Yue-Ie Hsing; Chyr-Guan Chern; Ming-Jen Fan; Po-Chang Lu; Ku-Ting Chen; Shuen-Fang Lo; Peng-Kai Sun; Shin-Lon Ho; Kuo-Wei Lee; Yi-Chieh Wang; Wen-Lii Huang; Swee-Suak Ko; et al. (Plant Molecular Biology, 2007)

A High CO Episode of Long-Range Transport Detected by MOPITT - Chunsheng Zhao; Li Peng; Xuexi Tie; Yunping Lin; Chengcai Li; Xiangdong Zheng; Yuanyuan Fang (Water, Air, & Soil Pollution, 2007)

Protoplast Fusion between Geotrichum candidium and Phanerochaete chrysosporium to Produce Fusants for Corn Stover Fermentation - Yong Zhang; Shu-Mei Lin; Yu-Jing Zhu; Chang-Jiang Liu; Yan Dong; Fang-Fang Li; Gao-Feng Wu; Hai-Yan Wang; Jing-Hai Zhang (Biotechnology Letters, 2006)

Dynamic analysis of hepatoma spheroid formation: roles of E-cadherin and β1-integrin - Ruei-Zeng Lin; Li-Fang Chou; Chi-Chen Michael Chien; Hwan-You Chang (Cell and Tissue Research, 2006)

Effect of fenofibrate on the level of asymmetric dimethylarginine in individuals with hypertriglyceridemia - Tian-Lun Yang; Mei-Fang Chen; Xin Xia; Bai-Lin Luo; Yuan-Jian Li (European Journal of Clinical Pharmacology, 2006)

Changes in Soil Properties After Establishment of Artemisia halodendron and Caragana microphylla on Shifting Sand Dunes in Semiarid Horqin Sandy Land, Northern China - Yong Zhong Su; Tong Hui Zhang; Yu Lin Li; Fang Wang (Environmental Management, 2005)

Genetic Diversity and Genetic Structure of an Endangered Species, Trillium tschonoskii - Qun Li; Meng Xiao; Liang Guo; Li Wang; Lin Tang; Ying Xu; Fang Yan; Fang Chen (Biochemical Genetics, 2005)

Fenofibrate decreases asymmetric dimethylarginine level in cultured endothelial cells by inhibiting NF-κB activity - Tian-Lun Yang; Mei-Fang Chen; Bai-Lin Luo; Qi-Ying Xie; Jun-Lin Jiang; Yuan-Jian Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2005)

Nucleotide Sequences and Functions of the Epstein-Barr Virus Latent Membrane Protein 1 Genes Isolated from Salivary Gland Lymphoepithelial Carcinomas - Kai Yu Jen; Masaya Higuchi; Jun Cheng; Jiang Li; Lan Yan Wu; Ying Fang Li; Han Liang Lin; Zhilong Chen; Vladimir Gurtsevitch; Masahiro Fujii; Takashi Saku (Virus Genes, 2005)

Eudragit E Accelerated the Diketopiperazine Formation of Enalapril Maleate Determined by Thermal FTIR Microspectroscopic Technique - Shun-Li Wang; Shan-Yang Lin; Ting-Fang Chen; Wen-Ting Cheng (Pharmaceutical Research, 2004)

Effect of fenofibrate on LDL-induced endothelial dysfunction in rats - Tian-Lun Yang; Mei-Fang Chen; Bai-Ling Luo; Jing Yu; Jun-Lin Jiang; Yuan-Jian Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2004)

Cloning and Characterization of the First Cnidarian ADP-Ribosylation Factor, and Its Involvement in the Aiptasia-Symbiodinum Endosymbiosis - Ming-Chyuan Chen; Ying-Min Cheng; Li-Hsueh Wang; Chorng-Horng Lin; Xing-Yan Huang; Ming-Chin Liu; Ping-Jyun Sung; Lee-Shing Fang (Marine Biotechnology, 2004)

Sequence Analysis of the Complete Genome of Rice Black-Streaked Dwarf Virus Isolated from Maize with Rough Dwarf Disease - Zhao-Hui Wang; Shou-Guo Fang; Jia-Ling Xu; Li-Ying Sun; Da-Wei Li; Jia-Lin Yu (Virus Genes, 2003)

Chloroplast Transformation in Oilseed Rape - Bing-Kai Hou; Yi-Hua Zhou; Li-Hong Wan; Zhong-Lin Zhang; Gui-Fang Shen; Zheng-Hua Chen; Zan-Min Hu (Transgenic Research, 2003)

RAPD markers in diversity detection and variety identification of Tibetan hulless barley - Zeng Yu; Lan Li-Qiong; Luo Huan; Bai Jie; Yang Man-Ye; Miao Chen; Cai Ying-Fan; Qiang Xiao-Lin; Chen Fang (Plant Molecular Biology Reporter, 2002)

Suppression subtractive hybridization cloning of cDNAs of differentially expressed genes in dovetree (Davidia involucrata) bracts - Yun-Xiang Li; Li Chen; Lin Juan; Yufeng Li; Fang Chen (Plant Molecular Biology Reporter, 2002)

Study on methods of land use dynamic monitoring at county level - Lin-yi Li; Fang Huang; Zhao-li Liu; En-pu Wan (Chinese Geographical Science, 2001)

Chemical characters and antioxidative properties of sulfated polysaccharides from Laminaria japonica - Chang-Hu Xue; Yu Fang; Hong Lin; Lei Chen; Zhao-Jie Li; Deng Deng; Chong-Xiao Lu (Journal of Applied Phycology, 2001)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)